Sperm morphology, functionality, and cryopreservation challenges in wild Ocellate River stingrays Potamotrygon motoro - Nathalia dos Santos Teixeira; Jhony Lisbôa Benato; Rômulo Batista Rodrigues; Eduardo Thome Nicoleti; Larise Caroline Oliveira Lima; Louise Nex Spica; Lis Santos Marques; Lorrânny Pereira de Assis Valadares; Pedro Nacib Jorge-Neto; Jayme Aparecido Povh; Mônica Rodrigues Ferreira Machado; Danilo P. Streit Jr (Tissue and Cell, 2027)

PACme: A versatile computer code for simulation and analysis of TDPAC spectra with generalized time-dependent magnetic and electric quadrupole hyperfine fields - M.B. Barbosa; J.G. Correia; P. Rocha-Rodrigues; J.P. Araújo (Computer Physics Communications, 2026)

A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

Molecular surveillance of Bordetella pertussis during the 2024 outbreak in Southeast Brazil: allelic profiles and comparison to vaccine strain - Thiago J. Sousa; Felipe D. Gatti; Joana Z. Nodari; Gabriela C. de Mendonça; Anna Clara G. Có; Thabata C. D. Damasceno; Nayara C. Silva; Lílian S. Lavagnoli; Danielle G. P. Lyra; Jaqueline P. Goulart; Rodrigo Ribeiro-Rodrigues (Brazilian Journal of Microbiology, 2026)

Topography- and depth-driven variability of β-glucosidase activity in Amazonian Forest soils (Brazil): A machine learning and structural equation modeling approach - Gizachew Ayalew Tiruneh; Ciro Abbud Righi; Jefferson Lordello Polizel; Vinicius Gonçalves; Carlos Rodrigues Pereira; Fernando Dini Andreote; Rafael Lima Oliveira; Jean Jesus Macedo Novais; Marcelo Henrique Procópio Pelegrino; Jose Alexandre Melo Dematte; Marcelino Carneiro Guedes; Ranjith P. Udawatta (CATENA, 2026)

Kogia Records in Brazilian Equatorial and Southwestern Atlantic Oceans - Joao Pedro M. Mura; Raphael B. Machado; Yasmin P. Viana; Natalia Rodrigues‐Soares; Giovanne A. Ferreira; Larissa Kelmer L. Kascher; Barbara S. Silva; Lucia O. Alencar; Gabrieli M. Rodrigues; Franciele R. de Castro; Daniela F. Godoy; Jose L. Pizzorno; et al. (Marine Mammal Science, 2026)
The pygmy ( Kogia breviceps ) and dwarf ( Kogia sima ) sperm whales are cryptic cetaceans characterized by inconspicuous surfacing behavior, small group sizes, and deep‐diving habits, making visual detection particularly challenging. Here, we present the first broad‐scale passive acoustic monitoring (PAM) assessment of Kogia spp. occurrence along the Brazilian coast, spanning both the Equatorial Atlantic Ocean (EAO) and Southwestern Atlantic Ocean (SWAO). Across 25 survey campaigns, 504 survey days, and more than 6441 h of acoustic recordings, 94 acoustic detections were identified, predominantly within the Brazilian Equatorial Margin (BEM), resulting in substantially higher detection‐per‐unit‐effort values in the EAO than in the SWAO. Two rare visual‐acoustic encounters of Kogia sima were also documented, including one detection incorporated into the dataset. A total of 2796 echolocation clicks were analyzed, exhibiting the characteristic narrow‐band high‐frequency acoustic profile of Kogia spp. (mean peak frequency = 126.2 ± 3.8 kHz; mean −3 dB bandwidth = 4.7 ± 2.56 kHz; mean inter‐click interval = 141 ± 97 ms). Detections occurred across a broad bathymetric range (9–4411 m), and kernel density analyses revealed spatial heterogeneity in occurrence patterns, with recurrent detection areas concentrated within the BEM. Collectively, these findings demonstrate the effectiveness of PAM for studying elusive deep‐diving cetaceans and provide an important baseline for future ecological monitoring, impact assessment, and conservation efforts targeting Kogia spp. in the western Atlantic.

Correlating polymer solution and membrane fabrication with morphological and permeation properties of cellulose acetate ultrafiltration membranes - Rita F. Pires; Margarida P. Valente; Flávia S.C. Rodrigues; Ana Charas; Mónica Faria (Carbohydrate Polymers, 2026)

eDNA-based assessment of microbial dynamics in response to persistent contaminants and degraded water quality in a hypereutrophic urban reservoir - Juliana S. M. Pimentel; Maria Clara V. M. Starling; Camila C. Amorim; Valquíria F. L. Viana; Alessandra S. Martins; Daniel A. S. Rodrigues; Luciana P. M. Brandão; Nadieh de Jonge; Niels O. G. Jørgensen; Louise Schlüter; Matt Simcik; Jeppe Lund Nielsen (Environmental Monitoring and Assessment, 2026)
Urban freshwater ecosystems are increasingly exposed to mixtures of pollutants, including per- and polyfluoroalkyl substances (PFAS). However, their ecological effects remain poorly understood, especially in tropical regions with limited sanitation infrastructure. This study investigated PFAS contamination, water quality, and microbial community structure in Pampulha Lake, a tropical urban reservoir in southeastern Brazil. Spatiotemporal patterns in prokaryotic and eukaryotic diversity were assessed over a year (2022–2023) using environmental DNA metabarcoding of 16S and 18S rRNA genes by integrating taxonomic data with PFAS concentrations and water quality. Physicochemical and multivariate analyses revealed strong seasonal and spatial heterogeneity, influenced by eutrophication, hydrological variability, and pollution gradients. Among the seven PFAS detected above quantification limits, PFBS and PFOA were the most common. Prokaryotic communities showed significant correlations with PFAS, especially with sulfonated forms, while eukaryotic communities were more stable. Diversity patterns highlighted microbial community sensitivity to environmental stress. Overall, results indicate that PFAS influenced microbial assemblages, supporting their inclusion in monitoring frameworks, and eDNA was proved effective for assessing ecological risks in tropical urban reservoirs.

From invasive nuisance to biotechnological asset: LC–MS/MS chemical profiling and pharmacological potential of ascidian Styela plicata from Albufeira Lagoon, Portugal - Maria João Nunes; Catarina M. Luís; Vanda Marques; Bárbara Gonçalves; Luís C. Branco; Cecília M. P. Rodrigues; Rita G. Sobral; Susana P. Gaudêncio (Environmental Science and Pollution Research, 2026)

Spatial Scale Modulates the Effect of Habitat Amount on Diversity Patterns of Arachnid Assemblages Across Different Brazilian Ecosystems - André F. A. Lira; Adriano M. DeSouza; Thayna R. Brito‐Almeida; Hugo L. L. Neves; Gilberto G. Rodrigues; Carlos Henrique De‐Oliveira‐Nogueira; Ubiratã F. Souza; Alessandra R. S. Andrade; Rafael G. Jansen; Ana Lúcia Tourinho; Leonardo S. Carvalho; Laís M. Pordeus; et al. (Journal of Biogeography, 2026)
Aim We evaluated how native vegetation cover influences the diversity of arachnid assemblages across multiple spatial scales in major Brazilian ecosystems. Location Brazil (Amazon and Atlantic rainforests, Cerrado savanna and Caatinga dry forest). Taxon Arachnida (Opiliones, Pseudoscorpiones and Scorpiones). Methods We sampled arachnids at 120 sites using active search and litter sifting. Native vegetation cover was quantified at three spatial scales (100, 200 and 300 m buffers) using GIS data. Assemblage structure was assessed using abundance, species richness, and Hill numbers ( q = 0, 1 and 2). Generalized linear mixed models were used to evaluate responses across taxonomic groups and ecosystems. Results We recorded 3986 individuals from 179 species. Diversity responses to native vegetation cover were taxon‐, ecosystem‐ and scale‐dependent. Positive effects of vegetation cover were stronger and more consistent in rainforest than in savanna and dry forest ecosystems. In rainforests, most responses occurred at smaller spatial scales (100–200 m), whereas no significant effects were detected in the savanna. Opiliones richness showed limited variation with vegetation cover but differed in dominance structure among ecosystems. Scorpion assemblages were characterized by low richness and high dominance, while pseudoscorpions exhibited low evenness in more species‐rich sites, particularly in the Amazon. Main Conclusions Native vegetation cover plays an important role in structuring arachnid diversity in Brazil, but its effects vary across taxa, ecosystems and spatial scales. These findings highlight the need for taxon‐ and scale‐specific conservation strategies and reinforce the importance of multi‐scale approaches to biodiversity conservation in Neotropical landscapes under increasing anthropogenic pressure.

Inclusion of carotenoids and Eicosapentaenoic Acid (EPA) in sea urchin (Paracentrotus lividus) broodstock diets improves gonad development and oocyte quality - A. S. Gomes; A. F. Rodrigues; M. Neves; C. Roseiro; H. Cardoso; A. P. Violante; P. J. Gavaia; C. Suckling; S. Lourenço (Aquaculture International, 2026)

Using the capabilities approach to achieve people‐centered conservation - Arthur Rodrigues; Felipe P. L. Melo; Lucas Alencar; James Angus Fraser; Luke Parry (Conservation Biology, 2026)
Top‐down interventions carried out by state and nonstate institutions to conserve biodiversity and improve the lives of forest‐proximate people (FPP) in the Global South tend to reflect economistic understandings of human well‐being. More progressive and people‐centered conservation projects are guided by normative visions of how the world should be, yet these projects are limited because the social dimensions of project design, planning, and evaluation often remain focused on quantifiable aspects of well‐being. We demonstrated that considering human well‐being qualitatively in terms of freedom and dignity can help achieve rights‐based, people‐centered conservation. We applied the capabilities approach (CA), a social theory that emphasizes marginalized people's freedom to live a life they have reason to value. First, we reviewed English‐language literature to assess how the CA has been used conceptually and empirically to examine the well‐being of FPP. Based on 31 methodologically diverse studies from 16 countries, we found that equitable access to forest resources is essential for the flourishing of FPP, capability creation for FPP requires strong and local social institutions, and FPP's agency (a person's power to act and bring about change) to pursue valued capabilities is often deeply embedded in collective structures. Thus, we developed a framework to guide people‐centered conservation actions that promote the flourishing of FPP. We applied this framework to the Brazilian Caatinga dry forest, which is characterized by diverse use of forest resources and deep social inequities, and identified examples of conservation practices and their mixed influences on the lives of people in this biome. Adopting the CA can help ensure that people‐centered conservation initiatives uphold FPP's rights and prioritize their well‐being, while striving for sustainability.

Late Quaternary change in sources and burial of organic carbon off Northeastern Brazil - Alice Maria da S. Rodrigues; Rodrigo de L. Sobrinho; Patrícia Piacsek; Ioanna Bouloubassi; Arnaud Huguet; Ana Luiza S. Albuquerque; Igor M. Venancio; Thiago P. Santos; Joana F. Cruz; Marcelo C. Bernardes (Quaternary Science Reviews, 2026)

Thermal limits of estuarine amphipods and their implications for aquaculture production - Daniela P. Rodrigues; Luísa Marques; Joana Teixeira; João Ferreira; João P. Sousa; Rafael C. Duarte; Ricardo Calado (Marine Environmental Research, 2026)

Power dynamics in strategic environmental assessment: examining actors' relations in Portuguese urban planning processes - M. Pereira; M. Pereira; M.L. Fernandes; F. Teles; S. Moreno Pires; P. Silva; C. Rodrigues; C. Jalali; A. Polido (Environmental Impact Assessment Review, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The anterograde tarsal venography enhances vessel visualization compared to the retrograde approach in horses - Daniel L. Parra-Torres; Gabriel B. Melo-Neto; Hector O. Garcia; Ana Paula A. Souza; Emanuel Vitor P. Apolonio; Celso Antônio Rodrigues; Ana Liz G. Alves; Carlos Alberto Hussni; Marcos J. Watanabe (The Veterinary Journal, 2026)

Monte San Nicola (Sicily): Gelasian GSSP and base Quaternary/Pleistocene - L. Capraro; S. Bonomo; A. Incarbona; F.J. Hilgen; E. Zanola; A. Di Stefano; F. Dela Pierre; S. Ferraro; P. Ferretti; E. Fornaciari; S. Galeotti; P. Macrì; et al. (Quaternary Science Reviews, 2026)

Chemical pretreatment enhances vacuum filtration of slime-rich iron ore tailings - P. Muñoz; A. Azevedo; R. Rodrigues; J. Rubio (Minerals Engineering, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Ex vivo validation of osteogenic efficacy in a bioceramic dual drug-delivery system - Miguel A. Rodrigues; Liliana Grenho; Rita Araújo; João P. Borges; Maria H. Fernandes; Pedro S. Gomes; José D. Santos; Maria A. Lopes (Drug Delivery and Translational Research, 2026)

Evaluation of cross-reactivity of monoclonal antibodies against cytokines and cellular molecules of bovine and human origin to identify immunological markers in buffaloes (Bubalus bubalis) - Kelly M.G. Godoy; Maysa Serpa Gonçalves; Ana Carolina Chalfun de Sant'ana; Carine Rodrigues Pereira; Wanessa A. Carvalho; Fabrizio de Massis; Flavio Sacchini; Elaine M.S. Dorneles; Andrey P. Lage (Veterinary Immunology and Immunopathology, 2026)

Influence of the Amazon River plume on upper water column stratification in the western tropical Atlantic Ocean during the last 30 ka - P. Palhano; L. Sartori; L.F. Rodrigues; A.H. Augustin; M. Ketzer; M.A.G. Pivel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Synthesis and application of silver-doped glass waste pellets for drinking water treatment - J. S. C. Vieira; J. D. A. do Ano; A. R. Pereira; A. da Costa Reis; F. W. Carvalho; I. A. da Silva; M. R. de Melo Rodrigues; E. M. V. de Carvalho; D. L. P. Macuvele; G. J. Muchave (International Journal of Environmental Science and Technology, 2026)

Modeling Future Climate Impacts on Brazil’s Operational Wind and Solar Energy Capacity - Felipe Husadel Poyer; Francisco Lopes Lima; Rodrigo Santos Costa; André Rodrigues Gonçalves; Fernando R. Martins; André F. P. Lucena; Enio Bueno Pereira (Environmental Modeling & Assessment, 2026)
Over the past decade, the Brazilian electricity sector has undergone a profound transformation, driven by the large-scale deployment of wind and solar photovoltaic power plants, a trend that is expected to continue in the years ahead. Although the transition to these variable renewable energy resources helps to reduce greenhouse gas emissions and mitigate the climate crisis, they are vulnerable to the very climate changes they help to avert. This study uses projections from CMIP6 global climate models under two future scenarios (SSP2-4.5 and SSP5-8.5) to assess potential impacts on power generation in the existing centralized wind and solar power facilities in Brazil. The study innovates by assessing the effects of climate change on the future performance of the power plants using measured historical capacity factors as a proxy, thereby eliminating the need for climate bias correction and standardized manufacturer power curves. Projections indicate a nationwide increase in wind potential between 6% and 15% by the end of the century, contributing to an extended wind season in the northeastern region and a stronger seasonality in the southern region. In contrast, the photovoltaic potential reveals modest change; the positive effects of increasing surface radiation are counterbalanced by the negative effects of warmer air temperatures across the assessed scenarios. These findings offer valuable insights for strengthening Brazil’s energy security under future climate conditions.

American Useful Plants in Post-Medieval Europe: Integrating Archaeobotanical and Historical Evidence - J. Irmišová; M. Ballesteros; J. J. Garay-Vázquez; C. Moricca; J. Skružná; T. Majerovičová; L. Speleers; S. Preiss; M. Badura; J. Wiethold; O. Brinkkemper; J. P. V. Tereso; et al. (Ethnobotany and Economic Botany, 2026)
The arrival of Europeans in the Americas in 1492 initiated new transatlantic connections that, through colonial expansion and trade networks, brought useful plants to Europe. This study investigates archaeobotanical and historical evidence for the introduction of American plants to Europe from the late fifteenth to the twentieth century. We compiled 183 archaeobotanical records from 14 countries, representing 24 taxa from 11 botanical families. We examined which American plant species were introduced to Europe during the post-medieval period, and how their uses and significance varied across regions and social contexts. Archaeobotanical data indicate that early introductions occurred predominantly in elite secular and ecclesiastical settings across Europe. Historical sources identify Spain as the first entry point, though other European countries yielded more records. The large number of archaeobotanical finds in the Netherlands and at the Habsburg court in Prague reflects the current state of research, site coverage, preservation, and data accessibility. The significance of these plants in Europe was shaped by economic value, prestige, ritual use, and medicinal properties. Our study highlights the importance of integrating archaeobotanical and historical sources and provides the most comprehensive account to date of material evidence tracing the cultural trajectories of American plants in Europe.

Phylogenetic diversity recovery along Atlantic Forest succession: The potential for conserving evolutionary history - Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Pedro Manuel Villa; Heitor Mancini Teixeira; Fabio Antônio Ribeiro Matos; Alice Cristina Rodrigues; Nayara Mesquita Mota; Fernando da Costa Britod Lacerda; Fábia Maria dos Santos Souza; Nathália Vieira Hissa Safar; Nathália Silva; Fabiana Bonani; et al. (Biological Conservation, 2026)

Targeting hypertension through natural phenolics: The multifaceted role of cinnamic acid and its derivatives - Samuel S. P. de Araujo; Brenda L. B. dos Santos; Waldilleny R. A. de Moura; Leonardo G. Rodrigues; Luiz G. S. Branco; Helio C. Salgado; Renato N. Soriano; Marina de T. Durand; João Paulo J. Sabino (Pflügers Archiv - European Journal of Physiology, 2026)

Hypothalamic Atrophy and Textural Changes in Polyglutamine Ataxias - Livia Rodrigues; Thiago J. R. Rezende; Alberto R. M. Martinez; Breno Massuyama; Jose Luiz Pedroso; Orlando G. P. Barsottini; Juan Eugenio Iglesias; Simone Appenzeller; Letícia Rittner; Marcondes C. França (The Cerebellum, 2026)
Background. Spinocerebellar ataxia (SCA) presents a complex genetic landscape, with over 40 subtypes. These autosomal dominant disorders manifest late onset and severe disability, primarily impacting the cerebellum but also involving other nervous system structures. While a single study has linked hypothalamic atrophy to SCA3, further research is needed to confirm and/or expand this association. This study aimed to investigate hypothalamic involvement in PolyQ SCAs, focusing on SCA 1, 2, 3, and 6. Methods. We studied 135 adult patients with genetically confirmed SCA (SCA1, SCA2, SCA3, and SCA6) and 117 healthy controls. Hypothalamic subregions were segmented using H-SynEx, and both volumetric and texture features were extracted from MR images. Group differences were assessed with the Mann–Whitney U test, and associations with disease duration and severity (measured by SARA) were examined using Spearman’s rank correlation. Results. Significant atrophy of hypothalamic subregions was observed in SCA1, SCA3, and SCA6 when compared with controls, with the anterior subregion being affected in all cases. Texture analysis revealed widespread alterations in SCA1, SCA3, and SCA6 across all subregions. In SCA1 and SCA3, both volumetric and texture measures correlated with disease duration and SARA scores. These findings suggest that hypothalamic involvement in SCAs is complex and may occur before overt clinical manifestations. Key words: Ataxia, Polyglutamine disease, Hypothalamus, MRI, Volumetry

Diameter, height, and volume as macroscopic predictors of photocarcinogenesis in UV-induced SKH1 papules - Mehdi Boostani; Alaina F. Carman; Erin C. Tracy; Sean P. Murphy; Rhea Carmel Glen Rodrigues; Katalin Ferenczi; Gillian Weston; Olayemi Sokumbi; Gyorgy Paragh; Wendy J. Huss (Journal of Photochemistry and Photobiology B: Biology, 2026)

Modeling of Listeria monocytogenes and Staphylococcus aureus behavior in salted and cured meat products - Matheus P.S. Láscaris; Jaqueline S. Correia; Dionisio P. Amorim-Neto; Beatriz D.P. Machado; Emilie Lang; Leonardo P. Silva; Augusto C.C. Santos; Juliana A.L. Pallone; David S. Costa; Camila A. Akiyama; Adriana P.A. Bragotto; Mayana A.R.V. Tomaz; et al. (International Journal of Food Microbiology, 2026)

Photoelectrocatalytic degradation of carbendazim using titanium‑tungsten oxide in a pilot-scale flow reactor - Joyce F. de Carvalho; Juliana de Almeida; Helena R. Tambelli; Ana Julia S. Rego; Maria Luiza P. da Silva; Débora N. Okamoto; Milene C. Codolo; Christiane de Arruda Rodrigues (Chemical Engineering Journal, 2026)

Rehydrated ground corn silage as alternative to feedlot lambs: feeding behavior and performance - Leandro A. S. da Silva; Cláudia L. S. Lima; Gleidson G. P. de Carvalho; Henry D. R. Alba; Maria L. G. M. L. de Araújo; Cláudia H. da Cruz; Carlindo S. Rodrigues; Dalton H. Pereira; José E. de Freitas Júnior; Manuela S. L. Tosto; Douglas dos S. Pina (Tropical Animal Health and Production, 2026)

Pixel-level detection and classification of marine oil spills in aerial imagery with annotation uncertainty handling - Luiz G.C. Tavares; Wesley L. Passos; Bruno C. Martins; Mauricio de P. Rodrigues; Eduardo A.B. da Silva; Sergio L. Netto (Marine Pollution Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Acute UV response of early erythema and late edema in SKH1 mice - Szabolcs Bozsányi; Rhea Carmel Glen Rodrigues; Ruby Acquah; Erin C. Tracy; Sean P. Murphy; Jocelyn Tracy; Li Yan; Mehdi Boostani; Hamid-Reza Rezvani; Wendy J. Huss; Gyorgy Paragh (Journal of Photochemistry and Photobiology B: Biology, 2026)

Impact of melatonin on inflammatory cytokine profiles in 24-hour cultured equine uterine explants’ - Murilo F. Rodrigues; Adriana P. Neves; Rogério Ferreira; Gilson A. Pessoa; Denise N. Araujo; Guilherme V. de Souza (Journal of Equine Veterinary Science, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Tree cover influences bird assemblage composition in a city within the cerrado biodiversity hotspot - Daniele Pereira Rodrigues; David P. Edwards; Ana Claudia Almeida; Mauricio Almeida-Gomes (Urban Ecosystems, 2026)

Adipose-Derived Stem Cells in Traumatic Brain Injury: A Systematic Review of Preclinical Studies - Marcio Yuri Ferreira; Luis F. Fabrini Paleare; Yasmin P. Silva; Kaike Lobo; Leonardo Januário Campos Cardoso; Christian Ken Fukunaga; Ary Rodrigues Neto; José da Conceição Carvalho; Gustavo L. Franklin; Lydia Masako Ferreira; Netanel Ben-Shalom (Tissue Engineering and Regenerative Medicine, 2026)

An overview of the contaminant mixtures present in key consumed fish and seafood species along the Portuguese territory - Filipe Costa; Manuel J. Rodrigues; Filipe Martinho; Maria E. Pereira; Miguel A. Pardal; João P. Coelho (Marine Pollution Bulletin, 2026)

Scaling up bedload monitoring: a passive acoustic approach for large river systems - J. Le Guern; P. Jugé; F.G. Latosinski; A. Andréault; C.L. Wintenberger; S. Rodrigues (Science of The Total Environment, 2026)

Effects of red light-emitting diode therapy in imiquimod-induced psoriasis in mice - Mab P. Corrêa; Rebeca D. Correia-Silva; Diego D. Santos; Nathália Rodrigues-Silva; Pâmela P. Borges; Silvana Sandri; Karin V. Greco; Cristiane D. Gil (Journal of Photochemistry and Photobiology B: Biology, 2026)

Citral impairs intestinal changes caused by ulcerative colitis through modulation of antioxidant, anti-inflammatory and healing activities - Maycon T. Emílio-Silva; Vinícius P. Rodrigues; Antonio J. Ruiz-Malagon; Isabela G. Guidolin; Felipe L. Dario; Mariana M. Fioravanti; Alba Rodriguez-Nogales; Julio Gálvez; Clelia A. Hiruma-Lima (Inflammopharmacology, 2026)

Short-term high-intensity resistance training: a feasibility study on pulmonary, immune and physical-functional fitness benefits for older adults with metabolic syndrome - Juliana de Melo Batista dos Santos; Guilherme Eustáquio Furtado; Eviton Correa-Sousa; Maysa Alves Rodrigues Brandao-Rangel; Manoel Carneiro Oliveira-Junior; Katielle Rodrigues da Silva Cardoso; Mariana Alvarez de Souza; Francisco Rodrigues; Patricia Coelho; Luís Vicente Franco de Oliveira; André Luís Lacerda Bachi; Luciana Malosa Sampaio Jorge; et al. (European Journal of Applied Physiology, 2026)
The incidence of metabolic syndrome (MetS) is rising rapidly, particularly among older adults, and is associated with comorbidities that impair respiratory and immune functions. Physical exercise has proven effective in mitigating the adverse effects of both aging and MetS. However, evidence on the impact of high-intensity resistance training (HIRT) on the respiratory and immune systems in older adults with MetS remains limited. This study aimed to evaluate the effects of HIRT on respiratory function, skeletal muscle strength, and immune modulation in older adults with MetS, highlighting its potential as a complementary therapeutic approach. A total of 43 older adults with MetS were enrolled and divided into two groups: a HIRT intervention group (n = 23; mean age 66.71 ± 4.98 years) and a non-exercising control group (n = 20; mean age 66.91 ± 5.26 years). The HIRT protocol involved twice-weekly sessions (10 total) over 5 weeks, performed at 80–90% of one-repetition maximum. Results showed that HIRT significantly improved lung mechanics (R5Hz, R20Hz, Z5Hz, X5Hz), peripheral muscle strength, and both maximal expiratory and inspiratory pressures. Furthermore, HIRT increased anti-inflammatory and anti-fibrotic cytokines in sputum (klotho, IL-10, adiponectin) and serum (klotho, relaxin-1, relaxin-3, IL-10), while reducing pro-inflammatory cytokines in sputum (IL-6, TNF-α) and serum (IL-1ra, IL-6, TNF-α, leptin). A decrease in total leukocyte, neutrophil, lymphocyte, and monocyte counts was also observed. In conclusion, HIRT effectively mitigates the effects of MetS on respiratory, muscular, and immune functions in older adults and may be recommended as a complementary strategy for managing MetS in this population.

Hemocyte Apoptosis as a Biomarker of Environmental Stress in Aeglid Species (Decapoda: Anomura) - Renan A. P. dos Santos; Graziela G. Romagnoli; George S. Yasui; Isabela R. R. Moraes; Mariana V. Capparelli; Gabriel F. B. Rodrigues; Larissa R. C. de Oliveira; Antonio L. Castilho (Bulletin of Environmental Contamination and Toxicology, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Taxonomic update for the giant algal chloroviruses of the family Phycodnaviridae - Rodrigo A. L. Rodrigues; João Victor R. P. Carvalho; Lethícia R. Henriques; David D. Dunigan; James L. Van Etten (Archives of Virology, 2026)

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Myrcene suppressed fever by downregulating systemic TNF-α levels in acute LPS-induced systemic inflammation in rats - Maycon T. Emilio-Silva; Vinicius P. Rodrigues; Mariana M. Fioravanti; Luiz G. S. Branco; Clelia A. Hiruma-Lima (Advances in Traditional Medicine, 2025)

Why marine gammarids belong to the future portfolio of aquafeed ingredients - Ricardo Calado; Marta Carvalho; Luísa Marques; Daniela P. Rodrigues; João P. Sousa; Felisa Rey; Maria Rosário Domingues; Joana Filipa Fernandes; Ruben X. G. Silva; Diana Madeira; Arne M. Malzahn; Óscar Monroig; et al. (Frontiers in Marine Science, 2025)
The sustainable supply of n-3 long-chain polyunsaturated fatty acids ( n -3 LC-PUFA) remains a major challenge for global aquaculture. Although plant oils, microalgae, genetically modified crops, insects, krill, and fish by-products have been explored as alternative sources, none currently provides a stand-alone solution for meeting the growing demand of n -3 LC-PUFA in aquafeeds’ production. Here, we present marine gammarids as a potential complementary source of these fatty acids. Our Perspective article focuses on the nutritional attributes of marine gammarids, including their naturally high levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and considers their biological traits that support aquaculture practicality. We also examine the potential of marine gammarids for circular bioeconomy applications through trophic upgrading of low-value side streams. While evidence from feeding trials is limited, preliminary data suggest marine gammarids may maintain their high EPA and DHA content even when fed on low-quality diets. Critical research priorities include developing scalable production systems, optimising feed formulations, evaluating performance across key aquaculture species, and assessing ecological and operational feasibility. This Perspective also highlights the potential of marine gammarids to contribute to a diversified and resilient aquafeed portfolio. Although they are unlikely to replace fish meal or fish oil entirely, marine gammarids may serve as a strategic complementary ingredient.

Individual and combined effects of a simulated heatwave and the emerging Phytophthora ×multiformis on European alder species - I. Gomes Marques; C. Vieites-Blanco; M.J. Barrento; A. Cupertino; J.N. Semedo; A.P. Rodrigues; P. Scotti-Campos; T. Jung; A. Solla; T.S. David; P.M. Rodríguez-González (Forest Ecology and Management, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Cryopreservation of fish ovarian tissue post-mortem: Solution for emergency genetic preservation - Thaiza R. de Freitas; Lis S. Marques; Raquel S. dos Santos; Renata V. Dantas; Thales S. França; Rômulo B. Rodrigues; Karel G. Torres Lozano; Eduardo Albuquerque; Diógenes H. Siqueira-Silva; Tiantian Zhang; Danilo P. Streit (Cryobiology, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Geological and geomechanical properties of soft rocks from the Lower Jurassic Vale Das Fontes Formation (Lusitanian Basin, Portugal): an exploratory study - P. F. Moreira; C. F. Rodrigues; L. V. Duarte; J. P. Temporão de Sousa; A. Vega y de La Fuente; A. Maldonado-Zamora; M. J. Lemos de Sousa; H. I. Chaminé (Mediterranean Geoscience Reviews, 2025)

Evaluation of Chlorella vulgaris application as a biostimulant for lettuce growth in soilless culture - J. Vieira; M. Saque; F. Gama; C. Viana; L. Coelho; M. H. Rodrigues; J. Varela; H. Pereira; P. Palencia; M. Reis; M. Pestana; P. J. Correia (Journal of Applied Phycology, 2025)

Studies in Neotropical Araliaceae. XIII. Four new globose-capitate species of Sciodaphyllum from the Northern and Eastern Andes of Ecuador - Carlos Rodrigues-Vaz; Porter P. Lowry; Gregory M. Plunkett (Brittonia, 2025)

SpiderATLAS : A Database of Spider Traits and Distributions in the Brazilian Atlantic Forest - Gabriel X. Boldorini; Paulo M. Martins; Antonio D. Brescovit; Adalberto J. Santos; Leonardo S. Carvalho; Ubirajara Oliveira; Philip Russo; Joyce C. B. Brito; Aparecida P. Barbosa; André Celso Bezerra Rodrigues; Aníbal Silva Cantalice; Arthur A. B. Rodrigues; et al. (Journal of Biogeography, 2025)
Aim Biodiversity shortfalls related to limited knowledge about geographic distribution (Wallacean) and species traits (Raunkiæran) are extremely common in many animal groups and perhaps more evident in invertebrate groups such as spiders. This lack of knowledge could present challenges for researchers investigating the response and effects of spiders along large spatial scales, particularly in the Global South. The aim of the SpiderATLAS is to facilitate research that links macroecology, biogeography, trait‐based ecology and global change biology. Location Brazilian Atlantic Forest, spanning virtually the entire eastern coastline of Brazil, encompassing 1,620,000 km 2 , 30 degrees of latitude (3° 42′ S to 33° 31′ S), and 22 degrees of longitude (34° 50′ W to 56° 45′ W). Taxon Spiders (Class Araneae), including 1648 species from 63 families. Methods We compiled the spatial distribution (i.e., occurrence data) and data on morphological characteristics and derived traits for spider species from species descriptions, taxonomic revisions and personal collection. Species occurrences were extracted from several data sources spanning from the 1880s to 2023. Data on the morphological traits of species were compiled from taxonomic and diversity inventory papers published between 1833 and 2024. Results We provide 9369 georeferenced point locations and six morphological traits (body length, prosoma length, prosoma width, prosoma height, femur I length, and patella I length) for 1648 spider species. Most data are available for females and males. The dataset and code are available to download from Dryad, World Spider Trait database, and the ZooTraits app. Main Conclusions The SpiderATLAS can be useful to access information on the distribution and traits of spiders, contributing to the development of macroecological, biogeographical and trait‐based ecology. This dataset can also facilitate the biodiversity conservation of one of the most abundant and important arthropod predators on the planet, in a biodiversity hotspot.

Evolution in Response to an Abiotic Stress Shapes Species Coexistence - Inês Fragata; Diogo P. Godinho; Leonor R. Rodrigues; Miguel A. Cruz; Flore Zélé; Oscar Godoy; Sara Magalhães (Ecology Letters, 2025)
Adaptation to abiotic stresses generally relies on traits that are not independent from those affecting species interactions. Still, the impact of such evolutionary processes on coexistence remains elusive. Here, we studied two spider mite species evolving separately on tomato plants that hyper‐accumulated cadmium, a stressful environment for herbivores, or on plants without cadmium. Through experimental evolution and structural stability theory, we found that both species coexist in the cadmium environment, but the evolution of a single species in cadmium leads to exclusion. However, when both species evolve in cadmium they can coexist. This shift occurred due to a simultaneous increase in intra and a decrease in interspecific competition in that environment. These predictions were further confirmed with complementary experiments of population dynamics. Therefore, population shifts to novel environments, even in the absence of interspecific competitors, may have unforeseen evolutionary consequences for community composition and the maintenance of species diversity.

Uncovering neotropical rock geckos’ diversity: multiple data sources on an integrated taxonomic approach reveal a new species of Phyllopezus Peters, 1878 (Squamata: Phyllodactylidae) from northeastern Brazilian Atlantic Forest - Marcos J.M. Dubeux; Gisele M.N. Vieira Dubeux; Jessika M.M. Neves; Fernanda P. Werneck; Miguel T. Rodrigues; Tamí Mott; Pedro M.S. Nunes (Zoologischer Anzeiger, 2025)

Democratizing deep-sea research for biodiversity conservation - Telmo Morato; Luís Rodrigues; Marina Carreiro-Silva; João Balsa; Inês Bruno; Inês Carneiro; Laurence Fauconnet; Guilherme Sampaio-Gonçalves; Marc P. Vilavendrell; Manuela Ramos; Gerald H. Taranto; Carlos Dominguez-Carrió (Trends in Ecology & Evolution, 2025)

Single stage production of ultra-high-grade iron ore using a novel fluidisation arrangement in a Reflux Classifier - Kevin P. Galvin; James Zhou; Armando F.d.V. Rodrigues (Minerals Engineering, 2025)

Patterns of pharmaceutical contamination in streams of European cities across urbanisation gradients: Potential impacts on One Health - Fernanda Rodrigues; Ana R. Calapez; André M.P.T. Pereira; Liliana J.G. Silva; Andreia Freitas; Rayan Bouchali; Andree De Cock; Marie Anne Eurie Forio; Peter Goethals; Silje H. Henni; Adeline Loyau; Anne Moen; et al. (Journal of Hazardous Materials, 2025)

Superionic conductor glass-ceramics for lithium extraction from aqueous solution - João Felipe Pierdoná; Laís P. Caminata; Antonio C. Hernandes; Guilherme Zepon; Ana C.M. Rodrigues; Juliana M.P. Almeida (Desalination, 2025)

Metabolomic profiles and antioxidant intake in female soccer players: a cross-sectional study - M. M. S. Gouveia; M. B. A. Nascimento; A. C. Crispim; E. R. da Rocha; M. P. P. Santos; E. S. Bento; T. M. Aquino; P. Balikian; N. A. Rodrigues; T. Ataide-Silva; G. G. de Araujo; F. A. B. Sousa (European Journal of Applied Physiology, 2025)

The Functional Role of Specific Habitats for the Daily Routine of Juvenile Spoonbills in Protected Coastal Wetlands - Manuela S. Rodrigues; Pedro M. Araújo; Jaime A. Ramos; Pedro C. Rodrigues; Afonso D. Rocha; João P. Silva; José A. Alves (Estuaries and Coasts, 2025)
Wetlands are decreasing globally and species that depend on these habitats must adjust their behaviour or may face population declines. Protected wetlands designed for the conservation of certain species may fail to meet their objectives if habitats critical for specific behaviours are degraded, even if other habitats remain unaffected. It is therefore important to better understand the functional role of specific coastal wetland habitats and when species need them. We investigated the behaviour of juvenile spoonbills ( Platalea leucorodia ) from two Portuguese protected wetlands: the Tagus estuary and Ria Formosa coastal lagoon. Forty-four juvenile spoonbills were equipped with GPS/GSM tags with a 3-axial accelerometer, which allowed integrating spatially explicit behaviour with land use data. We then explored how habitat use changes with diel and tidal cycles within these dynamic landscapes and assessed the functional role of habitats. Juvenile spoonbills vary their daily routines according to the composition of habitats in their natal wetland, with the diel cycle being more influential in the Tagus estuary, while in Ria Formosa both cycles (diel and tidal) were of similar relevance. Habitats were used differently within the study areas: intertidal flats accounted for 62.09% of feeding activity in Ria Formosa versus 47.16% in the Tagus estuary, where rice fields represented the highest feeding percentage (52.27%). This work highlights the need for species- and site-specific studies and can serve as a template for understanding habitat use by other species (or different life stages) to support the development of targeted conservation measures.

Chemical profile of extracts from wild and farmed Chondrosia reniformis sponges - Maria João Nunes; Despoina Varamogianni-Mamatsi; Vanda Marques; Thekla I. Anastasiou; Eirini Kagiampaki; Emmanouela Vernadou; Thanos Dailianis; Nicolas Kalogerakis; Luís C. Branco; Cecília M. P. Rodrigues; Rita G. Sobral; Manolis Mandalakis; et al. (Aquaculture International, 2025)

Ancient Introgression Explains Mitochondrial Genome Capture and Mitonuclear Discordance Among South American Collared Tropidurus Lizards - Matheus M. A. Salles; André L. G. Carvalho; Adam D. Leaché; Nicolas Martinez; Frederick Bauer; Martha Motte; Viviana Espínola; Miguel T. Rodrigues; Carla Piantoni; Marcio R. Pie; André Olivotto; Guarino R. Colli; et al. (Molecular Ecology, 2025)
Mitonuclear discordance—evolutionary discrepancies between mitochondrial and nuclear DNA phylogenies—can arise from various factors, including introgression, incomplete lineage sorting, recent or ancient demographic fluctuations, sex‐biased dispersal asymmetries, among others. Understanding this phenomenon is crucial for accurately reconstructing evolutionary histories, as failing to account for discordance can lead to misinterpretations of species boundaries, phylogenetic relationships, and historical biogeographic patterns. We investigate the evolutionary drivers of mitonuclear discordance in the Tropidurus spinulosus species group, which contains nine species of lizards inhabiting open tropical and subtropical environments in South America. Using a combination of population genetic and phylogenomic approaches applied to mitochondrial and nuclear data, we identified different instances of gene flow that occurred in ancestral lineages of extant species. Our results point to a complex evolutionary history marked by prolonged isolation between species, demographic fluctuations, and potential episodes of secondary contact with genetic admixture. These conditions likely facilitated mitochondrial genome capture while diluting signals of nuclear introgression. Furthermore, we found no strong evidence supporting incomplete lineage sorting or natural selection as primary drivers of the observed mitonuclear discordance. Therefore, the unveiled patterns are most consistent with neutral demographic processes, coupled with ancient mitochondrial introgression, as the main factors underlying the mismatch between nuclear and mitochondrial phylogenies in this system. Future research could further explore the role of other demographic processes, such as asymmetric sex‐biased dispersal, in shaping these complex evolutionary patterns.

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Evaluating the efficacy of topical application of Genista tridentata (L.) (Fabaceae) leaf extract on wound healing in experimental diabetes - Inês Martins Laranjeira; Beatriz Gonçalves; Diana Rodrigues-Fonseca; Alberto C. P. Dias; Filipa Pinto-Ribeiro (Phytochemistry Letters, 2025)

Hybrid machine learning model for disinfectant dosing in small-scale water treatment under data scarcity - Diego Takashi Sato; Orlando M. Oliveira Belo; Antonio P. Castro; Viviane M. Gomes Pacheco; Cloves Gonçalves Rodrigues; Antonio Paulo Coimbra; Wesley Pacheco Calixto (Journal of Water Process Engineering, 2025)

Treatment of wine distillery effluent by the fenton's process - João P. Lemos; Anabela Nogueira; Sérgio Castro-Silva; Carmen S.D. Rodrigues; Luis M. Madeira (Journal of Water Process Engineering, 2025)

Fault-related carbonates as evidence of continentalization during the Permian-Triassic of the Paraná Basin, Southern Brazil - P. Zacca; I.C. Rodrigues; A.M. Mizusaki; G. Cioccari; C. Urban (Journal of South American Earth Sciences, 2025)

Post-crystallization fluid behavior in acidic volcanic context: genesis and isotopic signature of fracture-filling calcite in the Paraná Basin, Brazil - P. Zacca; G.M. Cioccari; I.C. Rodrigues; A.M. Mizusaki (Journal of South American Earth Sciences, 2025)

The overlooked variables: Slide thickness and 3D tumour heterogeneity on mitotic counts of canine mast cell tumours - P. Faísca; L. Silva; I. Carvalho; J. Santos; J. Catarino; D. Ramilo; P. Rodrigues; A. Gama (Journal of Comparative Pathology, 2025)

On the power of CNNs to detect slums in Brazil - João P. da Silva; José F. Rodrigues-Jr; João P. de Albuquerque (Computers, Environment and Urban Systems, 2025)

Graft copolymerization of bio-based β-farnesene and n-butyl acrylate onto modified anionic cassava starch via emulsifier-free emulsion polymerization for sustainable adhesives - Lina D.A. Rodrigues; Lilia M. Guerrini; Maurício P. Oliveira (Carbohydrate Polymers, 2025)

Exploring In Vitro Mesenchymal Stem Cell Osteodifferentiation via Vibrational Microspectroscopy: A Review - Daniela S. Bispo; Inês C. R. Graça; João A. Rodrigues; João T. S. Martins; Mariela M. Nolasco; Maria P. M. Marques; Helena I. S. Nogueira; João F. Mano; Mariana B. Oliveira; Paulo J. A. Ribeiro-Claro; Ana M. Gil (Stem Cell Reviews and Reports, 2025)
The application of vibrational microspectroscopy to the study of in vitro mesenchymal stem cells (MSC) osteogenic differentiation is a promising approach towards the understanding of the molecular processes involved in bone fabrication. Both infrared (IR) and Raman microspectroscopies have been applied, with a clear predominance of the latter. Bone marrow MSC have been the target of most studies, followed by those originating from dental/oral and adipose tissues. Interests have increasingly addressed single cell and extracellular matrix characterization at the molecular level. Most studies have focused on the characteristics and maturity of time-course mineralization, attempting to localize mineral aggregates formed onto the evolving collagen strands. Some reports have focused on time-dependent changes in protein structure and other components of extracellular matrix components. Besides spectral band examination through position, linewidth and shape, selected band ratios have proved largely informative to assess mineral species evolution and mineral-to-organic matrix interactions over time. The increasing use of multivariate analysis (or chemometrics) and machine learning strategies to detect finer spectral variations is evident, as is the promise of more recent IR and Raman variations to provide higher sensitivity and spatial resolution conditions. The label-free non-invasive nature of vibrational microspectroscopy makes it particularly promising for rapid and effective selection of suitable MSC donors, to support scale-up procedures for translation to the clinic. Some of the challenges to be faced are briefly discussed. Graphical Abstract

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Climate change scenarios differentially modulate the impact of invasion in a native macrophyte species - Tauany Rodrigues; Joseph L. S. Ferro; Reinaldo L. Bozelli; Aliny P. F. Pires; Vinicius F. Farjalla (Limnology and Oceanography, 2025)
Biological invasion and climate change threaten freshwater ecosystems, potentially amplifying their impacts through interaction. However, empirical evidence on how future climate scenarios influence the invasion process and their interactive effects on native species remains limited. We conducted a full‐factorial experiment to evaluate the independent and interactive effects of Hydrilla verticillata invasion and future climate scenarios (baseline, mitigation, and business‐as‐usual) on the native macrophyte Cabomba caroliniana . We also assessed the response of the non‐native H. verticillata to these climate scenarios. The climate change mitigation scenario maintained the invasive potential of H. verticillata , as indicated by its vertical growth and colonization potential via vegetative propagules, which were comparable to baseline conditions. Simultaneously, the mitigation scenario supported the vertical growth and production of C. caroliniana at levels similar to those under the baseline. Under the business‐as‐usual scenario, H. verticillata exhibited enhanced vertical growth and colonization capacity via vegetative propagules. Interestingly, its presence under the business‐as‐usual scenario was associated with increased vertical production of the native species. Although invasion appeared to buffer the adverse effects of extreme climatic stress, it merely enabled C. caroliniana to recover vertical production to baseline and mitigation levels, rather than providing a long‐term advantage. Our findings highlight the ecological benefits of climate change mitigation and the complex outcomes arising from the interaction between invasion and future climate scenarios for native species.

Preservation and detection of carotenoid pigments of Deinococcus radiodurans on mineral substrates under UV irradiation - Tamires Gallo; Fabio Rodrigues; Evelyn A.M. Sanchez; Fabio S. de Vicente; Veronica C. Teixeira; Evandro P. Silva; Marcia Rizzuto; Gabriel S. Teofilo-Guedes; Douglas Galante (Icarus, 2025)

Co-fermentation of sugar-alcohol industry waste to produce hydrogen and value-added metabolites - Bruna S. Dionizio; Camila A.B.S. Rabelo; Caroline V. Rodrigues; Franciele P. Camargo; Edson L. Silva; Dulce H.F. de Souza; Maria Bernadete A. Varesche (Bioresource Technology Reports, 2025)

Application of graphene oxide incorporated into biopolymer microfibers as a novel adsorbent for removing pharmaceuticals from water - L. Pellenz; A. H. da Silva Júnior; C. R. S. de Oliveira; L. P. Mazur; L. H. I. Mei; N. M. Medeiros Rodrigues; A. A. U. de Souza; A. da Silva (International Journal of Environmental Science and Technology, 2025)

A multispecies microcosm to assess the effect of footwear wastes on soil biota: a contribution towards sustainability - Beatriz Fernandes; Verónica Nogueira; Sirine Bouguerra; Cristiano Soares; Fernanda Fidalgo; Joana Machado; Susana M. P. Carvalho; Maria José Ferreira; Vera Pinto; José Rodrigues; Carlos M. Pereira; Ruth Pereira (Environmental Science and Pollution Research, 2025)
Due to the high quantities of solid waste with high concentrations of chromium that the footwear industry produces and its disposal sites, it is vital to understand whether leather residue itself is harmful to the ecosystem. Thus, a microcosm test with multispecies ( Brassica oleracea and Eisenia fetida ) was carried out using an agricultural soil contaminated with two different leather residues (Wet Blue and Finished Leather) from the footwear industry. After the stabilization period, Brassica oleracea seedlings and Eisenia fetida adults were exposed to these treatments. At the end of the experiment, a series of parameters were analysed in the B. oleracea leaves (leaf chlorophyl content, gas exchange measurements and photosynthetic parameters), in the E. fetida organisms (alkaline comet assay and biomarkers such as acetylcholinesterase and lipid peroxidation) and in the soils (total chromium content, enzymes activity and nitrogen mineralization and potential nitrification). In the case of soil’s enzymatic activity, even though some were significantly altered, no negative effects could be attributed to the leather residues. Moreover, the addition of residues to the soil did not significantly affect the plant species; however, the same was not observed for the earthworm E. fetida when in contact with Finished Leather. Overall, Finished Leather residue was the one that caused more effects on the parameters analysed and therefore its disposal should be carefully examined.

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

Electrical stimulation of table grape berries as new alternative for postharvest Escherichia coli contamination management - Mariana P. Fernandes; Flávio Rodrigues; Vanessa F. Cardoso; Filipe S. Silva; Margarida M. Fernandes (Postharvest Biology and Technology, 2025)

Fermented brewer's spent grain as a sustainable feed ingredient impacts meagre (Argyrosomus regius) growth, intermediary metabolism, digestive enzymes, oxidative stress, and intestinal histology - T. Estevão-Rodrigues; H. Fernandes; S. Moutinho; A. Couto; I. Belo; C. Castro.; P. Pousão; J.M. Salgado; A. Oliva-Teles; H. Peres (Animal Feed Science and Technology, 2025)

Fatty acid profile of Gammarus locusta newly hatched offspring from the wild and from adults farmed on mono-specific macroalgal diets - João P. Sousa; Luísa Marques; Daniela P. Rodrigues; Felisa Rey; Manuel Albuquerque; Maria Rosário M. Domingues; Rafael C. Duarte; Ricardo Calado (Frontiers in Marine Science, 2025)
The accelerated growth of marine aquaculture targeting species that require formulated aquafeeds creates a pressing need to find new sustainable ingredients and additives that can secure a premium farming performance, as well as the nutritional value of farmed species. Marine gammarid amphipods can be an excellent source of essential fatty acids (FA), namely, long-chain n -3 polyunsaturated FA (LC-PUFA). However, their potential contribution to aquaculture feeds remains largely unexplored. The present work evaluated the effect of five mono-specific macroalgal diets ( Ulva sp., Fucus sp., Laminaria sp., Gracilaria sp., and Chondrus sp.) on the FA composition of the offspring of Gammarus locusta fed on these macroalgae and compared it with the offspring of wild conspecifics. Results revealed that offspring from wild G. locusta showed the highest amount of PUFA (4.95 ± 0.31 μg mg -1 DW), as well as essential FA, namely eicosapentaenoic acid (EPA, 20:5 n -3) (2.49 ± 0.21 μg mg -1 DW) and docosahexaenoic acid (DHA, 22:6 n -3) (0.87 ± 0.16 μg mg -1 DW). The treatment with the highest amount of PUFA and EPA was the one using Fucus sp. as a mono-specific macroalgal diet (4.46 ± 0.31 μg mg -1 DW and 2.42 ± 0.24 μg mg -1 DW, respectively). The best levels of DHA in offspring were recorded for specimens feeding on Chondrus sp. (0.56 ± 0.10 μg mg -1 DW). Significant differences in the abundance of stearic acid (18:0) and DHA were observed between the offspring of adults fed algal-based diets and those from the wild. These findings suggest that G. locusta selectively conserves and directly or indirectly biosynthesises essential FA for growth and reproduction, particularly LC-PUFA. Overall, G. locusta can perform a trophic upgrade of its diet, making this gammarid amphipod a promising additive for the formulation of high-quality aquafeeds supplying LC-PUFA.

Pre-adapted to glacial periods: the reproductive cycle of the rissoid Cingula trifasciata (J. Adams, 1800) (Mollusca, Gastropoda) at São Miguel island (Azores Archipelago) - Sérgio P. Ávila; Paulo J. Melo; Patrícia Madeira; Ana Hipólito; Armindo Rodrigues (Invertebrate Reproduction & Development, 2025)

Rhabdomyosarcomas in dystrophin-deficient Sprague Dawley rats - M. Rodrigues; E. Reyes-Gomez; L. Tiret; P. Lafuste; F. Relaix (Journal of Comparative Pathology, 2025)

Survival analysis of female dogs and cats with rare and uncommon malignant mammary tumours - preliminary results - J.N. Pontes; C. Pereira; J. Rodrigues-Jesus; A. Santos; A. Catarina Figueira; S. Guedes; F. Seixas; M. dos Anjos Pires; A. Alves; F. Ferreira; J. Correia; P. Faísca; et al. (Journal of Comparative Pathology, 2025)

Combining stereology and image analysis for accurate and fast quantification in experimental pathology - P. Faísca; M. Razões; D.Ramilo; A. Pereira; P. Rodrigues (Journal of Comparative Pathology, 2025)

Comparisons of Hyperostotic Bones in Two Species of the Genus Oligoplites Gill, 1863 in the Southern Brazilian Coast - Fernando A. P. Tuna; Ana Paula C. de Rodrigues; Gustavo P Filgueira; Rebeca s da Bianca; Wilson T. V. Machado; Márcia C. Salomão; Helena P. Lavrado (Journal of Fish Diseases, 2025)
The description of skeletal disorders is commonly reported in fish species raised through aquaculture; however, wild marine fish may also exhibit high frequencies of anomalies, particularly the development of hyperostosis, a condition that causes thickening of the bones. Specimens of Oligoplites saliens ( n = 15) and Oligoplites palometa ( n = 14) were radiographed to verify hyperostotic bone occurrences. Hyperostosis was detected in all individuals (> 400 mm TL) analysed for both species, occurring in six distinct regions of the skeleton (supraoccipital bone, cleithrum, dorsal pterygiophores, anal pterygiophore, haemal spines, and neural spines), regardless of the sex of the individuals. No hyperostosis was found in the neural and haemal spines of O. palometa and in the anal pterygiophore of O. saliens . Histological sections of the supraoccipital bone of O. saliens were conducted, revealing high porosity characterised by the presence of vascular channels in bones with hyperostosis. The species exhibited species‐specific patterns for the condition, demonstrating differences even among species of the same genus occurring in the same geographic area. This is the first record of hyperostosis for both species in Brazilian waters.

Unveiling the Genomic Landscape of Understudied Salmonella enterica Serovars from Poultry and Human: Implications for Food Safety - Valdinete P. Benevides; Mauro M. S. Saraiva; Viviane A. Ferreira; Michelli Inácio G. Funnicelli; Lucas B. Rodrigues Alves; Adriana M. Almeida; Henrik Christensen; John E. Olsen; Angelo Berchieri Junior (Current Microbiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Estimation of diurnal and nocturnal radiation balance in tropical ecosystems - D. O. Maionchi; I. J. C. de Paulo; S. R. de Paulo; J. B. Marques; A. L. P. Junior; H. J. A. da Silva; R. S. Palácios; T. R. Rodrigues; T. A. dos Santos; A. M. S. Lima; M. S. Biudes; L. Sanches; et al. (Theoretical and Applied Climatology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Effects of starvation and honey diet in oosorption in Cryptolaemus montrouzieri Mulsant, 1850 (Coleoptera: Coccinellidae) - Jefferson Rodrigues-Pedrosa; Carlos M. P. Marques; Wendel J. Teles Pontes (Invertebrate Reproduction & Development, 2025)

A Cryptococcus neoformans polysaccharide conjugate vaccine made with filtered polysaccharide elicits protective immunity in mice - Piotr R. Stempinski; Paola Ramos Irizarry; Scott A. McConnell; Livia C. Liporagi Lopes; Samuel Rodrigues Dos Santos Júnior; Maggie P. Wear; Arturo Casadevall (Fungal Biology, 2025)

Neuroinflammation in Severe COVID-19: The Dynamics of Inflammatory and Brain Injury Markers During Hospitalization - Carla Andretta Moreira Neves; Gilson P. Dorneles; Paula C. Teixeira; Paulo C. Santana Filho; Alessandra Peres; Carina Rodrigues Boeck; Liane N. Rotta; Claudia E. Thompson; Pedro R. T. Romão (Molecular Neurobiology, 2025)

Detection of an Alphacoronavirus in a Brazilian Bat (Molossus sp.) - C. L. Molina; M. M. Magalhães; A. C. Rodrigues; S. A. Taniwaki; S. O. de Souza Silva; G. A. König; P. E. Brandão (Journal of Molecular Evolution, 2025)

Dragonflies (Odonata) as bioindicators of the sustainability of agroforestry systems in the Atlantic Forest - Cíntia Ribeiro; Fernando Geraldo de Carvalho; Fábio de Oliveira Roque; John P. Simaika; Ulisses Gaspar Neiss; Laís Rodrigues Santos; Francisco Maciel Barbosa-Santos; Karolina Teixeira Silva; Marciel Elio Rodrigues (Aquatic Sciences, 2025)

Key patterns in exceptional fossil preservation since the rise of metazoans - Filipe G. Varejão; Rodrigo I. Cerri; Lucas V. Warren; Mariza G. Rodrigues; Stephen J. Puetz; Paloma P. de Lorenso; Marcello G. Simões (Earth-Science Reviews, 2025)

Contextualizing the Upper Paleolithic of the Armenian Highlands: New data from Solak-1, central Armenia - Tanner Z. Kovach; Artur Petrosyan; Keith N. Wilkinson; Yannick Raczynski-Henk; Kathleen Rodrigues; Ellery Frahm; Emily Beverly; Jayson P. Gill; Jennifer E. Sherriff; Boris Gasparyan; Hayk G. Avetisyan; Artak V. Gnuni; et al. (Journal of Human Evolution, 2025)

Unraveling the effect of glycerol and amides and different cooling rates on post-thawed sperm parameters of equine frozen semen - M.S. Frasson; S.N. Oliveira; J.A. Dell'Aqua; L.T. Rodrigues; T.M.S. Cavaleiro; C.P. Freitas-Dell'Aqua; A.M. Crespilho; P. de Mello Papa; L. Segabinazzi; F.O. Papa (Journal of Equine Veterinary Science, 2025)

Impact of urban disturbance on soil insect communities in a Brazilian Atlantic Forest biological station - Felipe Ferraz Figueiredo Moreira; Juliana Mourão dos Santos Rodrigues; Marcos Krull; Raquel G. Boullosa; Rosana Gentile; Karina Cunha Sant’ana; Marianna V. P. Simões (Urban Ecosystems, 2025)
Urbanization constitutes a major threat to biodiversity. Understanding its effects on insect communities is relevant because they are key elements of trophic interactions, and indicators and targets of conservation. Herein, we investigated the influence of meteorological and habitat factors on the soil entomofauna in three areas with distinct levels of urbanization at the Parque Estadual da Pedra Branca, Brazil. We investigated whether community structure differs among areas with different levels of urbanization, and how changes in the environment affect soil insect community composition and distribution. We systematically monitored communities for 12 months in three areas along a gradient of anthropogenic disturbance, representing preserved secondary forest, disturbed forest and peridomicile areas. The results revealed that the degree of urbanization affects insect communities, with a strong effect of habitat factors, such as canopy cover, presence of flooded areas, quantity of fallen trunks and mean temperature. Insect abundance did not show significant differences among areas, while biomass was higher in disturbed forest than in preserved forest and peridomicile areas. Additionally, insect richness and diversity were higher in preserved and disturbed forests than in peridomicile areas, with no significant difference between preserved and disturbed forests. Our results can be used to enhance the understanding of the effects of urbanization on taxonomically and functionally diverse groups of insects, and to advise residents and urban planners about the consequences of urbanization on biodiversity and ecosystem services in urban-sylvatic interface areas.

Comparative effects of Serendipita indica and a mix of arbuscular mycorrhizal fungi on the growth, photosynthetic capacity, and proteomics of Schinus terebinthifolius Raddi - Amanda A. Bertolazi; Lucas Z. Passamani; Sávio B. de Souza; Weverton P. Rodrigues; Eliemar Campostrini; Vitor B. Pinto; Vanildo Silveira; Carlos E. de Rezende; Cristina Cruz; Elke J. B. N. Cardoso; Alessandro Coutinho Ramos (Planta, 2025)

An automated technique and decision support system for lightning early warning - M. A. Alves; B. A. S. Oliveira; D. B. S. Ferreira; A. P. P. Santos; W. F. S. Maia; W. S. Soares; F. P. Silvestrow; L. F. M. Rodrigues; E. L. Daher; O. Pinto (International Journal of Environmental Science and Technology, 2025)

Impact of Drilling Fluids on Borehole Hydraulic Conductivity in Geotechnical Investigations - F. Schnaid; B. A. Rodrigues; D. E. Lourenço; G. M. A. do Patrocínio; S. Maghous; J. L. dos Santos; M. L. P. Alves; R. Fonseca; V. B. de Araújo (Geotechnical and Geological Engineering, 2025)

Ceftazidime-avibactam tolerance and persistence among difficult-to-treat KPC-producing Klebsiella pneumoniae clinical isolates from bloodstream infections - N. Abichabki; G. G. Gaspar; L. R. Bortolato; D. A. F. S. Lima; L. N. Silva; R. H. C. Pocente; J. C. Ferreira; T. C. Ogasawara; D. Pereira; R. R. Guerra; C. Wilhelm; P. Barth; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Elevational Range Impacts Connectivity and Predicted Deme Sizes From Models of Habitat Suitability - Connor M. French; Roberta P. Damasceno; Mariana M. Vasconcellos; Miguel T. Rodrigues; Ana C. Carnaval; Michael J. Hickerson (Molecular Ecology, 2025)
In integrative distributional, demographic and coalescent (iDDC) modelling, a critical component is the statistical relationship between habitat suitability and local population sizes. This study explores this relationship in two Enyalius lizard species from the Brazilian Atlantic Forest: the high‐elevation E. iheringii and low‐elevation E. catenatus and how this transformation affects spatiotemporal demographic inference. Most previous iDDC studies assumed a linear relationship, but this study hypothesises that the relationship may be nonlinear, especially for high‐elevation species with broader environmental tolerances. We test two key hypotheses: (1) The habitat suitability to population size relationship is nonlinear for E. iheringii (high‐elevation) and linear for E. catenatus (low‐elevation); and (2) E. iheringii exhibits higher effective migration across populations than E. catenatus . Our findings provide clear support for hypothesis (2), but mixed support for hypothesis (1), with strong model support for a nonlinear transformation in the high‐elevation E. iheringii and some (albeit weak) support for a nonlinear transformation also in E. catenatus . The iDDC models allow us to generate landscape‐wide maps of predicted genetic diversity for both species, revealing that genetic diversity predictions for the high‐elevation E. iheringii align with estimated patterns of historical range stability, whereas predictions for low‐elevation E. catenatus are distinct from range‐wide stability predictions. This research highlights the importance of accurately modelling the habitat suitability to population size relationship in iDDC studies, contributing to our understanding of species' demographic responses to environmental changes.

Genetic Variation in the Atlantic Bobtail Squid‐ Vibrio Symbiosis From the Galician Rías - P. A. Pérez‐Ferrer; M. Ashraf; M. Rodrigues; J. Troncoso; M. K. Nishiguchi (Molecular Ecology, 2025)
Symbiotic marine bacteria that are transmitted through the environment are susceptible to abiotic factors (salinity, temperature, physical barriers) that can influence their ability to colonize their specific hosts. Given that many symbioses are driven by host specificity, environmentally transmitted symbionts are more susceptible to extrinsic factors depending on conditions over space and time. In order to determine whether the population structure of environmentally transmitted symbionts reflects host specificity or biogeography, we analysed the genetic structure of Sepiola atlantica (Cephalopoda: Sepiolidae) and their Vibrio symbionts ( V. fischeri and V. logei ) in four Galician Rías (Spain). This geographical location is characterized by a jagged coastline with a deep‐sea entrance into the land, ideal for testing whether such population barriers exist due to genetic isolation. We used haplotype estimates combined with nested clade analysis to determine the genetic relatedness for both S. atlantica and Vibrio bacteria. Analyses of molecular variance (AMOVA) were used to estimate variation within and between populations for both host and symbiont genetic data. Our analyses reveal a low percentage of variation among and between host populations, suggesting that these populations are panmictic. In contrast, Vibrio symbiont populations show certain degree of genetic structure, demonstrating that the hydrology of the rías is driving bacterial distribution (and not host specificity). Thus, for environmentally transmitted symbioses such as the sepiolid squid‐ Vibrio association, abiotic factors can be a major selective force for determining population structure for one of the partners.

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Impact of climatic seasons on the dynamics of carbon, nitrogen and mercury in soils of Brazilian biomes affected by gold mining - Matheus B. Soares; Rebeca R. Rodrigues; Laura O. Péres; Carlos Eduardo P. Cerri; Luís Reynaldo F. Alleoni (Science of The Total Environment, 2024)

Taxonomy, systematics and conservation of the highly threatened and endemic Mexican genus Tridimeris (Annonaceae) - Andrés Ernesto Ortiz-Rodriguez; Francis J. Nge; Carlos Rodrigues-Vaz; Vincent Soulé; George E. Schatz; María Fernanda Martínez-Velarde; Leopoldo Hurtado-Reveles; Moises Rangel-Olguin; Thomas L. P. Couvreur (Plant Systematics and Evolution, 2024)
Tridimeris is the only genus of Annonaceae endemic to Mexico, and since its description more than 150 years ago, the genus has been largely ignored. Here, based on herbarium specimens and a comprehensive phylogenomic study involving hundreds of nuclear markers, the first taxonomic revision of the genus Tridimeris (Annonaceae, Malmeioideae, subtribe Sapranthinae) is presented. Ten species are recognized, six of which are newly described here. All the species are exclusively found in Mexico's most humid forests, particularly in the montane cloud forest and the tropical rainforest. The genus Tridimeris is morphologically distinguished from other neotropical genera of the Annonaceae by its leaves with pocket domatia present in the axils of the secondary veins, by its dimerous flowers (two sepals and four petals), basally fused sepals with ciliated margins, by a reduced number of carpels per flower (1–5) and by its large and fleshy fruits (monocarps) with numerous seeds. A highly resolved phylogenetic hypothesis provides strong support for the relationships among Tridimeris species, forming two well-supported clades. Consequently, two new sections are proposed, namely Tridimeris sect. Tridimeris and Tridimeris sect. Zoque . A detailed description of the morphology of the genus is presented, including the description of the pollen, domatia and its phylogenetic relationships. Taxonomic treatments of the species include synonyms, geographic and ecological notes, comparisons with similar species and a preliminary assessment of their conservation status. All species of the genus are potentially threatened with extinction and eight are assessed as Critically Endangered, which makes it the most threatened lineage of Mexican trees. This study emphasizes the importance of scientific collections as invaluable sources of data for current taxonomic revisions and conservation. It is a formal invitation to preserve and support the basic scientific research.

Aerobic physical training reduces severe asthma phenotype involving kinins pathway - Maysa Alves Rodrigues Brandao-Rangel; Renilson Moraes-Ferreira; Anamei Silva-Reis; Victor Hugo Souza-Palmeira; Francine Maria Almeida; Fabiana Regina da Silva Olimpio; Carlos Rocha Oliveira; Nilsa Regina Damaceno-Rodrigues; João Bosco Pesquero; Leonardo Martin; Flavio Aimbire; Regiane Albertini; et al. (Molecular Biology Reports, 2024)

Disentangling the basidiomycete family Agaricaceae - Pepijn W. Kooij; Meilinda P. Sulastri; Andre Rodrigues; Ester Gaya (Mycological Progress, 2024)

Dietary supplementation of mineral nanoparticles for channel catfish (Ictalurus punctatus) - Vitor F. Silva; José Luiz P. Mouriño; Maurício L. Martins; Pedro L. P. F. Carvalho; Edgar D. Rodrigues; Delbert M. Gatlin; Matt J. Griffin; Caitlin E. Older; Fernando Y. Yamamoto (Fish Physiology and Biochemistry, 2024)

Resource-efficiency of cyanobacterium production on Mars: Assessment and paths forward - Tiago P. Ramalho; Vincent Baumgartner; Nils Kunst; David Rodrigues; Emma Bohuon; Basile Leroy; Guillaume Pillot; Christiane Heinicke; Sven Kerzenmacher; Marc Avila; Cyprien Verseux (Algal Research, 2024)

Depth estimation of pre-Kalahari basement in Southern Angola using seismic noise measurements and drill-hole data - J. Carvalho; D. Alves; J. Borges; B. Caldeira; D. Cordeiro; A. Machadinho; A. Oliveira; E.C. Ramalho; J.F. Rodrigues; J.M. Llorente; M. Ditutala; J.L. García-Lobón; et al. (Journal of Applied Geophysics, 2024)

Comprehensive dynamics of bacterial and fungal diversity throughout concentrated chicken broth processing: Integrating culture-dependent and independent techniques - José T.D. Rodrigues; Larissa P. Margalho; Arthur K.R. Pia; Héctor Sierra; Louise Tavares; Míriam G. Marquezini; Melline Fontes Noronha; Lucélia Cabral; Wilson José Fernandes Lemos Junior; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2024)

Juvenile-related tolerance to papaya sticky disease (PSD): proteomic, ultrastructural, and physiological events - Silas P. Rodrigues; Eduardo de A. Soares; Tathiana F. Sá Antunes; Marlonni Maurastoni; Leidy J. Madroñero; Sabrina G. Broetto; Lucas E. C. Nunes; Brunno R. F. Verçoza; David S. Buss; Diolina M. Silva; Juliany C. F. Rodrigues; José A. Ventura; et al. (Plant Cell Reports, 2024)

Evaluation of antioxidant, anti-inflammatory and cytotoxic potential of phytochemicals from Gymnostachyum febrifugum -an in vitro study - K. J. Spandana; K. P. Fathimathul Lubaba; A. Sujina; Wilson Joel Rodrigues; K. R. Chandrashekar; N. Bhagya (Plant Biosystems, 2024)

Multi‐Taxa Responses to Climate Change in the Amazon Forest - Carlos A. S. Rodrigues‐Filho; Flávia R. C. Costa; Juliana Schietti; Anselmo Nogueira; Rafael Pereira Leitão; Juliana Menger; Gabriel Borba; Caian Souza Gerolamo; Stefano S. Avilla; Thaise Emilio; Carolina Volkmer de Castilho; Douglas Aviz Bastos; et al. (Global Change Biology, 2024)
Tropical biodiversity is undergoing unprecedented changes due to the hydrological cycle intensification, characterized by more intense droughts and wet seasons. This raises concerns about the resilience of animal and plant communities to such extremes and the existence of potential refugia—areas theorized to safeguard biological communities from adverse climate impacts. Over 20 years of monitoring in Central Amazonia, we investigated the short‐term and long‐term effects of hydrological cycle intensification on bird, fish, ant, and palm communities. We explored whether the ‘insurance effect’ of climate trends (droughts buffered by preceded wet seasons) or ‘environmental refugia’ (droughts or floods buffered by topographic features) could lessen the impact of climate events on community composition, richness, evenness, and species rank. Pronounced abundance changes were observed among animal species, whereas palm species showed relative temporal stability. Birds and fish were more affected by the immediate and long‐term severity of droughts and wet periods, while ants responded primarily to short‐term drought impacts. Conversely, palm communities exhibited delayed responses to climate extremes, primarily in long‐term comparisons. As expected, the proposed ‘insurance effect’ mitigates the long‐term impacts of extreme climate events on animal and plant community trends. However, less extreme hydrological conditions linked to topographic features did not provide effective ‘environmental refugia’ for animals or plants during adverse climate conditions. These outcomes underscore the complex and varied biological responses to ongoing climate change, challenging the prevailing assumptions about the efficacy of environmental refugia and highlighting the nuanced resilience of biodiversity in Central Amazonia.

Holistic evaluation of the environmental impacts of shipping in the sensitive region of Ria de Aveiro - A. Monteiro; V. Rodrigues; A. Picado; J.M. Dias; N. Abrantes; A. Ré; M. Rosa; M. Russo; A. Barreirinha; M. Potiris; M. Aghito; R. Hänninen; et al. (Science of The Total Environment, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Gut colonization by extended-spectrum β-lactamase-producing Escherichia coli in dairy herd in Brazil: successful dissemination of a One Health clone - Luciana Sartori; Fábio P. Sellera; Taiana T. Silva-Pereira; Bruna Fuga; Danny Fuentes-Castillo; Milena Dropa; Quézia Moura; Miriam R. Fernandes; Larissa Rodrigues; Fernanda Esposito; Elder Sano; Mario A. R. Aleman; et al. (Veterinary Research Communications, 2024)

Analysis of environmental variables and deforestation in the amazon using logistical regression models - Helder J. F. da Silva; Weber A. Gonçalves; Bergson G. Bezerra; Cláudio M. Santos e Silva; Cristiano P. de Oliveira; Jório B. Cabral Júnior; Daniele T. Rodrigues; Fabrício D. S. Silva (Environmental Monitoring and Assessment, 2024)

Sonification of electronic dynamical systems: Spectral characteristics and sound evaluation using EEG features - G. Acosta Martínez; E. Guevara; E. S. Kolosovas-Machuca; P. G. Rodrigues; D. C. Soriano; E. Tristán Hernández; L. J. Ontañón-García (Cognitive Neurodynamics, 2024)

The Goldilocks Dilemma: the optimal management strategy for invasive trees in the Atlantic Forest - Rodolfo Cesar Real Abreu; Pablo J. F. P. Rodrigues (Biological Invasions, 2024)

Climatic niche evolution and speciation modes in the transisthmian Alpheus shrimps (Caridea: Alpheidae) - Douglas Fernandes Rodrigues Alves; Pablo Ariel Martinez; Samara de P. de Barros‐Alves; Ariádine Cristine de Almeida; Marco Aurélio Mendes Elias; Carla Hurt; Kristin M. Hultgren (Journal of Biogeography, 2024)
Aim We studied the niche evolution and diversification modes in transisthmian Alpheus shrimps by examining the interplay between environmental niche divergence and conservatism in allopatric sister species. In a broader perspective, the current study analysed the evolution of climatic niche and the role of the environment in species diversification of Alpheus transisthmian shrimp. Location Atlantic and Eastern‐Pacific oceans. Taxon Alpheus shrimps (Caridea: Alpheidae). Methods We assembled georeferenced occurrences for 33 species of Alpheus (with 24 sister species) from a time‐calibrated molecular phylogeny. We modelled their ecological niches and assessed niche overlap through pairwise comparisons. Additionally, we performed phylogenetic reconstructions of the ancestral environmental niche, for each niche axis. Results Our results demonstrate that thermal tolerances, food availability and hydrodynamic forces were relevant environmental axes in evolutionary processes in transisthmian species of Alpheus . Among the 528 paired comparisons, we found that most niches were divergent, including in 12 clades formed by pairs of sister species (in only two of these clades were the niches fully equivalent). Phylogenetic reconstructions of ancestral niches showed an initial niche conservatism in all axes, with divergences intensifying in the last 12 million years. Main Conclusions We found evidence that confirms the relevance of the environmental changes that occurred in the West Atlantic and East Pacific for niche evolution in transisthmian Alpheus species, as well as for the emergence of some lineages. Our findings provide evidence for different modes of Alpheus species speciation in a period consistent with the closure of the Isthmus of Panama.

Interaction Between Climate Change Scenarios and Biological Invasion Reveals Complex Cascading Effects in Freshwater Ecosystems - Tauany Rodrigues; Pavel Kratina; Rayanne B. Setubal; Joseph L. S. Ferro; Douglas Hideki Abe; Luiza O. Costa; Clarice Casa Nova; Vinicius F. Farjalla; Aliny P. F. Pires (Global Change Biology, 2024)
Climate change often facilitates biological invasions, leading to potential interactive impacts of these global drivers on freshwater ecosystems. Although climatic mitigation efforts may reduce the magnitude of these interactive impacts, we are still missing experimental evidence for such effects under multiple climate change scenarios within a multi‐trophic framework. To address this knowledge gap, we experimentally compared the independent and interactive effects of two climate change scenarios (mitigation and business‐as‐usual) and biological invasion on the biomass of major freshwater trophic groups (phytoplankton, zooplankton, periphyton, macroinvertebrates, and a native macrophyte) and the decomposition rate of allochthonous material. Among the independent effects, we found that the business‐as‐usual climate treatment resulted in lower native macrophyte biomass and higher periphyton biomass compared to the climatic baseline and mitigation treatments. This indicates the potential of climate change to alter the relative dominance of different freshwater producers and demonstrates that climate mitigation efforts can counteract these effects. Biological invasion alone increased the biomass of chironomids, a dominant macroinvertebrate group in tropical freshwater ecosystems, demonstrating a compensatory effect on climate change. Climate change and biological invasion interactively reduced the decomposition rate of allochthonous detritus, likely mediated by the feeding preference of abundant chironomids for periphytic algae associated with the presence of non‐native macrophytes. We concluded that (i) climatic mitigation can maintain climate baseline conditions in freshwater ecosystems, and (ii) the interactive effects between future climate scenarios and biological invasion are related to complex cascading interactions among trophic groups on ecosystem processes.

P02-28 Microfluidics technology as a tool to improve maturation and drug metabolism capacity of stem cell-derived hepatocytes in vitro - J.S. Rodrigues; S. Relvas; P.G. Condelipes; B. Silva; R. Bozzo; P. Guedes de Pinho; V. Chu; F. Remião; J.P. Conde; J.P. Miranda (Toxicology Letters, 2024)

P02-12 Development of a hepatic spheroid co-culture model for prediction of cholestatic drug-induced liver injury - J. Sanz-Serrano; A. Drees; P. Olaizola; J. Bañales; P. Rodrigues; M. Vinken (Toxicology Letters, 2024)

Exploring the proton translocation mechanism in Complex I by integrative biophysical methods - Sofia Badolato; Jobst Liebau; Adel Beghiah; Henrique Rodrigues; Tobias Fritz; Andrea Gangdal; Hyunho Kim; Ana P. Gamiz-Hernandez; Abhishek Sirohiwal; Patricia Saura; Ville R.I. Kaila (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Resistance training improves cardiac function in older women: a randomized controlled trial - Ricardo J. Rodrigues; Paolo M. Cunha; João P. Nunes; Lauro C. Vianna; Patrícia C. Brum; Danilo S. Bocalini; Andrei C. Sposito; Luis C. Miguita Junior; Max D. Oliveira; Elaine Batistella; Rodrigo R. Fernandes; Paulo S. Junior; et al. (GeroScience, 2024)

Assessing interpreter’s disagreements in land cover reference data collection from historical Landsat time series in Amazon - Mariane S. Reis; Lucélia S. de Barros; Manoel R. Rodrigues Neto; Dayane Rafaela V. de Moraes; Noeli Aline P. Moreira; Gabriel Mikael R. Alves; Bruno V. Adorno; Cassiano Gustavo Messias; Luciano V. Dutra; Camilo D. Rennó; Sidnei João S. Sant’Anna; Maria Isabel S. Escada (International Journal of Remote Sensing, 2024)

The thermal equation of state of xenon: Implications for noble gas incorporation in serpentine minerals and their transport to depth - A.D. Rosa; F. Zecchi; P. Condamine; M.A. Bouhifd; J.E.F.S. Rodrigues; E. Mijit; T. Irifune; O. Mathon; G. Garbarino; M. Mezouar; A. Dewaele; N. Ishimatsu (Geochimica et Cosmochimica Acta, 2024)

Effects of post-exercise cold-water immersion on performance and perceptive outcomes of competitive adolescent swimmers - Natanael P. Batista; Flávia A. de Carvalho; Caio R. D. Rodrigues; Jéssica K. Micheletti; Aryane F. Machado; Carlos M. Pastre (European Journal of Applied Physiology, 2024)
Purpose To evaluate the effects of repeated use of cold-water immersion (CWI) during a training week on performance and perceptive outcomes in competitive adolescent swimmers. Methods This randomized-crossover study included 20 athletes, who received each intervention [CWI (14 ± 1 °C), thermoneutral water immersion (TWI) (27 ± 1 °C) as placebo, and passive recovery (PAS)] three times a week between the land-based resistance training and swim training. The interventions were performed in a randomized order with a 1-week wash-out period. We tested athletes before and after each intervention week regarding swim (100 m freestyle sprints) and functional performance (flexibility, upper and lower body power, and shoulder proprioception). We monitored athlete’s perceptions (well-being, heaviness, tiredness, discomfort and pain) during testing sessions using a 5-item questionnaire. Athlete preferences regarding the interventions were assessed at the end of the study. We used generalized linear mixed models and generalized estimating equations for continuous and categorical variables, respectively (intervention x time). Results We found a time effect for swim performance ( p = .01) in which, regardless the intervention, all athletes improved sprint time at post-intervention compared to baseline. There was an intervention effect for pain ( p = .04) and tiredness ( p = .04), but with no significant post-hoc comparisons. We found no significant effects for other outcomes. All athletes reported a preference for CWI or TWI in relation to PAS. Conclusion The repeated use of CWI throughout a training week did not impact functional or swim performance outcomes of competitive adolescent swimmers. Perceptive outcomes were also similar across interventions; however, athletes indicated a preference for both CWI and TWI.

The role of microRNAs in NBS-LRR gene expression and its implications for plant immunity and crop development - J. C. M. Rodrigues; J. Carrijo; R. M. Anjos; N. B. Cunha; P. Grynberg; F. J. L. Aragão; G. R. Vianna (Transgenic Research, 2024)

A novel tool for modeling the near- and far-field dispersion of brine effluent from desalination plants - Silvano Porto Pereira; Melissa Fontenelle Rodrigues; Paulo Cesar Colonna Rosman; Patrícia Rosman; Tobias Bleninger; Iran Eduardo Lima Neto; Carlos E. P. Teixeira; Iván Sola; José Luis Sánchez Lizaso (Frontiers in Marine Science, 2024)
Regardless of the specific technology adopted, the use of desalination to produce fresh water from seawater results in a discharge of brine effluent containing a high concentration of salts and other desalination by-products that must be dealt with appropriately. Until now, this effluent has most commonly been discharged into the sea through a submarine outfall. Computational tools are used to simulate the behavior of these brine discharges to minimize their impact on the marine environment. Environmental assessments of desalination plants that are made using these tools can include consideration of the rates of effluent production and flow, diffuser configurations, marine conditions (e.g., currents, tides, salinity, temperature), and the proximity of plants to environmentally significant areas. Computational tools can also assist in the design of programs for monitoring the surroundings of brine disposal points. In this study, we developed a new tool for modeling brine discharges from submarine outfalls based on an adaptation of a near-field mathematical model coupled with a Lagrangian model. This new model was specifically designed for application to negatively buoyant effluent discharges. The near-field dilution results that were obtained for various current velocities and different diffuser vertical inclinations using this tool were compared with those obtained using a reference tool (Visual Plumes), considering four different desalination plants. Excellent correlation and a mean absolute percentage error lower than 10% were obtained between the two sets of results along with good reproducibility. Additionally, the existence of an integrated wave propagation model in the simulation software allowed the analysis of changes in the brine plume direction produced by waves formed far from the outfall area. Using the new model, it was possible to evaluate how the diffuser configuration affected the performance of the diffuser line, and the saline plume generated by the combined Lagrangian and near-field model realistically reproduced the behavior of a submarine brine outfall. This combined model is potentially applicable to a range of other situations, including studies that aim to minimize the environmental impact of desalination plants based on considerations of outfall locations and optimization of the diffuser configuration.

Adsorption of methane by modified-biochar aiming to improve the gaseous fuels storage/transport capacity: process evaluation and modeling - Ederson F. Klitzke; Felipe Ketzer; Manuelle O. P. Almeida; Jean F. F. Calisto; João H. C. Wancura; Clovis A. Rodrigues; José Vladimir Oliveira; Jacir Dal Magro (Environmental Science and Pollution Research, 2024)

Nitrogen efficiency indices for sustainable sweet potato production in tropical environments - Adalton M. Fernandes; Patricio Sandaña; Rogério P. Soratto; Nathalia P. Ribeiro; Fabricio E. Rodrigues; Ítala T. Guimarães (Field Crops Research, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Cytotoxic screening of plants from the Brazilian Atlantic Forest has led to the identification of Casearia arborea and Sorocea hilarii as sources of antitumor compounds - L. A. Rodrigues; A. A. Almeida; A. P. Agrizii; N. Pacheco; B. C. R. Carvalho; A. C. Zanatta; M. Kohlhoff; C. M. M. E. Torres; G. C. Bressan; J. P. V. Leite (Natural Product Research, 2024)

Saline as solvent and ethanol-based purification process for the extraction of proteins and isoflavones from wet okara - Rafaela T. Privatti; Maria C. Capellini; Keila K. Aracava; Silvana M.P. Pugine; Mariza P. de Melo; Christianne E.C. Rodrigues (Food Chemistry, 2024)

ENSO effects on the relationship between aerosols and evapotranspiration in the south of the Amazon biome - Rafael Palácios; Daniela Castagna; Luzinete Barbosa; Adilson P. Souza; Breno Imbiriba; Cornélio A. Zolin; Danielle Nassarden; Leilane Duarte; Fernando G. Morais; Marco A. Franco; Glauber Cirino; Paulo Kuhn; et al. (Environmental Research, 2024)

A densely sampled molecular phylogeny of Tachigali (Leguminosae), an evolutionarily successful lineage of neotropical ant-housing canopy trees - Isau Huamantupa-Chuquimaco; Vitor Hugo Maia; Haroldo Cavalcante de Lima; Maristerra Rodrigues Lemes; Cristiane Snak; Bernarda Gregório; Sérgio Ricardo S. Cardoso; Luciano Paganucci de Queiroz; Charles E. Zartman; Gwilym P. Lewis; Euan K. James; Kyle G. Dexter; et al. (Brazilian Journal of Botany, 2024)

The cost of genetic diagnosis of suspected hereditary pediatric cataracts with whole-exome sequencing from a middle-income country perspective: a mixed costing analysis - Luiza M. Neves; Márcia Pinto; Olivia A. Zin; Daniela P. Cunha; Bruna N. S. Agonigi; Fabiana L. Motta; Leonardo H. F. Gomes; Dafne D. G. Horovitz; Daltro C. Almeida; Jocieli Malacarne; Leticia Guida; Andressa Braga; et al. (Journal of Community Genetics, 2024)
Up to 25% of pediatric cataract cases are inherited. There is sparse information in the literature regarding the cost of whole-exome sequencing (WES) for suspected hereditary pediatric cataracts. Molecular diagnosis of suspected hereditary pediatric cataracts is important for comprehensive genetic counseling. We performed a partial economic evaluation with a mixed costing analysis, using reimbursement data and microcosting approach with a bottom-up technique to estimate the cost of using WES for genetic diagnosis of suspected hereditary pediatric cataracts from the perspective of the Brazilian governmental health care system. One hundred and ten participants from twenty-nine families in Rio de Janeiro (RJ) were included. Costs of consumables, staff and equipment were calculated. Two scenarios were created: (1) The reference scenario included patients from RJ with suspected hereditary pediatric cataracts plus two family members. (2) The alternative scenario considered other genetic diseases, resulting in 5,280 exams per month. Sensitivity analysis was also performed. In the reference scenario, the total cost per exam was 700.09 United States dollars (USD), and in the alternative scenario, the total cost was 559.23 USD. The cost of WES alone was 527.85 USD in the reference scenario and 386.98 USD in the alternative scenario. Sensitivity analysis revealed that the largest costs were associated with consumables in both scenarios. Economic evaluations can help inform policy decisions, especially in middle-income countries such as Brazil.

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Gravity separation of fine itabirite iron ore using the Reflux Classifier – Part II – Establishing the underpinning partition surface - Armando F.d.V. Rodrigues; Homero Delboni Junior; James Zhou; Kevin P. Galvin (Minerals Engineering, 2024)

Inflammatory infiltrate in the feline mammary gland: healthy, non-neoplastic, benign and malignant lesions - J. Rodrigues-Jesus; A.C. Figueira; C. Marrinhas; G.N. Petrucci; H. Gregório; F. Tinoco; A. Goulart; H. Felga; H. Vilhena; A. Canadas-Sousa; P. Dias-Pereira (Journal of Comparative Pathology, 2024)

An acute bout of resistance exercise increases BDNF in hippocampus and restores the long-term memory of insulin-resistant rats - Camila Berbert-Gomes; Júlia S. Ramos; João G. Silveira-Rodrigues; Daniel M. M. Leite; Bruno P. Melo; Danusa D. Soares (Experimental Brain Research, 2024)

Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Evandro P. Prado; Júlio C. Guerreiro; Pedro J. Ferreira-Filho; Vagner do Nascimento; Samuel Ferrari; Fernando S. Galindo; Marina Funichello; Carlos G. Raetano; Paulo H. Pagliari; Rodolfo G. Chechetto; Arthur D. Rodrigues Neto (Crop Protection, 2024)

Effect of ramial chipped wood and poultry manure amendments on soil chemical properties and fungal communities in Benin - Rodrigue Daassi; Damase P. Khasa; Tatjana Stevanovic (Soil and Tillage Research, 2024)

Diversification of the terrestrial frog genus Anomaloglossus (Anura, Aromobatidae) in the Guiana Shield proceeded from highlands to lowlands, with successive loss and reacquisition of endotrophy - Jean-Pierre Vacher; Philippe J.R. Kok; Miguel Trefaut Rodrigues; Albertina Lima; Tomas Hrbek; Fernanda P. Werneck; Sophie Manzi; Christophe Thébaud; Antoine Fouquet (Molecular Phylogenetics and Evolution, 2024)

Extraction of phenolic compounds from grape pomace using ohmic heating: Chemical composition, bioactivity and bioaccessibility - P. Ferreira-Santos; C. Nobre; R.M. Rodrigues; Z. Genisheva; C. Botelho; J.A. Teixeira (Food Chemistry, 2024)

Role of vulvovaginal candidiasis infection in infertility: systematic review and meta-analysis - Ana Luiza P. Córdova; Stéfani Z. M. Fontanella; Tamy Colonetti; Maria Laura Rodrigues Uggioni; Antonio José Grande; Maria Carolina Saggioratto; Eduardo Schmitt Testoni; Maria Inês Rosa (Brazilian Journal of Microbiology, 2024)

Fluoxetine alters rat's milk properties causing impact on offspring's development - Gabriel R. Abreu; Julia Zaccarelli-Magalhães; Laís S. Féba; Emily Y. Penna; Julia P. Silva; Mariana V. Teixeira; Marianna Manes; Guilherme A. Vergara; Leonardo M.A. Rodrigues; André R. Fukushima; Esther L. Ricci; Helenice S. Spinosa (Toxicology and Applied Pharmacology, 2024)

First evidence of microplastics in commercial mussels from Amazonian estuaries - João M.S. Rodrigues; Juliana C.D. Pantoja; Antonio E.P. Oliveira; Maria A.P. Ferreira; Zélia M.P. Nunes; Bruno Nunes; Luiz P. Costa; Roberta M. Santos; Rossineide M. Rocha (Regional Studies in Marine Science, 2024)

Microrheological characterisation of Cyanoflan in human blood plasma - T. Rodrigues; R. Mota; L. Gales; P. Tamagnini; L. Campo-Deaño (Carbohydrate Polymers, 2024)

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Exceptionally well-preserved orthopteran proventriculi from the Cretaceous Crato Formation of Brazil - Arianny P. Storari; Gabriel L. Osés; Débora Soares de Almeida-Lima; Marcia A. Rizzutto; Renan Alfredo Machado Bantim; Flaviana Jorge de Lima; Taissa Rodrigues; Juliana Manso Sayão (Journal of South American Earth Sciences, 2024)

Effects of chemical aging on carbonaceous materials: Stability of water-dispersible colloids and their influence on the aggregation of natural-soil colloid - Laís G. Fregolente; Maria T. Rodrigues; Naiara C. Oliveira; Bruno Sousa Araújo; Ícaro V. Nascimento; Antonio G. Souza Filho; Amauri J. Paula; Mirian C.G. Costa; Jaedson C.A. Mota; Odair P. Ferreira (Science of The Total Environment, 2023)

Identifying imprints of externally derived dust and halogens in the sedimentary record of an Iberian alpine lake for the past ∼13,500 years – Lake Peixão, Serra da Estrela (Central Portugal) - J. Moreno; A.M. Ramos; P.M. Raposeiro; R.N. Santos; T. Rodrigues; F. Naughton; F. Moreno; R.M. Trigo; J. Ibañez-Insa; P. Ludwig; X. Shi; A. Hernández (Science of The Total Environment, 2023)

Bio-CH4 yield of swine manure and food waste optimized by co-substrate proportions diluted in domestic sewage and pH interactions using the response surface approach - Franciele P. Camargo; Vitor Lourenço; Caroline Varella Rodrigues; Carolina Aparecida Sabatini; Maria Angela Tallarico Adorno; Edson L. Silva; Maria Bernadete A. Varesche (Journal of Environmental Management, 2023)

Indole-3-carbinol and chlorogenic acid combination modulates gut microbiome and attenuates nonalcoholic steatohepatitis in a murine model - Gabriel P. Bacil; Guilherme R. Romualdo; Josias Rodrigues; Luís F. Barbisan (Food Research International, 2023)

Protocols for the seminal cryopreservation of South American catfishes – current status - Danilo P. Streit; Rômulo B. Rodrigues; Eduardo A. Sanches; Jayme A. Povh; Diógenes H. Siqueira-Silva; Thaíza R. de Freitas; Nathalia T. Santos; Jhony B. Lisboa; Thales S. França; Eduardo Nicoleti; Larise O.C. Lima; Tiantian Zhang (Cryobiology, 2023)

Effects of different subcutaneous sites on heterotopic autotransplantation of canine ovarian tissue - Fabiana AS Brandão; Danielle CC de Brito; Leda MC Pereira; Kele A Alves; Lucy VS Ñaupas; Samara S de Souza; Duanny M de S Cunha; Reginaldo P de S Filho; Benner G Alves; Ana PR Rodrigues; Dárcio IA Teixeira (Veterinary Research Communications, 2023)

An improved reference genome and first organelle genomes of Quercus suber - Ana Usié; Octávio Serra; Pedro M. Barros; Pedro Barbosa; Célia Leão; Tiago Capote; Tânia Almeida; Leandra Rodrigues; Isabel Carrasquinho; Joana B. Guimarães; Diogo Mendoça; Filomena Nóbrega; et al. (Tree Genetics & Genomes, 2023)
Cork oak ( Quercus suber L.) is an ecologically and economically important evergreen tree species native to the Mediterranean region and widespread in southwest Europe and northwest Africa. An improved genome assembly of cork oak using a combination of Illumina and PacBio sequencing is presented in this study. The assembled genome contains 2351 scaffolds longer than 1000 bp, accounting for 765.7 Mbp of genome size, L90 of 755, and a N50 of 1.0 Mbp, with 40,131 annotated genes. The repetitive sequences constitute 53.6% of the genome. The genome sequences of chloroplast and mitochondrion were determined for the first time, with a genome size of 161,179 bp and 531,858 bp, respectively. Phylogenetic analysis based on complete chloroplast genome sequence showed that Q. suber is closely related to Quercus variabilis , two cork-producing species with commercial use. All data generated are available through the public databases, being ready to be used without restrictions. This study provides an improved nuclear genome assembly together with the organelle genomes of cork oak. These resources will be useful for further breeding strategies and conservation programs and for comparative genomic studies in oak species.

Long-term memory in Staphylococcus aureus α-hemolysin ion channel kinetics - M. P. Silva; C. G. Rodrigues; D. C. Machado; R. A. Nogueira (European Biophysics Journal, 2023)

Metallothionein expression in the central nervous system in response to chronic heavy metal exposure: possible neuroprotective mechanism - A. Navarro-Sempere; P. Martínez-Peinado; A. S. Rodrigues; P. V. Garcia; R. Camarinho; G. Grindlay; L. Gras; M. García; Y. Segovia (Environmental Geochemistry and Health, 2023)
It has been reported that volcanoes release several tonnes of mercury per year among other heavy metals through eruptions, fumaroles, or diffuse soil degassing. Since a high percentage of the world's population lives in the vicinity of an active volcano, the aim of this study is to evaluate the accumulation of these metals in the central nervous system and the presence of cellular mechanisms of heavy metal detoxification such as metallothioneins. To carry out this study, wild mice (Mus musculus) chronically exposed to an active volcanic environment were captured in Furnas village (Azores, Portugal) and compared with those trapped in a reference area (Rabo de Peixe, Azores, Portugal). On the one hand, the heavy metal load has been evaluated by analyzing brain and cerebellum using ICP-MS and a mercury analyzer and on the other hand, the presence of metallothionein 2A has been studied by immunofluorescence assays. Our results show a higher load of metals such as mercury, cadmium and lead in the central nervous system of exposed mice compared to non-exposed individuals and, in addition, a higher immunoreactivity for metallothionein 2A in different areas of the cerebrum and cerebellum indicating a possible neuroprotection process.

Gravity separation of fine itabirite iron ore using the Reflux Classifier – Part I – Investigation of continuous steady state separations across a wide range of parameters - Armando F.d.V. Rodrigues; Homero Delboni Junior; Otavia M.S. Rodrigues; James Zhou; Kevin P. Galvin (Minerals Engineering, 2023)

Ethylene photocatalytic degradation using TiO2 immobilized in a NETmix mili-photoreactor - Jéssica de Matos Fonseca; Sandra M. Miranda; Joana P. Monteiro; Regina de Fátima Peralta Muniz Moreira; Germán Ayala Valencia; Alcilene Rodrigues Monteiro; Vítor J.P. Vilar (Journal of Environmental Chemical Engineering, 2023)

Flexible thermoelectric energy harvesting system based on polymer composites - T. Rodrigues-Marinho; V. Correia; C.-R. Tubio; A. Ares-Pernas; M.-J. Abad; S. Lanceros-Méndez; P. Costa (Chemical Engineering Journal, 2023)

Anti-Candida Potential of Peptides from Immature and Ripe Fruits of Capsicum chinense Jacq - Marilucia C. Ribeiro; Rodrigo S. Gebara; Gabriel B. Taveira; André de O. Carvalho; Rosana Rodrigues; Erica O. Mello; Celso S. Nagano; Renata P. Chaves; Valdirene M. Gomes (Probiotics and Antimicrobial Proteins, 2023)

Detection of Equus caballus Papillomavirus in Equine Aural Plaque Samples - Cristiana R. Bromberger; Julia Rodrigues Costa; Mariana Herman; Juliana Mira Hernandez; Lukas Garrido Albertino; Carlos Eduardo Fonseca Alves; Alexandre S. Borges; Jose P. Oliveira-Filho (Journal of Equine Veterinary Science, 2023)

On the quiet-time occurrence rates, severity and origin of L-band ionospheric scintillations observed from low-to-mid latitude sites located in Puerto Rico - J. Gomez Socola; J. Sousasantos; F.S. Rodrigues; C.G.M. Brum; P. Terra; A.O. Moraes; R. Eastes (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Plastisphere composition in a subtropical estuary: Influence of season, incubation time and polymer type on plastic biofouling - Tobias Sérvulo; Joe D. Taylor; Maíra C. Proietti; Lucas d.S. Rodrigues; Igor P. Puertas; Roberta A. Barutot; Ana L.d.F. Lacerda (Environmental Pollution, 2023)

Silicon, magnesium, and their interaction on wheat resistance against blast - Marcela U. P. Araujo; Lillian M. Oliveira; Leandro C. Silva; Luiz F. C. C. Pinto; Isaias S. Cacique; Fabrício A. Rodrigues (Plant and Soil, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Transforming iron ore processing – Simplifying the comminution and replacing reverse flotation with magnetic and gravity separation - Armando F. d. V. Rodrigues; Homero Delboni; Klaydison Silva; James Zhou; Kevin P. Galvin; Lev O. Filippov (Minerals Engineering, 2023)

[8] and [10]-Gingerol reduces urothelial damage in ifosfamide-induced hemorrhagic cystitis via JAK/STAT/FOXO signaling pathway via IL-10 - Francisco C. S. Ferreira; Marco Clementino; Francisco A. P. Rodrigues; Herlice N. Veras; Dainesy S. Martins; Marcus L. Queiroga; Mikael A. Lima; Dayara O. Silva; Thiago M. de Freitas; Samilly A. Ribeiro; Mario R. L. Mota; James A. da Silva; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Body size and its correlates in fruit-feeding butterflies in a seasonal environment - Geraldo de Brito Freire; Danielle Salcido; Hernani F. M. Oliveira; Danilo B. Ribeiro; Diogo B. Provete; Thayane Silva; Joao Paulo Dias; Hanna P. Rodrigues; Jessie P. Santos; Ivone R. Diniz (Journal of Insect Conservation, 2023)

Optimizing Reservoir Water Management in a Changing Climate - Pedro Beça; António C. Rodrigues; João P. Nunes; Paulo Diogo; Babar Mujtaba (Water Resources Management, 2023)
One of the UN agenda 2030 Sustainable Development goals is associated with water availability and its sustainable management. The present study intends to improve multipurpose reservoir management under climate change scenarios in water scarce regions such as the Mediterranean. Implemented methods include the sequential use of climate model results, hydrological modelling, and reservoir water balance simulation, which are used to estimate future water availability. This work focuses on developing an innovative reservoir management approach based on rule curves and a dynamic assessment of water needs, to improve the management of reservoirs that are dependent on a water transfer system. The proposed methods are implemented in two reservoirs located in a typical Mediterranean river basin and assessed under long-term climate change scenarios up to the year 2100. The results show that the proposed approach can ensure 100% of the urban water supply, improve the reliability of the irrigation supply from 75% to 86–91%, and provide 92–98% of the river ecological flow. It is also demonstrated that this management approach is beneficial, particularly in the case of multipurpose reservoirs in watersheds facing water scarcity risks, to optimize the balance between supply reliability, water transfer volumes, and costs.

Coexistence of two sympatric hermit crab species from South Brazil: the effect of the shell adequacy index and circadian movement patterns - Alexandre R. da Silva; Renan A. P. Santos; Gabriel F. B. Rodrigues; Neida R. Vieira; Bruna K. Baroni; Rafael A. Gregati (Aquatic Ecology, 2023)

Multiproxy reconstruction of late quaternary upper ocean temperature in the subtropical southwestern Atlantic - Joana F. Cruz; Ioanna Bouloubassi; Arnaud Huguet; Alice M.S. Rodrigues; Thiago P. Santos; Igor M. Venancio; Douglas Lessa; Rodrigo L. Sobrinho; Rodrigo A. Nascimento; Marcelo C. Bernardes (Quaternary Science Reviews, 2023)

A 50 kyr record of eolian sedimentation in the Eastern Arabian Sea – Dust deposition changes synchronous with the Northern Hemisphere Climatic Oscillations - Tyson Sebastian; B. Nagender Nath; M.B.L. Mascarenhas-Pereira; M. Venkateshwarlu; Tanvi Mungekar; Dryden Joe Rodrigues; K. Suresh; P. Linsy (Marine Geology, 2023)

Customized tissue microarray molds suitable for different histological workflows - J. De-Carvalho; J. Rodrigues-Lóios; A. Mindouro; R. Leite; P. Faísca (Journal of Comparative Pathology, 2023)

Modulation of rectal cancer stemness, patient outcome and therapy response by adipokines - Vanda Marques; Susana Ourô; Marta B. Afonso; Cecília M. P. Rodrigues (Journal of Physiology and Biochemistry, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Forage based diet as an alternative to a high concentrate diet for finishing young bulls - Effects on growth performance, greenhouse gas emissions and meat quality - José Santos-Silva; Susana P. Alves; Alexandra Francisco; Ana Paula Portugal; Maria Teresa Dentinho; João Almeida; José Leandro Regedor da Silva; Letícia Fialho; Liliana Cachucho; Eliana Jerónimo; Ana Barradas; António Rodrigues; et al. (Meat Science, 2023)

Carbamazepine, venlafaxine, tramadol, and their main metabolites: Toxicological effects on zebrafish embryos and larvae - P. Rodrigues; L. Guimarães; AP. Carvalho; L. Oliva-Teles (Journal of Hazardous Materials, 2023)

Limited impacts of the fungus Syncephalastrum on nests of leaf-cutting ants - Keminy R. Bautz; Marcela C.S. Caixeta; Nathalia P. Del Puppo; André Rodrigues; Thiago G. Kloss; Simon L. Elliot (Fungal Ecology, 2023)

NMDA receptor-mediated modulation on glutamine synthetase and glial glutamate transporter GLT-1 is involved in the antidepressant-like and neuroprotective effects of guanosine - Anderson Camargo; Ana P. Dalmagro; Glorister A. Altê; Ana Lúcia B. Zeni; Carla I. Tasca; Ana Lúcia S. Rodrigues (Chemico-Biological Interactions, 2023)

Unveiling the membrane bound dihydroorotate: Quinone oxidoreductase from Staphylococcus aureus - Filipe M. Sousa; Patrícia Pires; Andreia Barreto; Patrícia N. Refojo; Micael S. Silva; Pedro B. Fernandes; Ana P. Carapeto; Tiago T. Robalo; Mário S. Rodrigues; Mariana G. Pinho; Eurico J. Cabrita; Manuela M. Pereira (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Later prehistoric tin mining in the Ervedosa mine (Vinhais, Portugal): evidence and context - Emmanuelle Meunier; Filipa Dias; João Fonte; Alexandre Lima; Alexandra Rodrigues; Carlo Bottaini; Rui J. C. Silva; João P. Veiga; Manuel F. C. Pereira; Elin Figueiredo (Archaeological and Anthropological Sciences, 2023)

Ingestion of polystyrene microparticles impairs survival and defecation in larvae of Polistes satan (Hymenoptera: Vespidae) - André Rodrigues de Souza; Rodrigo Cupertino Bernardes; Wagner Faria Barbosa; Thaís Andrade Viana; Fábio Santos do Nascimento; Maria Augusta P. Lima; Gustavo Ferreira Martins (Environmental Science and Pollution Research, 2023)

Pre-assessments of plant conservation status in islands: the case of French Overseas Territories - S. Véron; A. Bernard; E. Lebreton; C. Rodrigues-Vaz; M. Durand; L. Procopio; M. Hélion; M. Gayot; G. Viscardi; G. A. Krupnick; C. M. S. Carrington; V. Boullet; et al. (Biodiversity and Conservation, 2023)

Food safety concerns on polycyclic aromatic hydrocarbon contamination in fish products from estuarine bays throughout the American continent - Júlia Vianna de Pinho; Amanda P. Lopes; Paloma de Almeida Rodrigues; Rafaela Gomes Ferrari; Rachel Ann Hauser-Davis; Carlos Adam Conte-Junior (Science of The Total Environment, 2023)

Methyl benzoate and nerolidol attract the cyclocephaline beetle Cyclocephala paraguayensis to trumpet flowers - Arodí P. Favaris; Amanda C. Túler; Weliton D. Silva; Marvin Pec; Sérgio R. Rodrigues; Artur C. D. Maia; José Maurício S. Bento (The Science of Nature, 2023)

Endotoxin tolerance and low activation of TLR-4/NF-κB axis in monocytes of COVID-19 patients - Gilson P. Dorneles; Paula C. Teixeira; Alessandra Peres; Luiz Carlos Rodrigues Júnior; Simone Gonçalves da Fonseca; Marta Chagas Monteiro; Sarah Eller; Tiago F. Oliveira; Eliana M. Wendland; Pedro R. T. Romão (Journal of Molecular Medicine, 2023)

Pharmacological evaluation of antinociceptive and anti-inflammatory activities of LQFM202: a new piperazine derivative - Aline N. Martins; Dionys de Souza Almeida; Iziara F. Florentino; Lorrane K. da Silva Moreira; Larissa C. Turones; Daniel C. Batista; Lucas S. Machado; Boniek G. Vaz; Luciano M. Lião; Gerlon de Almeida Ribeiro Oliveira; José Luís Rodrigues Martins; James Oluwagbamigbe Fajemiroye; et al. (Inflammopharmacology, 2023)

Connectivity between countries established by landbirds and raptors migrating along the African–Eurasian flyway - João L. Guilherme; Victoria R. Jones; Inês Catry; Martin Beal; Maria P. Dias; Steffen Oppel; Juliet A. Vickery; Chris M. Hewson; Stuart H. M. Butchart; Ana S. L. Rodrigues (Conservation Biology, 2023)
The conservation of long‐distance migratory birds requires coordination between the multiple countries connected by the movements of these species. The recent expansion of tracking studies is shedding new light on these movements, but much of this information is fragmented and inaccessible to conservation practitioners and policy makers. We synthesized current knowledge on the connectivity established between countries by landbirds and raptors migrating along the African–Eurasian flyway. We reviewed tracking studies to compile migration records for 1229 individual birds, from which we derived 544 migratory links, each link corresponding to a species’ connection between a breeding country in Europe and a nonbreeding country in sub‐Saharan Africa. We used these migratory links to analyze trends in knowledge over time and spatial patterns of connectivity per country (across species), per species (across countries), and at the flyway scale (across all countries and all species). The number of tracking studies available increased steadily since 2010 (particularly for landbirds), but the coverage of existing tracking data was highly incomplete. An average of 7.5% of migratory landbird species and 14.6% of raptor species were tracked per country. More data existed from central and western European countries, and it was biased toward larger bodied species. We provide species‐ and country‐level syntheses of the migratory links we identified from the reviewed studies, involving 123 populations of 43 species, migrating between 28 European and 43 African countries. Several countries (e.g., Spain, Poland, Ethiopia, Democratic Republic of Congo) are strategic priorities for future tracking studies to complement existing data, particularly on landbirds. Despite the limitations in existing tracking data, our data and results can inform discussions under 2 key policy instruments at the flyway scale: the African–Eurasian Migratory Landbirds Action Plan and the Memorandum of Understanding on the Conservation of Migratory Birds of Prey in Africa and Eurasia.

Are mercury levels in fishery products appropriate to ensure low risk to high fish-consumption populations? - Elsa T. Rodrigues; João P. Coelho; Eduarda Pereira; Miguel A. Pardal (Marine Pollution Bulletin, 2023)

MS-FINDER and SIRIUS for phenolic compound identification from high-resolution mass spectrometry data - Luana P. Mallmann; Alessandro O. Rios; Eliseu Rodrigues (Food Research International, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Diversification of the Pristimantis conspicillatus group (Anura: Craugastoridae) within distinct neotropical areas throughout the Neogene - Antoine Fouquet; Alexandre Réjaud; Miguel T. Rodrigues; Santiago R. Ron; Juan C. Chaparro; Mariela Osorno; Fernanda P. Werneck; Tomas Hrbek; Albertina P. Lima; Teresa Camacho-Badani; Andres F. Jaramillo-Martinez; Jérôme Chave (Systematics and Biodiversity, 2022)

Withalutin, a new cytotoxic withanolide from Athenaea velutina (Sendtn.) D’Arcy - Alisson A. Almeida; Betania B. Cota; Laís A. Rodrigues; Luana L. Dutra; Markus Kohlhoff; Gustavo C. Bressan; Geraldo C. Brandão; João P. V. Leite (Natural Product Research, 2022)

Triiodothyronine Treatment reverses Depression-Like Behavior in a triple-transgenic animal model of Alzheimer’s Disease - Andréa V. Maglione; Bruna P. P. do Nascimento; Miriam O. Ribeiro; Talytha J. L. de Souza; Renata E. C. da Silva; Monica A. Sato; Carlos A. A. Penatti; Luiz R. G. Britto; Janaina S. de Souza; Rui M.B. Maciel; Rodrigo Rodrigues da Conceição; Roberto Laureano-Melo; et al. (Metabolic Brain Disease, 2022)

Occurrence of Pharmaceutical and Pesticide Transformation Products in Freshwater: Update on Environmental Levels, Toxicological Information and Future Challenges - P. Rodrigues; L. Oliva-Teles; L. Guimarães; A. P. Carvalho (Reviews of Environmental Contamination and Toxicology, 2022)

The need for European harmonization of Nutrivigilance in a public health perspective: a comprehensive review - G. Vo Van Regnault; M. C. Costa; A. Adanić Pajić; A. P. Bico; S. Bischofova; U. Blaznik; F. Menniti-Ippolito; K. Pilegaard; C. Rodrigues; I. Margaritis (Critical Reviews in Food Science and Nutrition, 2022)

The success of algae with luxury P uptake and mixotrophy in P-limiting periphyton within-reservoir spatial heterogeneity - Carla Ferragut; Thiago Rodrigues dos Santos; Barbara Golebski Pellegrini; Mariane Lima Souza; Eduardo P. C. Gomes (Hydrobiologia, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Seasonal approach to forecast the suitability of spawning habitats of a temperate small pelagic fish under a high-emission climate change scenario - André R. A. Lima; Susana Garrido; Isabel Riveiro; Diana Rodrigues; Maria M. P. Angélico; Emanuel J. Gonçalves; Myron A. Peck; Gonçalo Silva (Frontiers in Marine Science, 2022)
Spawning habitats of cold-water, European small pelagic fishes have shifted poleward in the last three decades coincident with gradual ocean warming. We predicted present-day, season-specific habitat suitability for spawning by European sardine Sardina pichardus in the Atlantic Ocean and Mediterranean and Black Seas, and projected climate-driven changes in suitable areas from 2050-2099 under the IPCC – RCP 8.5 scenario. Sea surface temperature and distance to the coast had the greater influences in spawning habitats, reflecting the temperature- and coastal-dependent spawning of sardines. Chlorophyll- a was the third most important explanatory variable for spawning in winter to summer. Winds were predominantly important during autumn, whilst sea surface salinity was an important driver during spring and summer. Present-day, “hotspots” for spawning were identified in regions of highly productive, salty waters, where SST was between 6 and 18°C from autumn to spring or 16 and 25°C during summer and favourable winds occurred that would retain eggs and larvae closer to the coast (< 250 km). For future scenarios, forecasts indicate that environmental optima for spawning is projected to be in regions where SST varies between 11°C and 18°C from autumn to spring; and between 18°C and 24°C during summer. However, a negative relationship between phytoplankton productivity and habitat suitability induced by warming is likely to occur in the future. Projections suggest that suitable spawning habitats in all seasons will shift to higher latitudes, with a prominent range expansion along the coast of Norway during winter and autumn (> 83%). The total spawning area, however, was projected to contract in the future during spring (-10.5%) and autumn (-4.1%) due to losses of currently suitable areas along the Atlantic African Coast and Mediterranean Sea. Such regions currently support the greatest sardine stocks but climate-driven warming and decreased plankton productivity are projected to make these areas unsuitable for spawning and likely also for sardine fisheries in future.

Sugarcane: A Promising Source of Green Carbon in the Circular Bioeconomy - Susan G. Karp; Walter J. M. Burgos; Luciana P. S. Vandenberghe; Kim V. Diestra; Luis A. Z. Torres; Adenise L. Woiciechowski; Luiz A. J. Letti; Gilberto V. M. Pereira; Vanete Thomaz-Soccol; Cristine Rodrigues; Júlio C. de Carvalho; Carlos R. Soccol (Sugar Tech, 2022)

Epithelial morphometric alterations and mucosecretory responses in the nasal cavity of mice chronically exposed to hydrothermal emissions - R. Camarinho; A. Madrero Pardo; P. V. Garcia; A. S. Rodrigues (Environmental Geochemistry and Health, 2022)

Pleurotus strains with remediation potential to remove toxic metals from Doce River contaminated by Samarco dam mine - M. P. O. Santos; M. V. N. Santos; R. S. Matos; A. S. Van Der Maas; M. C. S. Faria; B. L. Batista; J. L. Rodrigues; C. A. Bomfeti (International Journal of Environmental Science and Technology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

QSAR-Guided Proposition of N-(4-methanesulfonyl)Benzoyl-N’-(Pyrimidin-2-yl)Thioureas as Effective and Safer Herbicides - Natânia E. Rodrigues; Adriana C. de Faria; Ingrid V. Pereira; Elaine F. F. da Cunha; Matheus P. Freitas (Bulletin of Environmental Contamination and Toxicology, 2022)

Occurrence of Volcanogenic Inorganic Mercury in Wild Mice Spinal Cord: Potential Health Implications - A. Navarro-Sempere; M. García; A. S. Rodrigues; P. V. Garcia; R. Camarinho; Y. Segovia (Biological Trace Element Research, 2022)
Mercury accumulation has been proposed as a toxic factor that causes neurodegenerative diseases. However, the hazardous health effects of gaseous elemental mercury exposure on the spinal cord in volcanic areas have not been reported previously in the literature. To evaluate the presence of volcanogenic inorganic mercury in the spinal cord, a study was carried out in São Miguel island (Azores, Portugal) by comparing the spinal cord of mice exposed chronically to an active volcanic environment (Furnas village) with individuals not exposed (Rabo de Peixe village), through the autometallographic silver enhancement histochemical method. Moreover, a morphometric and quantification analysis of the axons was carried out. Results exhibited mercury deposits at the lumbar level of the spinal cord in the specimens captured at the site with volcanic activity (Furnas village). A decrease in axon calibre and axonal atrophy was also observed in these specimens. Given that these are relevant hallmarks in the neurodegenerative pathologies, our results highlight the importance of the surveillance of the health of populations chronically exposed to active volcanic environments.

Level of genetic divergence among accessions of the native forage grass, Mesosetum chaseae Luces, for tracing strategies to conservation of germplasm collections from the brazilian pantanal - Ana Clara de Sousa Meirelles; Eliane Rodrigues Monteiro; Claudete Aparecida Mangolin; Sandra Aparecida Santos; Maria de Fátima P. S. Machado (Conservation Genetics Resources, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Optical time series for the separation of land cover types with similar spectral signatures: cocoa agroforest and forest - João E. Batista; Nuno M. Rodrigues; Ana I. R. Cabral; Maria J. P. Vasconcelos; Adriano Venturieri; Luiz G. T. Silva; Sara Silva (International Journal of Remote Sensing, 2022)

Correction to: Basic oxygen furnace sludge to treat industrial arsenic- and sulfate‑rich acid mine drainage - Sandrine F. Araujo; Cláudia L. Caldeira; Virginia S. T. Ciminelli; Ricardo P. Borba; Joanna P. Rodrigues; Gustavo F. Simões (Environmental Science and Pollution Research, 2022)

Basic oxygen furnace sludge to treat industrial arsenic- and sulfate-rich acid mine drainage - Sandrine F. Araujo; Cláudia L. Caldeira; Virginia S. T. Ciminelli; Ricardo P. Borba; Joanna P. Rodrigues; Gustavo F. Simões (Environmental Science and Pollution Research, 2022)

Phosphorus in soils and fluvial sediments from a Cerrado biome watershed under agricultural expansion - Fernando Braga Rimá; Yuri Jacques Agra Bezerra da Silva; Marcos Paulo Rodrigues Teixeira; Angelo Jamil Maia; Kamylla Gonçalves Oliveira Assis; Rayanna Jacques Agra Bezerra da Silva; Valdomiro Severino de Souza Júnior; Ygor Jacques Agra Bezerra da Silva; José Wellington Batista Lopes; Ronny Sobreira Barbosa; Vijay P. Singh (Environmental Monitoring and Assessment, 2022)

Onset and demise dates of the rainy season in the South American monsoon region: A cluster analysis result - Maria A. M. Rodrigues; Sâmia R. Garcia; Mary T. Kayano; Alan J. P. Calheiros; Rita V. Andreoli (International Journal of Climatology, 2022)
This work proposes an adaptation of the method developed in previous papers to determine the onset and demise of the rainy season (ONR and DER) dates in the areas of the South American monsoon system (SAMS) based on the pentad antisymmetric outgoing long‐wave radiation (AOLR). In those papers, the sign change of the mean AOLR in the central Amazon Basin (CAM) and western central Brazil (WCB) from positive to negative defined the ONR, from negative to positive, the DER dates. Since the monsoon convection presents a northwest–southeast oriented progression, the antisymmetric area to the WCB was selected subjectively. Thus, here we propose to use the Ward hierarchical clustering method to select areas in the SAMS and in the northern tropical America (NTA) for the regionalized AOLR calculation. The significant (at the 95% confidence level) negative correlations with the largest magnitude among the clusters in the SAMS and NTA and the outgoing long‐wave radiation (OLR) and precipitation annual cycles in each group define the pairs to calculate the AOLR. Then, the AOLR time series is calculated and subjected to a 5‐pentad running mean filter. This method keeps the climatological features of the convection annual cycle such that the closer (farther) the pair is to the equator the longer (shorter) the rainy season. The ONR and DER dates found with this new method are remarkably close to those found previously. Therefore, the new method proposed here highlights regional aspects of rainy season and can easily be automatized for its routine application at the operational climate monitoring centres, for instance at INPE. This is the most important advantage of the method and might be relevant to the SAMS rainy season monitoring.

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Indigenous and local communities can boost seed supply in the UN decade on ecosystem restoration - Danilo Urzedo; Simone Pedrini; Daniel L. M. Vieira; Alexandre B. Sampaio; Bruna D. F. Souza; Eduardo Malta Campos-Filho; Fatima C. M. Piña-Rodrigues; Isabel B. Schmidt; Rodrigo G. P. Junqueira; Kingsley Dixon (Ambio, 2022)
The UN Decade of Ecosystem Restoration is poised to trigger the recovery of ecosystem services and transform structural injustices across the world in a way unparalleled in human history. The inclusion of diverse Indigenous and local communities to co-create robust native seed supply systems is the backbone to achieve the goals for the Decade. Here we show how community-based organizations have co-developed native seed supply strategies for landscape restoration from the bottom-up. We draw on the interconnections over two decades of seed networks in Brazil and the emerging Indigenous participation in native seed production in Australia. From an environmental justice perspective, we provide a participatory seed supply approach for local engagement, noting local geographical, social and cultural contexts. Meeting large-scale restoration goals requires the connection between local seed production and collaborative platforms to negotiate roles, rights and responsibilities between stakeholders. An enduring native seed supply must include a diversity of voices and autonomy of community groups that builds equitable participation in social, economic, and environmental benefits.

Role of the YehD fimbriae in the virulence‐associated properties of enteroaggregative Escherichia coli - Jorge Soria‐Bustos; Waleska Saitz; Abraham Medrano; Cristina Lara‐Ochoa; Zineb Bennis; Valerio Monteiro‐Neto; Camilla Itapary dos Santos; Josias Rodrigues; Rodrigo T. Hernandes; Jorge A. Yáñez; Javier Torres; Fernando Navarro‐García; et al. (Environmental Microbiology, 2022)
Summary The interaction of enteroaggregative Escherichia coli (EAEC) strains with the colonic gut mucosa is characterized by the ability of the bacteria to form robust biofilms, to bind mucin, and induce a local inflammatory response. These events are mediated by a repertoire of five different aggregative adherence fimbriae variants (AAF/I‐V) typically encoded on virulence plasmids. In this study, we report the production in EAEC strains of a new Y eh D f imbriae (YDF), which is encoded by the chromosomal gene cluster yehABCD , also present in most E. coli strains. Immuno‐labelling of EAEC strain 042 with anti‐AAF/II and anti‐YDF antibodies demonstrated the presence of both AAF/II and YDF on the bacterial surface. We investigated the role of YDF in cell adherence, biofilm formation, colonization of spinach leaves, and induction of pro‐inflammatory cytokines release. To this aim, we constructed yehD deletion mutants in different EAEC backgrounds (strains 17‐2, 042, 55989, C1010, 278‐1, J7) each harbouring one of the five AAFs. The effect of the YDF mutation was strain dependent and AAF independent as the lack of YDF had a different impact on the phenotypes manifested by the different EAECs tested. Expression of the yehABCD operon in a E. coli K12 ORN172 showed that YDF is important for biofilm formation but not for adherence to HeLa cells. Lastly, screening of pro‐inflammatory cytokines in supernatants of Caco‐2 cells infected with EAEC strains 042 and J7 and their isogenic Δ yehD mutants showed that these mutants were significantly defective in release of IL‐8 and TNF‐α. This study contributes to the understanding of the complex and diverse mechanisms of adherence of EAEC strains and identifies a new potential target for preventive measures of gastrointestinal illness caused by EAEC and other E. coli pathogroups.

Reduced Cerebellar Brain Inhibition Measured Using Dual-Site TMS in Older Than in Younger Adults - B. K. Rurak; J. P. Rodrigues; B. D. Power; P. D. Drummond; A. M. Vallence (The Cerebellum, 2022)

Financial analysis of a complex agroforestry system for environmental restoration purpose in the Brazilian Rainforest - M. P. Padovan; F. F. Nogueira; F. G. Ruas; A. C. C. Rodrigues; M. F. Arco-Verde (Agroforestry Systems, 2022)

Phylogenomics, introgression, and demographic history of South American true toads ( Rhinella ) - Danielle Rivera; Ivan Prates; Thomas J. Firneno; Miguel Trefaut Rodrigues; Janalee P. Caldwell; Matthew K. Fujita (Molecular Ecology, 2022)
The effects of genetic introgression on species boundaries and how they affect species’ integrity and persistence over evolutionary time have received increased attention. The increasing availability of genomic data has revealed contrasting patterns of gene flow across genomic regions, which impose challenges to inferences of evolutionary relationships and of patterns of genetic admixture across lineages. By characterizing patterns of variation across thousands of genomic loci in a widespread complex of true toads ( Rhinella ), we assess the true extent of genetic introgression across species thought to hybridize to extreme degrees based on natural history observations and multilocus analyses. Comprehensive geographic sampling of five large‐ranged Neotropical taxa revealed multiple distinct evolutionary lineages that span large geographic areas and, at times, distinct biomes. The inferred major clades and genetic clusters largely correspond to currently recognized taxa; however, we also found evidence of cryptic diversity within taxa. While previous phylogenetic studies revealed extensive mitonuclear discordance, our genetic clustering analyses uncovered several admixed individuals within major genetic groups. Accordingly, historical demographic analyses supported that the evolutionary history of these toads involved cross‐taxon gene flow both at ancient and recent times. Lastly, ABBA‐BABA tests revealed widespread allele sharing across species boundaries, a pattern that can be confidently attributed to genetic introgression as opposed to incomplete lineage sorting. These results confirm previous assertions that the evolutionary history of Rhinella was characterized by various levels of hybridization even across environmentally heterogeneous regions, posing exciting questions about what factors prevent complete fusion of diverging yet highly interdependent evolutionary lineages.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Prospecting for a quinoline containing selenium for comorbidities depression and memory impairment induced by restriction stress in mice - Renata L. de Oliveira; Guilherme T. Voss; Karline da C. Rodrigues; Mikaela P. Pinz; Julia V. Biondi; Nicole P. Becker; Eduardo Blodorn; William B. Domingues; Allya Larroza; Vinícius F. Campos; Diego Alves; Ethel A. Wilhelm; et al. (Psychopharmacology, 2022)

Surface functionalization of natural hydroxyapatite by polymerization of β-cyclodextrin: application as electrode material for the electrochemical detection of Pb(II) - Rodrigue Tchoffo; Guy B. P. Ngassa; Giscard Doungmo; Arnaud T. Kamdem; Ignas K. Tonlé; Emmanuel Ngameni (Environmental Science and Pollution Research, 2022)

Household dependence on fish-based farming systems in the Bons Sinais Estuary in Mozambique - Rodrigues P. Francisco; Antonio M. Hoguane; Rosa L. Simbine; Humberto S. Mabota (Western Indian Ocean Journal of Marine Science, 2021)
Households in estuarine deltas of the Western Indian Ocean depend on small-scale fishing, farming in flood-recession and adjacent areas, and mangrove forest products for food security, energy and an income in so-called deltaic fish-based farming (FBF) systems. It was hypothesized that the relative importance of household activities would depend on location along the Bons Sinais Estuary in Mozambique, diversifying in peri-urban settings. Semi-structured interviews were undertaken at five sites, including rural sites near the estuary mouth and upstream, and peri-urban settings near Quelimane city. Fishing contributed the most to FBF livelihoods (54 %) followed by farming (15 %), small business operators (14 %), collection and use of mangrove products (6 %) and other activities such as wage-earning or formal employment (10 %). The highest diversity of activities was at a peri-urban site, Chuabo Dembe, which differed from all other sites in Cluster and Principal Components Analyses. Fishing dominated activities at four of five sites, with the highest preponderance near the estuary mouth. Women played an important role in generating household income, mainly through farming and operating small businesses in peri-urban areas. The education level declined in rural settings. Overexploitation and degradation of natural ecosystems to provide for an increasing urban population around Quelimane threaten estuarine functioning, making deltaic FBF systems vulnerable. Rural development programmes should focus on improving education levels and the efficiency of food production, processing and distribution systems.

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Insulin and glucose regulation at rest and during flight in a Neotropical nectar-feeding bat - David Leonardo Justinico Castro; Renata Maria P. Freitas; Stella Bicalho Silva; Fabiana Cristina Silveira Alves de Melo; Mariaurea M. Sarandy; Esteban Giraldo Ospina; Sirlene Rodrigues Sartori; Reggiani Vilela Gonçalves; Mariella Bontempo Freitas (Mammalian Biology, 2021)

Determination of intestinal absorption of the paralytic shellfish toxin GTX-5 using the Caco-2 human cell model - Elsa T. Rodrigues; Susana F. Nascimento; Cristiana L. Pires; Lia P. Godinho; Catarina Churro; Maria João Moreno; Miguel A. Pardal (Environmental Science and Pollution Research, 2021)

Amikacin for the treatment of carbapenem-resistant Klebsiella pneumoniae infections: clinical efficacy and toxicity - Diógenes Rodrigues; Giulia Soska Baldissera; Douglas Mathos; Aline Sartori; Alexandre P. Zavascki; Maria Helena Rigatto (Brazilian Journal of Microbiology, 2021)

Trophic downgrading decreases species asynchrony and community stability regardless of climate warming - Felipe Rezende; Pablo A. P. Antiqueira; Owen L. Petchey; Luiz Felipe M. Velho; Luzia C. Rodrigues; Gustavo Q. Romero (Ecology Letters, 2021)
Theory and some evidence suggest that biodiversity promotes stability. However, evidence of how trophic interactions and environmental changes modulate this relationship in multitrophic communities is lacking. Given the current scenario of biodiversity loss and climate changes, where top predators are disproportionately more affected, filling these knowledge gaps is crucial. We simulated climate warming and top predator loss in natural microcosms to investigate their direct and indirect effects on temporal stability of microbial communities and the role of underlying stabilising mechanisms. Community stability was insensitive to warming, but indirectly decreased due to top predator loss via increased mesopredator abundance and consequent reduction of species asynchrony and species stability. The magnitude of destabilising effects differed among trophic levels, being disproportionally higher at lower trophic levels (e.g. producers). Our study unravels major patterns and causal mechanisms by which trophic downgrading destabilises large food webs, regardless of climate warming scenarios.

Whiptail lizard lineage delimitation and population expansion as windows into the history of Amazonian open ecosystems - Lidia F. Martins; Erik L. Choueri; Alan F. S. Oliveira; Fabrícius M. C. B. Domingos; Gabriel H. O. Caetano; Vitor H. G. L. Cavalcante; Rafael N. Leite; Antoine Fouquet; Miguel T. Rodrigues; Ana C. Carnaval; Guarino R. Colli; Fernanda P. Werneck (Systematics and Biodiversity, 2021)

Chronic exposure to volcanic gaseous elemental mercury: using wild Mus musculus to unveil its uptake and fate - R. Camarinho; A. Navarro-Sempere; P. V. Garcia; M. García; Y. Segovia; A. S. Rodrigues (Environmental Geochemistry and Health, 2021)

Microencapsulated Lemongrass ( Cymbopogon flexuosus ) Essential Oil Supplementation on Quality and Stability of Silver Catfish Fillets during Frozen Storage - Cristine Rampelotto; Caroline S. Speroni; Lisiane Conte; Dirleise Pianesso; Isadora S. Machado; Renata F. Rodrigues; Natália M. Minuzzi; Taida J. Adorian; Bruna Klein; Roger Wagner; Bernardo Baldisserotto; Leila P. da Silva; et al. (Journal of Aquatic Food Product Technology, 2021)

Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Bruno Lopes da Silva Ferrette; Bruno Mourato; Fábio Hissa Vieira Hazin; Freddy Arocha; Samuel Mackey Williams; Carlos Egberto Rodrigues Junior; Fábio Porto-Foresti; Alberto Ferreira de Amorim; Matheus Marcos Rotundo; Rui Coelho; John P. Hoolihan; Fambaye Ngom Sow; et al. (Hydrobiologia, 2021)

Toxicity Assays of Commercial Chlorpyrifos Under UV/H2O2 and UVC Photolysis Treatments - Suelen Angeli; Eliane Adams; Gabriella P. Masceno; Rúbia M. Lima; Larisa M. Utzig; Fernando Rodrigues-Silva; Liziê D. T. Prola; Adriane M. Freitas; Marcus V. Liz (Water, Air, & Soil Pollution, 2021)

Combining regional to local restoration goals in the Brazilian Atlantic forest - Cassia M.G. Lemos; Pedro R. Andrade; Ricardo R. Rodrigues; Leticia Hissa; Ana P. D. Aguiar (Regional Environmental Change, 2021)
To achieve regional and international large-scale restoration goals with minimum costs, several restoration commitments rely on natural regeneration, a passive and inexpensive strategy. However, natural regeneration potential may vary within the landscape, mainly due to its historical context. In this work, we use spatially explicit restoration scenarios to explore how and where, within a given region, multiple restoration commitments could be combined to achieve cost-effectiveness outcomes. Our goal is to facilitate the elaboration of forest restoration plans at the regional level, taking into consideration the costs for active and passive restoration methods. The approach includes (1) a statistical analysis to estimate the natural regeneration potential for a given area based on alternative sets of biophysical, land cover, and/or socioeconomic factors and (2) the use of a land change allocation model to explore the cost-effectiveness of combining multiple restoration commitments in a given area through alternative scenarios. We test our approach in a strategic region in the Brazilian Atlantic Forest Biome, the Paraiba Valley in São Paulo State. Using the available data for 2011, calibrated for 2015, we build alternative scenarios for allocating natural regeneration until 2025. Our models indicate that the natural regeneration potential of the region is actually very low, and the cost-effectiveness outcomes are similar for all scenarios. We believe our approach can be used to support the regional-level decision-making about the implementation of multiple commitments aiming at the same target area. It can also be combined with other approaches for more refined analysis (e.g., optimization models).

Low doses of ketamine and guanosine abrogate corticosterone-induced anxiety-related behavior, but not disturbances in the hippocampal NLRP3 inflammasome pathway - Anderson Camargo; Ana Paula Dalmagro; Daiane B. Fraga; Julia M. Rosa; Ana Lúcia B. Zeni; Manuella P. Kaster; Ana Lúcia S. Rodrigues (Psychopharmacology, 2021)

Identification of TIA1 mRNA targets during human neuronal development - Loryn P. Byres; Marat Mufteev; Kyoko E. Yuki; Wei Wei; Alina Piekna; Michael D. Wilson; Deivid C. Rodrigues; James Ellis (Molecular Biology Reports, 2021)
Background Neuronal development is a tightly controlled process involving multi-layered regulatory mechanisms. While transcriptional pathways regulating neurodevelopment are well characterized, post-transcriptional programs are still poorly understood. TIA1 is an RNA-binding protein that can regulate splicing, stability, or translation of target mRNAs, and has been shown to play critical roles in stress response and neurodevelopment. However, the identity of mRNAs regulated by TIA1 during neurodevelopment under unstressed conditions is still unknown. Methods and Results To identify the mRNAs targeted by TIA1 during the first stages of human neurodevelopment, we performed RNA immunoprecipitation-sequencing (RIP-seq) on human embryonic stem cells (hESCs) and derived neural progenitor cells (NPCs), and cortical neurons under unstressed conditions. While there was no change in TIA1 protein levels, the number of TIA1 targeted mRNAs decreased from pluripotent cells to neurons. We identified 2400, 845, and 330 TIA1 mRNA targets in hESCs, NPC, and neurons, respectively. The vast majority of mRNA targets in hESC were genes associated with neurodevelopment and included autism spectrum disorder-risk genes that were not bound in neurons. Additionally, we found that most TIA1 mRNA targets have reduced ribosomal engagement levels. Conclusion Our results reveal TIA1 mRNA targets in hESCs and during human neurodevelopment, indicate that translation repression is a key process targeted by TIA1 binding and implicate TIA1 function in neuronal differentiation.

Exhumation of an anatectic complex by channel flow and extrusion tectonics: structural and metamorphic evidence from the Porto–Viseu Metamorphic Belt, Central-Iberian Zone - T. Bento dos Santos; J. F. Rodrigues; P. Castro; B. Cotrim; I. Pereira; J. A. Ferreira; C. Meireles; N. Ferreira; P. Ferreira; A. Ribeiro; F. Guimarães (International Journal of Earth Sciences, 2021)

Impact of growing seasons and pesticides used on the occurrence and severity of the gummy stem blight in melon cultivation in Brazil - Gil Rodrigues dos Santos; P. H. Tschoeke; R. A. Sarmento; E. E. Oliveira; N. Rodrigues-Silva; M. S. Dalcin; K. Haddi; R. S. Silva (European Journal of Plant Pathology, 2021)

Studies in Neotropical Araliaceae. Three new species of Sciodaphyllum P. Browne (Araliaceae) with globose capitate inflorescences from Ecuador and Peru - Carlos Rodrigues-Vaz; Gregory M. Plunkett; Porter P. Lowry II (Brittonia, 2021)

Physiological seasonality in the symbiont and host of the northern star coral, Astrangia poculata - Wolfgang Trumbauer; Sean P. Grace; Lisa J. Rodrigues (Coral Reefs, 2021)

ROS in vivo determination and antioxidant responses in rotifers Brachionus plicatilis fed with commercial yeast Saccharomyces cerevisiae or microalgae Nannochloropsis oculata - Ricardo Vieira Rodrigues; Lucas C. Maltez; Cristiano C. Ferreira; Thiago P. A. P. Oliveira; Luís A. Sampaio; José María Monserrat (Aquaculture International, 2021)

Tidal and Physicochemical Effects on Phytoplankton Community Variability at Tagus Estuary (Portugal) - Rui Cereja; Vanda Brotas; Joana P. C. Cruz; Marta Rodrigues; Ana C. Brito (Frontiers in Marine Science, 2021)
The Tagus Estuary is one of the largest estuaries in Europe and merges large urban and industrial areas. Understanding phytoplankton community variability is key for an appropriate assessment of the estuarine ecological status. The objective of the present study was to assess the importance of the tidal influence over the phytoplankton community and to evaluate its main drivers of variation. Weekly sampling was performed at two stations on the Tagus Estuary with different anthropogenic pressures (Alcântara and Barreiro). The sampling covered periods with different tidal amplitude. Alcântara presented both the lowest and highest concentrations of dissolved inorganic nitrogen (DIN) and orthophosphate concentration (DIP), depending on the tidal height. Such high variability in this sampling station is probably due to its proximity to a sewage treatment station outfall and to the estuary mouth. In the present study, both seasonal and tidal variations influenced the chlorophyll a concentration of which the tidal cycle explained up to 50% of the chlorophyll a variations. Chlorophyll a displayed a seasonal trend with two peaks of phytoplankton biomass between spring and mid-summer. The main drivers of chlorophyll a variation were radiation, water temperature, tidal amplitude, salinity, river discharge, and the inorganic nutrients DIN and DSi. The estuarine phytoplankton community was mainly dominated by Bacillariophyceae, especially at Alcântara. Bacillariophyceae were less important at Barreiro, where communities had a higher representation from other phytoplankton groups, such as Cryptophyceae and Prasinophyceae. The drivers of variability in the community composition were similar to those influencing the total biomass. In conclusion, the spring-neap tidal cycle strongly influenced the phytoplankton community, both in terms of biomass and community composition. Of the several tidal conditions, spring tides were the tidal condition that presented both higher biomass and higher Bacillariophyceae representativity in the community.

The neurotherapeutic role of a selenium-functionalized quinoline in hypothalamic obese rats - Karline C. Rodrigues; Cristiani F. Bortolatto; Ketlyn P. da Motta; Renata L. de Oliveira; Jaini J. Paltian; Roberta Krüger; Silvane S. Roman; Silvana P. Boeira; Diego Alves; Ethel Antunes Wilhelm; Cristiane Luchese (Psychopharmacology, 2021)

Fire and water: the role of grass competition on juvenile tree growth and survival rates in a mesic savanna - P. Laris; L. Yang; F. Dembele; C. M. Rodrigue (Plant Ecology, 2021)

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

Potent Anti-Candida Fraction Isolated from Capsicum chinense Fruits Contains an Antimicrobial Peptide That is Similar to Plant Defensin and is Able to Inhibit the Activity of Different α-Amylase Enzymes - Mariana C. L. Aguieiras; Larissa M. Resende; Thaynã A. M. Souza; Celso S. Nagano; Renata P. Chaves; Gabriel B. Taveira; André O. Carvalho; Rosana Rodrigues; Valdirene M. Gomes; Érica O. Mello (Probiotics and Antimicrobial Proteins, 2021)

Vibrotactile biofeedback devices in Parkinson’s disease: a narrative review - Helena R. Gonçalves; Ana Margarida Rodrigues; Cristina P. Santos (Medical & Biological Engineering & Computing, 2021)

Correction to: A copper(II)-binding triazole derivative with ionophore properties is active against Candida spp. - A. Gaspar-Cordeiro; S. da Silva; M. Aguiar; C. Rodrigues-Pousada; H. Haas; L. M. P. Lima; C. Pimentel (JBIC Journal of Biological Inorganic Chemistry, 2021)

KIR2DL4 genetic diversity in a Brazilian population sample: implications for transcription regulation and protein diversity in samples with different ancestry backgrounds - Emiliana Weiss; Heloisa S. Andrade; Juliana Rodrigues Lara; Andreia S. Souza; Michelle A. Paz; Thálitta H. A. Lima; Iane O. P. Porto; Nayane S. B. Silva; Camila F. Bannwart Castro; Rejane M. T. Grotto; Eduardo A. Donadi; Celso T. Mendes-Junior; et al. (Immunogenetics, 2021)

Peptide fraction from latex of Calotropis procera exhibits antifungal and insecticidal activities - Jackson L. Amaral; Cleverson D. T. Freitas; João P. V. Rodrigues; Ghulam Hussain; Márcio V. Ramos; Pedro F. N. Souza (Arthropod-Plant Interactions, 2021)

Systematics and biogeography of the Boana albopunctata species group (Anura, Hylidae), with the description of two new species from Amazonia - Antoine Fouquet; Pedro Marinho; Alexandre Réjaud; Thiago R. Carvalho; Marcel A. Caminer; Martin Jansen; Raíssa N. Rainha; Miguel T. Rodrigues; Fernanda P. Werneck; Albertina P. Lima; Tomas Hrbek; Ariovaldo A. Giaretta; et al. (Systematics and Biodiversity, 2021)

Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems - Fernando M. Lansac‐Tôha; Luis M. Bini; Jani Heino; Bianca R. Meira; Bianca T. Segovia; Carla S. Pavanelli; Claudia C. Bonecker; Claudia P. de Deus; Evanilde Benedito; Geziele M. Alves; Gislaine I. Manetta; Juliana D. Dias; et al. (Journal of Biogeography, 2021)
Aim Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location Four major Brazilian floodplains, with the largest distance among them of 2,300 Km. Taxon 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.

Feeding behavior of feedlot-finished crossbred bulls fed palm kernel cake - Mateus de M. Lisboa; Robério R. Silva; Fabiano F. da Silva; Maria M. S. Pereira; Gabriel D. Costa; Fabrício B. L. Mendes; Sinvaldo O. de Souza; Marceliana da C. Santos; Laoan B. O. Rodrigues; Henry D. R. Alba; Gleidson G. P. de Carvalho (Tropical Animal Health and Production, 2021)

New phylotypes of foraminifera in subtropical Brazilian coastal waters revealed by environmental DNA metabarcoding - André Rosch Rodrigues; Vivian Helena Pellizari; Cristiano de Salles Almeida; Eduinetty Ceci P. M. de Sousa; Maria Holzmann; Jan Pawlowski (Journal of Sedimentary Environments, 2021)

The CORDEX Flagship Pilot Study in southeastern South America: a comparative study of statistical and dynamical downscaling models in simulating daily extreme precipitation events - M. L. Bettolli; S. A. Solman; R. P. da Rocha; M. Llopart; J. M. Gutierrez; J. Fernández; M. E. Olmo; A. Lavin-Gullon; S. C. Chou; D. Carneiro Rodrigues; E. Coppola; R. Balmaceda Huarte; et al. (Climate Dynamics, 2021)

Physical exercise prevents amyloid β1−40-induced disturbances in NLRP3 inflammasome pathway in the hippocampus of mice - Julia M. Rosa; Anderson Camargo; Ingrid A. V. Wolin; Manuella P. Kaster; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2021)

Administration of branched-chain amino acids alters epigenetic regulatory enzymes in an animal model of Maple Syrup Urine Disease - Emilio L. Streck; Felipe P. Bussular; Leticia B. Wessler; Mariane B. Duarte; Victoria L. Rezende; Matheus S. Rodrigues; Carolina A. Torres; Isabela S. Lemos; Gabriela Candiotto; Fernanda F. Gava; Jade de Oliveira; Samira S. Valvassori (Metabolic Brain Disease, 2021)

Purification of arsenic-contaminated water using iron molybdate filters and monitoring of their genotoxic, mutagenic, and cytotoxic effects through bioassays - Rodrigo C. Hott; Thainá S. Magalhães; Luiz F. O. Maia; Kallel S. F. Santos; Guilherme L. Rodrigues; Luiz C. A. Oliveira; Márcio C. Pereira; Márcia C. S. Faria; Alessandra P. Carli; Caio C. Souza Alves; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2021)

Reliability of evidence‐review methods in restoration ecology - João P. Romanelli; Paula Meli; Rafaela P. Naves; Marcelo C. Alves; Ricardo R. Rodrigues (Conservation Biology, 2021)
In restoration science, evidence reviews play a crucial role in summarizing research findings in practice and policy. However, if unreliable or inappropriate methods are used to review evidence, decisions based on these reviews may not accurately reflect the available evidence base. To assess the current value of restoration reviews, we examined a sample of meta‐analyses and narrative syntheses (n = 91) with the Collaboration for Environmental Evidence Synthesis Assessment Tool (CEESAT), which uses detailed criteria to assesses the method of policy‐relevant evidence synthesis according to elements important for objectivity, transparency, and comprehensiveness. Overall, reviews scored low based on this standard: median score 16 out of 39, modal score 15, and mean 16.6. Meta‐analyses scored higher than narrative syntheses (median 17 vs. 5, respectively), although there were some outlier narrative syntheses that had high scores, suggesting that quantitative synthesis does not solely reflect the reliability of a review. In general, criteria spanning the more fundamental review stages (i.e., searching for studies and including studies) received low scores for both synthesis types. Conversely, criteria comprising the later stages of the review (i.e., critical appraisal, data extraction, and data synthesis) were generally well described in meta‐analyses; thus, these criteria achieved the highest individual CEESAT scores. We argue that restoration ecology is well positioned to advance so‐called evidence‐based restoration, but review authors should elucidate their conceptual understanding of evidence syntheses and recognize that conducting reliable reviews demands the same methodological rigor and reporting standards used in primary research. Given the potential of evidence reviews to inform management, policy, and research, it is of vital importance that the overall methodological reliability of restoration reviews be improved.

Different wavelengths of visible light influence the conidial production and tolerance to ultra-violet radiation of the plant pathogens Colletotrichum acutatum and Fusarium fujikuroi - Tacyana P. C. Costa; Eliane M. Rodrigues; Luciana P. Dias; Breno Pupin; Paulo C. Ferreira; Drauzio E. N. Rangel (European Journal of Plant Pathology, 2021)

Soil loss and sediment yield in a perennial catchment in southwest Piauí, Brazil - Kamylla Gonçalves Oliveira Assis; Yuri Jacques Agra Bezerra da Silva; José Wellington Batista Lopes; João Carlos Medeiros; Marcos Paulo Rodrigues Teixeira; Fernando Braga Rimá; Vijay P. Singh (Environmental Monitoring and Assessment, 2021)

First record on mercury accumulation in mice brain living in active volcanic environments: a cytochemical approach - A. Navarro-Sempere; Y. Segovia; A. S. Rodrigues; P. V. Garcia; R. Camarinho; M. García (Environmental Geochemistry and Health, 2021)

Climate change drives spatial mismatch and threatens the biotic interactions of the Brazil nut - Lilian P. Sales; Lucirene Rodrigues; Rômulo Masiero (Global Ecology and Biogeography, 2021)
Aim Climate change and deforestation will redistribute biodiversity in the next century. Species‐specific differences in the response to these stressors will lead to distribution decoupling of interacting species. However, consequences for ecosystem services are poorly known. Here, we assess the potential effects of future distribution mismatch on a key ecosystem service mediated by seed dispersal and pollination interactions: the sustainable exploitation of Brazil nuts. Location The Amazon. Major taxa studied Woody plants, medium‐sized mammals, and insects. Time period Present day, end of the 21st century. Methods Combining ecological niche models to simulations of tree cover loss and dispersal constraints, we compare the forecasted distribution of the plant to that of its interacting fauna of pollinators and seed dispersers. Results Our projections indicate that climate change itself could have no or even slightly positive effects on the distribution of the Brazil nut tree, expected to increase by up to 6% by the year 2090. However, the pollinators of this tree were forecasted lose nearly 50% of their suitable distribution in the future, leading to an almost 80% reduction in co‐occurrence potential. In addition, local pollinator richness was predicted to diminish by 20%, with likely consequences for pollination redundancy and resilience to subsequent environment changes. Although range contractions were also forecasted for some seed dispersers in the future, the overall patterns of potential co‐occurrence between the Brazil nut tree and seed dispersers, as well as local richness of seed dispersers. were mostly unabated. Main conclusions The forecasted declines in pollinator diversity may reduce ecosystem functional redundancy and threaten the long‐term resilience of the services provided by Brazil nut trees. Such pervasive and indirect effects of climate change, often neglected and unaccounted for in most conservation assessments, may have cascading effects upon into economies and human well‐being worldwide.

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Kalina M. Brauko; Alex Cabral; Natasha V. Costa; Juliana Hayden; Carlos E. P. Dias; Edilene S. Leite; Renan D. Westphal; Carolina M. Mueller; Jason M. Hall-Spencer; Regina R. Rodrigues; Leonardo R. Rörig; Paulo R. Pagliosa; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temporal trends. Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, lasting for 9 days and coinciding with our research cruise. During this period, seawater temperatures reached 29.8°C and anoxia was detected for the first time in the bay. A decrease in macrobenthic and phytoplankton community richness correlated with decreases in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with MHWs to degrade coastal waters. Mitigation strategies are needed to minimize the impact of MHWs, including improved sewage treatment, restoration and conservation of wetlands and the use of nature-based technologies to promote coastal ecosystem recovery.

Violacein antimicrobial activity on Staphylococcus epidermidis biofilm - H. V. Dodou; A. H. M. Batista; S. C. Medeiros; G. W. P. Sales; M. L. Rodrigues; P. I. O. Pereira; P. C. N. Nogueira; E. R. Silveira; T. B. Grangeiro; N. A. P. Nogueira (Natural Product Research, 2020)

Combined Soil and Foliar Nitrogen Fertilization Effects on Rainfed Almond Tree Performance - Maria C. Morais; Alfredo Aires; David Barreales; M. Ângelo Rodrigues; António C. Ribeiro; Berta Gonçalves; Ana P. Silva (Journal of Soil Science and Plant Nutrition, 2020)

A copper(II)-binding triazole derivative with ionophore properties is active against Candida spp. - A. Gaspar-Cordeiro; S. da Silva; M. Aguiar; C. Rodrigues-Pousada; H. Haas; L. M. P. Lima; C. Pimentel (JBIC Journal of Biological Inorganic Chemistry, 2020)

Recent advances on anaerobic digestion of swine wastewater - G. Lourinho; L. F. T. G. Rodrigues; P. S. D. Brito (International Journal of Environmental Science and Technology, 2020)

Mitoxantrone impairs proteasome activity and prompts early energetic and proteomic changes in HL-1 cardiomyocytes at clinically relevant concentrations - Vera Marisa Costa; João Paulo Capela; Joana R. Sousa; Rute P. Eleutério; Patrícia R. S. Rodrigues; José Luís Dores-Sousa; Rui A. Carvalho; Maria Lourdes Bastos; José Alberto Duarte; Fernando Remião; M. Gabriela Almeida; Kurt J. Varner; et al. (Archives of Toxicology, 2020)

Sanitary quality improvement of fish produced in the northern Benin cotton basin water reservoirs by cage culture and fish transfer in agricultural contaminant-free water: human health implications - Rodrigue O. E. Pèlèbè; Ibrahim Imorou Toko; Issa N. Ouattara; Ulbad P. Tougan; Eloi Y. Attakpa; Jean Fall; Elie Montchowui (Tropical Animal Health and Production, 2020)

Inoculation with the endophytic bacterium Herbaspirillum seropedicae promotes growth, nutrient uptake and photosynthetic efficiency in rice - Alessandro C. Ramos; Juliana Melo; Sávio B. de Souza; Amanda A. Bertolazi; Renderson A. Silva; Weverton P. Rodrigues; Eliemar Campostrini; Fábio L. Olivares; Frederico J. Eutrópio; Cristina Cruz; Teresa Dias (Planta, 2020)

Historical biogeography identifies a possible role of Miocene wetlands in the diversification of the Amazonian rocket frogs (Aromobatidae: Allobates ) - Alexandre Réjaud; Miguel T. Rodrigues; Andrew J. Crawford; Santiago Castroviejo‐Fisher; Andrés F. Jaramillo; Juan C. Chaparro; Frank Glaw; Giussepe Gagliardi‐Urrutia; Jiří Moravec; Ignacio J. De la Riva; Pedro Perez; Albertina P. Lima; et al. (Journal of Biogeography, 2020)
Aim We investigate the spatiotemporal context of the diversification of Allobates , a widespread genus of Amazonian frogs with high species diversity particularly in western Amazonia. We tested if that diversity originated in situ or through repeated dispersals from other Amazonian areas and if this diversification took place during or after the Pebas system, a vast lacustrine system occupying most western Amazonia between 23 and 10 million years ago (Mya). Location Amazonia. Taxon Allobates (Anura: Aromobatidae). Methods We gathered a spatially and taxonomically extensive sampling of mitochondrial DNA sequences from 932 Allobates specimens to delimit Operational Taxonomic Units (OTUs). Complete mitogenomes of these OTUs were assembled to reconstruct a time‐calibrated phylogeny used to infer the historical and spatial origin of the Amazonian Allobates lineages. Results Phylogenetic analyses and ancestral area reconstruction suggested that most of the western Amazonian lineages resulted from in situ diversification and that these events occurred between the inferred origin of the genus (25 Mya) and 10 Mya, with a possible peak between 14 and 10 Mya. Dispersal among areas mostly occurred from western Amazonia towards the Brazilian and the Guiana Shields. Closely related Allobates OTUs display an allopatric pattern of distribution, matching interfluves delimited by modern Amazonian rivers. Main Conclusions In western Amazonia, diversification of Allobates appears to have been simultaneous with the last stages of the Pebas system (14–10 Mya). Subsequently (within the last 10 Mya), modern Amazonian river courses shaped the distribution pattern of Allobates species and possibly promoted allopatric speciation.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Stimulation of isoprene emissions and electron transport rates as key mechanisms of thermal tolerance in the tropical species Vismia guianensis - Tayana B. Rodrigues; Christopher R. Baker; Anthony P. Walker; Nate McDowell; Alistair Rogers; Niro Higuchi; Jeffrey Q. Chambers; Kolby J. Jardine (Global Change Biology, 2020)
Tropical forests absorb large amounts of atmospheric CO 2 through photosynthesis, but high surface temperatures suppress this absorption while promoting isoprene emissions. While mechanistic isoprene emission models predict a tight coupling to photosynthetic electron transport (ETR) as a function of temperature, direct field observations of this phenomenon are lacking in the tropics and are necessary to assess the impact of a warming climate on global isoprene emissions. Here we demonstrate that in the early successional species Vismia guianensis in the central Amazon, ETR rates increased with temperature in concert with isoprene emissions, even as stomatal conductance ( g s ) and net photosynthetic carbon fixation ( P n ) declined. We observed the highest temperatures of continually increasing isoprene emissions yet reported (50°C). While P n showed an optimum value of 32.6 ± 0.4°C, isoprene emissions, ETR, and the oxidation state of PSII reaction centers (q L ) increased with leaf temperature with strong linear correlations for ETR (ƿ = 0.98) and q L (ƿ = 0.99) with leaf isoprene emissions. In contrast, other photoprotective mechanisms, such as non‐photochemical quenching, were not activated at elevated temperatures. Inhibition of isoprenoid biosynthesis repressed P n at high temperatures through a mechanism that was independent of stomatal closure. While extreme warming will decrease g s and P n in tropical species, our observations support a thermal tolerance mechanism where the maintenance of high photosynthetic capacity under extreme warming is assisted by the simultaneous stimulation of ETR and metabolic pathways that consume the direct products of ETR including photorespiration and the biosynthesis of thermoprotective isoprenoids. Our results confirm that models which link isoprene emissions to the rate of ETR hold true in tropical species and provide necessary “ground‐truthing” for simulations of the large predicted increases in tropical isoprene emissions with climate warming.

Three new species of Pseuderanthemum (Acanthaceae) from the Neotropics - Marianna Conceição Rodrigues; Vinicius Castro Souza; Cassio A. P. Toledo (Kew Bulletin, 2020)

Melaleuca leucadendra Essential Oil Promotes Loss of Cell Membrane and Wall Integrity and Inhibits Bacterial Growth: An In Silico and In Vitro Approach - Jessica P. Bautista-Silva; Janaína B. Seibert; Tatiane R. Amparo; Ivanildes V. Rodrigues; Luiz Fernando M. Teixeira; Gustavo Henrique B. Souza; Orlando D. H. dos Santos (Current Microbiology, 2020)

Antifungal compounds with anticancer potential from Trichoderma sp. P8BDA1F1, an endophytic fungus from Begonia venosa - Diana F. Grigoletto; Daniela B. B. Trivella; André G. Tempone; André Rodrigues; Ana Maria L. Correia; Simone P. Lira (Brazilian Journal of Microbiology, 2020)

Ion Pair Strategy in Solid Lipid Nanoparticles: a Targeted Approach to Improve Epidermal Targeting with Controlled Adapalene Release, Resulting Reduced Skin Irritation - Linna B. O. Rodrigues; Flávia A. Lima; Camila P. B. Alves; Elisângela Martins-Santos; Marta M. G. Aguiar; Cleida A. Oliveira; Rodrigo L. Oréfice; Lucas A. M. Ferreira; Gisele A. C. Goulart (Pharmaceutical Research, 2020)

Large‐scale DNA‐based survey of frogs in Amazonia suggests a vast underestimation of species richness and endemism - Jean‐Pierre Vacher; Jérôme Chave; Francesco Gentile Ficetola; Guilhem Sommeria‐Klein; Shengli Tao; Christophe Thébaud; Michel Blanc; Agustín Camacho; José Cassimiro; Timothy J. Colston; Maël Dewynter; Raffael Ernst; et al. (Journal of Biogeography, 2020)
Aim Mapping Amazonian biodiversity accurately is a major challenge for integrated conservation strategies and to study its origins. However, species boundaries and their respective distribution are notoriously inaccurate in this region. Here, we generated a georeferenced database of short mtDNA sequences from Amazonian frogs, revised the species richness and the delimitation of bioregions of the Eastern Guiana Shield and estimated endemism within these bioregions. Location Amazonia, with a focus on the Eastern Guiana Shield. Taxon studied Amphibia: Anura. Methods We used an extensive DNA‐based sampling of anuran amphibians of Amazonia using next‐generation sequencing to delimit Operational Taxonomic Units (OTU) and their distribution. We analysed this database to infer bioregions using Latent Dirichlet Allocation modelling. We then compared endemism within these bioregions based on our results and the current IUCN database, and inferred environmental variables that contributed the most to the biogeographic pattern. Results The recognized anuran species richness within the focal area increased from 440 species currently listed by the IUCN Red List to as much as 876 OTUs with our dataset. We recovered eight bioregions, among which three lie within the Eastern Guiana Shield. We estimated that up to 82% of the OTUs found in this area are endemic, a figure three times higher than the previous estimate (28%). Environmental features related to seasonal precipitations are identified as playing an important role in shaping Amazonian amphibian bioregions. Main conclusions Our results have major implications for defining future conservation priorities of this vast area given that endemism in most Amazonian bioregions is vastly underestimated, and might therefore hide a large portion of threatened species. Moreover, these findings raise concern about meta‐analyses based on public databases within Amazonia dealing with poorly known groups.

Entomopathogenic Viruses in the Neotropics: Current Status and Recently Discovered Species - D R Sosa-Gómez; F S Morgado; R F T Corrêa; L A Silva; D M P Ardisson-Araújo; B M P Rodrigues; E E Oliveira; R W S Aguiar; B M Ribeiro (Neotropical Entomology, 2020)

Cytotoxic Effect of Prodigiosin, Natural Red Pigment, Isolated from Serratia marcescens UFPEDA 398 - J. C. L. Lapenda; V. P. Alves; M. L. Adam; M. D. Rodrigues; S. C. Nascimento (Indian Journal of Microbiology, 2020)

Correction to: In vitro mechanistic studies on α-amanitin and its putative antidotes - Daniela Ferreira Rodrigues; Ricardo Pires das Neves; Alexandra T. P. Carvalho; Maria Lourdes Bastos; Vera M. Costa; Félix Carvalho (Archives of Toxicology, 2020)

In vitro mechanistic studies on α-amanitin and its putative antidotes - Daniela Ferreira Rodrigues; Ricardo Pires das Neves; Alexandra T. P. Carvalho; Maria Lourdes Bastos; Vera M. Costa; Félix Carvalho (Archives of Toxicology, 2020)

Assessing ecological function in the context of species recovery - H. Resit Akçakaya; Ana S. L. Rodrigues; David A. Keith; E. J. Milner‐Gulland; Eric W. Sanderson; Simon Hedges; David P. Mallon; Molly K. Grace; Barney Long; Erik Meijaard; P. J. Stephenson (Conservation Biology, 2020)
Species interactions matter to conservation. Setting an ambitious recovery target for a species requires considering the size, density, and demographic structure of its populations such that they fulfill the interactions, roles, and functions of the species in the ecosystems in which they are embedded. A recently proposed framework for an International Union for Conservation of Nature Green List of Species formalizes this requirement by defining a fully recovered species in terms of representation, viability, and functionality. Defining and quantifying ecological function from the viewpoint of species recovery is challenging in concept and application, but also an opportunity to insert ecological theory into conservation practice. We propose 2 complementary approaches to assessing a species’ ecological functions: confirmation (listing interactions of the species, identifying ecological processes and other species involved in these interactions, and quantifying the extent to which the species contributes to the identified ecological process) and elimination (inferring functionality by ruling out symptoms of reduced functionality, analogous to the red‐list approach that focuses on symptoms of reduced viability). Despite the challenges, incorporation of functionality into species recovery planning is possible in most cases and it is essential to a conservation vision that goes beyond preventing extinctions and aims to restore a species to levels beyond what is required for its viability. This vision focuses on conservation and recovery at the species level and sees species as embedded in ecosystems, influencing and being influenced by the processes in those ecosystems. Thus, it connects and integrates conservation at the species and ecosystem levels.

Identification of genes from the general phenylpropanoid and monolignol-specific metabolism in two sugarcane lignin-contrasting genotypes - Douglas Jardim-Messeder; Tatiane da Franca Silva; Jose Pedro Fonseca; José Nicomedes Junior; Lucia Barzilai; Thais Felix-Cordeiro; Joyce Carvalho Pereira; Clara Rodrigues-Ferreira; Isabela Bastos; Tereza Cristina da Silva; Vinicius de Abreu Waldow; Daniela Cassol; et al. (Molecular Genetics and Genomics, 2020)

Human Losses and Damage Expected in Future Earthquakes on Faial Island–Azores - J. Fontiela; P. Rosset; M. Wyss; M. Bezzeghoud; J. Borges; F. Cota Rodrigues (Pure and Applied Geophysics, 2020)

Evidence of strong population bottleneck in genetics of endangered Brazilian Merganser (Mergus octosetaceus) - T. A. Maia; D. P. Campos; L. R. Silva; L. V. Lins; F. Ribeiro; F. Sebaio; F. R. Rodrigues; G. P. M. Dantas (Journal of Ornithology, 2020)

Phylogenetic analysis revealed that Salmonella Typhimurium ST313 isolated from humans and food in Brazil presented a high genomic similarity - Amanda Ap. Seribelli; Júlia C. Gonzales; Fernanda de Almeida; Leandro Benevides; Marta I. Cazentini Medeiros; Dália dos Prazeres Rodrigues; Siomar de C. Soares; Marc W. Allard; Juliana P. Falcão (Brazilian Journal of Microbiology, 2020)

Studies in Neotropical Araliaceae. I. Resurrection of the genus Sciodaphyllum P. Browne to accommodate most New World species previously included in Schefflera J. R. Forst. & G. Forst. - Porter P. Lowry II; Gregory M. Plunkett; M. Marcela Mora; Asunción Cano; Pedro Fiaschi; David G. Frodin; Roy E. Gereau; Álvaro Idárraga-Piedrahíta; Jáider Jiménez-Montoya; J. Moisés F. Mendoza; David A. Neill; Orlando Rivera-Diaz; et al. (Brittonia, 2020)

A novel cellular automata approach: seed input/output of the alien species Leucaena leucocephala in the soil and the effects of climate changes - Andréa Rodrigues Marques; Larissa Lopes Lima; Queila Souza Garcia; Allbens P. F. Atman (Plant Ecology, 2020)

Natural Vs Managed Habitat: Effect Over the Seed-Predator Pachymerus nucleorum and Its Natural Enemies - J O S Silva; M L E Costa; B S Paixão; J D B Macêdo; P M S Rodrigues; E M F Lins-Neto (Neotropical Entomology, 2020)

Molecular characterization of a germplasm bank of Platonia insignis Mart.: a fruit tree - D. N. Pena; E. F. Moura; S. M. Rodrigues; M. S. P. Oliveira; J. P. Sanches; M. F. Moura (Genetic Resources and Crop Evolution, 2020)

A risk-based multi-level stress test methodology: application to six critical non-nuclear infrastructures in Europe - Sotirios A. Argyroudis; Stavroula Fotopoulou; Stella Karafagka; Kyriazis Pitilakis; Jacopo Selva; Ernesto Salzano; Anna Basco; Helen Crowley; Daniela Rodrigues; José P. Matos; Anton J. Schleiss; Wim Courage; et al. (Natural Hazards, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of ammoniated pearl millet silage on intake, feeding behavior, and blood metabolites in feedlot lambs - Thomaz C. G. de C. Rodrigues; Poliane M. Freitas; Edson M. Santos; Gherman G. L. de Araújo; Aureliano J. V. Pires; Maria C. C. Ayres; Lorendane M. de Carvalho; Jocely G. Souza; Gleidson G. P. de Carvalho (Tropical Animal Health and Production, 2019)

Synthesis, structural characterization, and cytotoxic evaluation of chalcone derivatives - Paulo N. Bandeira; Telma L. G. Lemos; Hélcio S. Santos; Mylena C. S. de Carvalho; Daniel P. Pinheiro; Manoel O. de Moraes Filho; Cláudia Pessoa; Francisco W. A. Barros-Nepomuceno; Tigressa H. S. Rodrigues; Paulo R. V. Ribeiro; Herbert S. Magalhães; Alexandre M. R. Teixeira (Medicinal Chemistry Research, 2019)

Testing main Amazonian rivers as barriers across time and space within widespread taxa - Renata M. Pirani; Fernanda P. Werneck; Andréa T. Thomaz; Mariah L. Kenney; Marcelo J. Sturaro; Teresa C. S. Ávila‐Pires; Pedro L. V. Peloso; Miguel T. Rodrigues; L. Lacey Knowles (Journal of Biogeography, 2019)
Aim Present Amazonian diversity patterns can result from many different mechanisms and, consequently, the factors contributing to divergence across regions and/or taxa may differ. Nevertheless, the river‐barrier hypothesis is still widely invoked as a causal process in divergence of Amazonian species. Here we use model‐based phylogeographic analyses to test the extent to which major Amazonian rivers act similarly as barriers across time and space in two broadly distributed Amazonian taxa. Local Amazon rain forest. Taxon The lizard Gonatodes humeralis (Sphaerodactylidae) and the tree frog Dendropsophus leucophyllatus (Hylidae). Methods We obtained RADseq data for samples distributed across main river barriers, representing main Areas of Endemism previously proposed for the region. We conduct model‐based phylogeographic and genetic differentiation analyses across each population pair. Results Measures of genetic differentiation (based on F ST calculated from genomic data) show that all rivers are associated with significant genetic differentiation. Parameters estimated under investigated divergence models showed that divergence times for populations separated by each of the 11 bordering rivers were all fairly recent. The degree of differentiation consistently varied between taxa and among rivers, which is not an artifact of any corresponding difference in the genetic diversities of the respective taxa, or to amounts of migration based on analyses of the site‐frequency spectrum. Main conclusions Taken together, our results support a dispersal (rather than vicariance) history, without strong evidence of congruence between these species and rivers. However, once a species crossed a river, populations separated by each and every river have remained isolated—in this sense, rivers act similarly as barriers to any further gene flow. This result suggests differing degrees of persistence and gives rise to the seeming contradiction that the divergence process indeed varies across time, space and species, even though major Amazonian rivers have acted as secondary barriers to gene flow in the focal taxa.

(Cyto)genomic and epigenetic characterization of BICR 10 cell line and three new established primary human head and neck squamous cell carcinoma cultures - Ilda P. Ribeiro; Joana M. Rodrigues; Alexandra Mascarenhas; Vanessa Marques; Francisco Caramelo; Maria J. Julião; Thomas Liehr; Joana B. Melo; Isabel M. Carreira (Genes & Genomics, 2019)

Defining the indigenous ranges of species to account for geographic and taxonomic variation in the history of human impacts: reply to Sanderson 2019 - P. J. Stephenson; Molly K. Grace; H. Resit Akçakaya; Ana S. L. Rodrigues; Barney Long; David P. Mallon; Erik Meijaard; Jon Paul Rodriguez; Richard P. Young; Thomas M. Brooks; Craig Hilton‐Taylor (Conservation Biology, 2019)

Near-future changes in storm surges along the Atlantic Iberian coast - André B. Fortunato; Edmund P. Meredith; Marta Rodrigues; Paula Freire; Hendrik Feldmann (Natural Hazards, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Skeletal muscle miR-34a/SIRT1:AMPK axis is activated in experimental and human non-alcoholic steatohepatitis - André L. Simão; Marta B. Afonso; Pedro M. Rodrigues; Margarida Gama-Carvalho; Mariana V. Machado; Helena Cortez-Pinto; Cecília M. P. Rodrigues; Rui E. Castro (Journal of Molecular Medicine, 2019)

Generation and validation of genetic markers for the selection of carioca dry bean genotypes with the slow-darkening seed coat trait - Renata C. Alvares; Robert Stonehouse; Thiago L. P. O. Souza; Patrícia G. S. Melo; Phillip N. Miklas; Kirstin E. Bett; Leonardo C. Melo; Luana A. Rodrigues; Lorena L. Souza; Helton S. Pereira (Euphytica, 2019)

Occurrence and Environmental Distribution of 5 UV Filters During the Summer Season in Different Water Bodies - S. K. Fagervold; A. S. Rodrigues; C. Rohée; R. Roe; M. Bourrain; D. Stien; P. Lebaron (Water, Air, & Soil Pollution, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Amyloid β Peptide Compromises Neural Stem Cell Fate by Irreversibly Disturbing Mitochondrial Oxidative State and Blocking Mitochondrial Biogenesis and Dynamics - Maria Filipe Ribeiro; Tânia Genebra; Ana Cristina Rego; Cecília M. P. Rodrigues; Susana Solá (Molecular Neurobiology, 2019)

Evaluation of the effects of extracts of Maytenus imbricata (Celastraceae) on the treatment of inflammatory and metabolic dysfunction induced by high-refined carbohydrate diet - C. C. Veloso; M. C. Oliveira; V. G. Rodrigues; C. C. Oliveira; L. P. Duarte; M. M. Teixeira; A. V. M. Ferreira; A. C. Perez (Inflammopharmacology, 2019)

Phylogeography of eagle rays of the genus Aetobatus: Aetobatus narinari is restricted to the continental western Atlantic Ocean - João Bráullio L. Sales; Cintia Negrão de Oliveira; Wagner César Rosa dos Santos; Matheus Marcos Rotundo; Yrlene Ferreira; Jonathan Ready; Iracilda Sampaio; Claudio Oliveira; Vanessa P. Cruz; Raul E. Lara-Mendoza; Luis Fernando da Silva Rodrigues-Filho (Hydrobiologia, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Progress on the phylogeny of the Omphalotaceae: Gymnopus s. str., Marasmiellus s. str., Paragymnopus gen. nov. and Pusillomyces gen. nov. - Jadson J. S. Oliveira; Ruby Vargas-Isla; Tiara S. Cabral; Doriane P. Rodrigues; Noemia K. Ishikawa (Mycological Progress, 2019)

Secretomic analysis of Beauveria bassiana related to cattle tick, Rhipicephalus microplus, infection - Lucélia Santi; Caio J. B. Coutinho-Rodrigues; Markus Berger; Lisete A. S. Klein; Eduardo M. De Souza; Rafael L. Rosa; Jorge A. Guimarães; John R. Yates; Wendell M. S. Perinotto; Vânia R. E. P. Bittencourt; Walter O. Beys-da-Silva (Folia Microbiologica, 2019)

Geostatistical stationary space-time covariance functions modeling of Yellow Sigatoka progress in banana crop - J. D. P. Rodrigues; M. C. Alves; A. S. Freitas; E. A. Pozza; M. S. Oliveira; H. J. P. Alves (Australasian Plant Pathology, 2019)

Biogeographical history constrains climatic niche diversification without adaptive forces driving evolution - Marco Túlio P. Coelho; João Fabrício M. Rodrigues; José Alexandre F. Diniz‐Filho; Thiago F. Rangel (Journal of Biogeography, 2019)
Aim To evaluate the effect of biogeographical history on climatic niche diversification. Location Simulated clades evolving in South America. Methods We modelled species evolution under neutral community dynamics and purposely assumed that climatic niche is an emergent property of species. This assumption allows us to better understand whether phylogenetic niche conservatism could be observed when climatic niche is only constrained by biogeographical processes of dispersal and speciation. We varied speciation and dispersal probability, calculating phylogenetic signal of niche overlap and distance between niche centroids for each emergent artificial biota. We then compared the phylogenetic signal of our model with the expectation of climatic niche evolution under Brownian motion (BM). Results We found that phylogenetic signal of climatic niche in the spatially explicit neutral model is usually higher than expected by chance, but lower than expected by BM evolution. Because simulated climatic niches have lower phylogenetic signal than expected by BM evolution, standard ecological and evolutionary interpretation would suggest that climatic niche evolved with little variation over time caused by strong evolutionary constraints. However, our model assumes that climatic niche does not evolve by adaptive forces and is only a consequence of stochastic dispersal and speciation over space and time. Main conclusions Our study reinforces the strong imprints of biogeographical processes on climatic niche evolution, even when no adaptive forces are driving niche diversification. Therefore, although testing phylogenetic signal is the most common approach in studies evaluating phylogenetic patterns in climatic niche conservatism, our results reinforce previous claims that these patterns alone are not capable of distinguishing the possible effect of space in the retention of climatic niche. Biogeographical processes alone can leave imprints in patterns of climatic niche overlap between related species. A careful evaluation of macroevolutionary models underlying phylogenetic patterns of niche variation among species is important to avoid pitfalls related to interpretation of mechanisms of niche diversification.

Ochratoxin A in the Portuguese Wine Market, Occurrence and Risk Assessment - Liliana J.G. Silva; Ana P. Rodrigues; André M.P.T. Pereira; Celeste M. Lino; Angelina Pena (Food Additives & Contaminants Part B-Surveillance, 2019)

Control of Non-migrating Bar Morphodynamics on Survival of Populus nigra Seedlings during Floods - C. L. Wintenberger; S. Rodrigues; S. Greulich; J. G. Bréhéret; P. Jugé; M. Tal; A. Dubois; M. Villar (Wetlands, 2019)

Levels of 25-hydroxyvitamin D3, biochemical parameters and symptoms of depression and anxiety in healthy individuals - Gleicilaine A. S. Casseb; Gabriela Ambrósio; Ana Lúcia S. Rodrigues; Manuella P. Kaster (Metabolic Brain Disease, 2019)

Multiple feedings enhance the growth performance and feed efficiency of juvenile Litopenaeus vannamei when fed a low-fish meal amino acid-supplemented diet - Alberto J. P. Nunes; Hassan Sabry-Neto; Francisco Hélio Pires da Silva; Adhemar Rodrigues de Oliveira-Neto; Karthik Masagounder (Aquaculture International, 2019)

Chemical characterisation of the constituents of Eugenia protenta McVaugh and leishmanicidal activity of dimethylxanthoxylin - Flávio N. Sarges; Márcia M. Cascaes; Lienne S. Moraes; Giselle M. S. P. Guilhon; Edilene O. Silva; Maria das Graças B. Zoghbi; Eloisa H. A. Andrade; Ana Paula D. Rodrigues; Brenda F. Costa; Rayssa N. M. Figueiredo (Natural Product Research, 2019)

Allochthonous versus autochthonous organic matter sustaining macroconsumers in a subtropical sandy beach revealed by stable isotopes - A. M. Garcia; M. C. L. M. Oliveira; C. Odebrecht; J. L. A. Colling; J. P. Vieira; F. L. Rodrigues; R. F. Bastos (Marine Biology Research, 2019)

Correction to: Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. G. Coelho; G. V. Tolesano-Pascoli; V. S. Rodrigues; M. P. J. Szabó; V. N. Ramos (Tropical Animal Health and Production, 2019)

Insights for the Angra do Heroísmo hydrothermal reservoir conceptual model - Antonio P. N. Trota; Francisco Cota Rodrigues; José Gabriel do Álamo de Meneses (Sustainable Water Resources Management, 2019)

Glyphosate detection: methods, needs and challenges - A. L. Valle; F. C. C. Mello; R. P. Alves-Balvedi; L. P. Rodrigues; L. R. Goulart (Environmental Chemistry Letters, 2019)

Eucalyptus rust climatic risk as affected by topography and ENSO phenomenon - R. S. Nóia Júnior; F. Schwerz; J. L. Safanelli; J. C. Rodrigues; P. C. Sentelhas (Australasian Plant Pathology, 2019)

Biofilm Formation by Avian Pathogenic Escherichia coli is Not Related to In Vivo Pathogenicity - Suelle V. Rodrigues; Vanessa Laviniki; Karen A. Borges; Thales Q. Furian; Hamilton L. S. Moraes; Vladimir P. Nascimento; Carlos T. P. Salle (Current Microbiology, 2019)

Crispoic acid, a new compound from Laelia marginata (Orchidaceae), and biological evaluations against parasites, human cancer cell lines and Zika virus - Andrezza C. Belloto; Gredson K. Souza; Paula C. Perin; Ivania T. A. Schuquel; Silvana M. O. Santin; Lucas U. R. Chiavelli; Francielle P. Garcia; Vanessa Kaplum; Jean H. S. Rodrigues; Débora B. Scariot; Rodrigo Delvecchio; Erik Machado-Ferreira; et al. (Natural Product Research, 2018)

Lagged Population Growth in a Termite Host Colony: Cause or Consequence of Inquilinism? - V B Rodrigues; D A Costa; P F Cristaldo; O DeSouza (Neotropical Entomology, 2018)

Computing derivative information of sequentially coupled subsurface models - Rafael J. de Moraes; José R. P. Rodrigues; Hadi Hajibeygi; Jan Dirk Jansen (Computational Geosciences, 2018)

Brachyuran crab (Crustacea, Decapoda) assemblage associated with Sargassum cymosum in southeastern Brazil - Samara de P. Barros-Alves; Douglas Fernandes Rodrigues Alves; Valter José Cobo (Marine Biodiversity, 2018)

Current advances in gibberellic acid (GA3) production, patented technologies and potential applications - Marcela C. Camara; Luciana P. S. Vandenberghe; Cristine Rodrigues; Juliana de Oliveira; Craig Faulds; Emmanuel Bertrand; Carlos R. Soccol (Planta, 2018)

Phosphites attenuate Sclerotinia sclerotiorum-induced physiological impairments in common bean - I. R. F. Fagundes-Nacarath; D. Debona; V. V. Brás; P. R. Silveira; F. A. Rodrigues (Acta Physiologiae Plantarum, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Morphometric differences between two exotic invasive freshwater caridean species (genus Macrobrachium ) - Thiago Elias da Silva; Douglas Fernandes Rodrigues Alves; Samara de P. Barros-Alves; Ariádine Cristine Almeida; Fabiano Gazzi Taddei; Adilson Fransozo (Invertebrate Reproduction & Development, 2018)

A facile method to prepare translucent anatase thin films in monolithic structures for gas stream purification - Caio Rodrigues-Silva; Ricardo A. R. Monteiro; Márcia Dezotti; Adrián M. T. Silva; Eugénia Pinto; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2018)

Histopathological Evaluation of Combined Impacts of the Synthetic Progestin Levonorgestrel and Temperature on the Female Zebrafish Maturation Using a Semi-quantitative Grading Analysis—Is it Enough? - P. G. Cardoso; D. Rodrigues; T. V. Madureira; M. J. Rocha; E. Rocha (Bulletin of Environmental Contamination and Toxicology, 2018)

In Vivo Determination of Moisturizers Efficacy on Human Skin Hydration by Confocal Raman Spectroscopy - Vamshi Krishna Tippavajhala; Taciana D. Magrini; Daniele C. Matsuo; Michely G. P. Silva; Priscila P. Favero; Leonardo Rodrigues De Paula; Airton Abrahão Martin (AAPS PharmSciTech, 2018)

Front Cover - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)

Functional diversity mediates macroecological variation in plant–hummingbird interaction networks - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)
Aim Species interaction networks are known to vary in structure over large spatial scales. We investigated the hypothesis that environmental factors affect interaction network structure by influencing the functional diversity of ecological communities. Notably, we expect more functionally diverse communities to form interaction networks with a higher degree of niche partitioning. Location: Americas. Time period: Current. Major taxa studied: Hummingbirds and their nectar plants. Methods We used a large dataset comprising 74 quantitative plant–hummingbird interaction networks distributed across the Americas, along with morphological trait data for 158 hummingbird species. First, we used a model selection approach to evaluate associations between the environment (climate, topography and insularity), species richness and hummingbird functional diversity as predictors of network structure (niche partitioning, i.e., complementary specialization and modularity). Second, we used structural equation models (SEMs) to ask whether environmental predictors and species richness affect network structure directly and/or indirectly through their influence on hummingbird functional diversity. For a subset of 28 networks, we additionally evaluated whether plant functional diversity was associated with hummingbird functional diversity and network structure. Results Precipitation, insularity and plant richness, together with hummingbird functional diversity (specifically, functional dispersion), were consistently strong predictors of niche partitioning in plant–hummingbird networks. Moreover, SEMs showed that environmental predictors and plant richness affected network structure both directly and indirectly through their effects on hummingbird functional diversity. Plant functional diversity, however, was unrelated to hummingbird functional diversity and network structure. Main conclusions: We reveal the importance of hummingbird functional diversity for niche partitioning in plant–hummingbird interaction networks. The lack of support for similar effects for plant functional diversity potentially indicates that consumer functional diversity might be more important for structuring interaction networks than resource functional diversity. Changes in pollinator functional diversity are therefore likely to alter the structure of interaction networks and associated ecosystem functions.

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Targeting the mitochondrial VDAC in hepatocellular carcinoma using a polyclonal antibody-conjugated to a nitrosyl ruthenium complex - Loyanne C. B. Ramos; Fernando P. Rodrigues; Juliana C. Biazzotto; Sergio de Paula Machado; Leonardo D. Slep; Michael R. Hamblin; Roberto S. da Silva (JBIC Journal of Biological Inorganic Chemistry, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Transcriptome analysis provides insights into the delayed sticky disease symptoms in Carica papaya - Johana Madroñero; Silas P. Rodrigues; Tathiana F. S. Antunes; Paolla M. V. Abreu; José A. Ventura; A. Alberto R. Fernandes; Patricia Machado Bueno Fernandes (Plant Cell Reports, 2018)

Diversification with gene flow and niche divergence in a lizard species along the South American “diagonal of open formations” - Emanuel M. Fonseca; Marcelo Gehara; Fernanda P. Werneck; Flávia M. Lanna; Guarino R. Colli; Jack W. Sites; Miguel T. Rodrigues; Adrian A. Garda (Journal of Biogeography, 2018)
Aim To assess the effects of historical events on the tempo and mode of diversification of the lizard Polychrus acutirostris along the South American diagonal of open formations ( DOF ). Location Caatinga and Cerrado biomes in Brazil. Methods We sequenced fragments of one mt DNA and three nu DNA genes of 68 individuals from 33 localities. We used population assignment methods to access genetic structure and estimate lineage boundaries. Next, we estimated lineage relationships, intraspecific diversity, environmental niche similarity and demographic history. Finally, we tested 12 diversification scenarios using an approximate Bayesian computation ( ABC ) approach. Results We recovered three non‐overlapping, geographically structured lineages corresponding to Caatinga, north‐east Cerrado and south‐west Cerrado, with the major divergence event dating to the Late Neogene. We also recovered a complex scenario of divergence associated with gene flow and niche divergence. Main conclusions We show a complex history of diversification along the South American DOF . Our findings support the role of environmental features as the likely drivers of P. acutirostris intraspecific diversification during the Late Neogene.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Diversity of endophytic fungi in Eucalyptus microcorys assessed by complementary isolation methods - Lorena T. Lacerda; Luís F. P. Gusmão; Andre Rodrigues (Mycological Progress, 2018)

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

Omics-based responses induced by bosentan in human hepatoma HepaRG cell cultures - Robim M. Rodrigues; Laxmikanth Kollipara; Umesh Chaudhari; Agapios Sachinidis; René P. Zahedi; Albert Sickmann; Annette Kopp-Schneider; Xiaoqi Jiang; Hector Keun; Jan Hengstler; Marlies Oorts; Pieter Annaert; et al. (Archives of Toxicology, 2018)

Historical stability promoted higher functional specialization and originality in Neotropical stream fish assemblages - Carlos A.S. Rodrigues‐Filho; Rafael P. Leitão; Jansen Zuanon; Jorge I. Sánchez‐Botero; Fabricio B. Baccaro (Journal of Biogeography, 2018)
Aim Disturbances are events that influence the structure of biological assemblages, yet how historical disturbances have affected the functional structure of recent assemblages is still poorly known. We used species functional traits to investigate the effects of historical disturbances, such as past climate change (aridification), on the current structure of stream fish assemblages. Location Amazon Basin and Brazilian Northeast streams. Methods We used measures of functional specialization and originality to assess the effects of historical disturbances on the structure of fish assemblages in streams with similar local environmental conditions in each biome (Amazonia and Caatinga). For this, we measured 15 traits related to locomotion, feeding and habitat use for each species sampled. We then compared the functional structure of each assemblage expressed as functional richness (FRic) and evenness (FEve) between biomes. We also used structured and random simulations of species extinctions to identify the influence of the loss of original and specialized species due to historical disturbance. Results We found high levels of functional specialization in Amazonia (historically more stable) and redundancy in Caatinga (higher frequency of historical disturbances) regional assemblages, regardless of the inter‐biome differences in species richness. These results were also detected in local assemblages, suggesting that the effect of historical disturbances influences the structure of fish assemblages, both at small and large spatial scales. Main conclusions The historical stability in Amazonian fish assemblages may have favoured a higher taxonomic and FRic, as well as greater functional specialization and originality, compared to Caatinga assemblages. Our results reinforce the importance of understanding and evaluating the evolutionary history of ecosystems in order to describe the current functional structure of species assemblages.

Electrodialytic treatment of sewage sludge: influence on microbiological community - Paula Guedes; Nazaré Couto; Joana Almeida; António M. Rodrigues; Eduardo P. Mateus; Alexandra B. Ribeiro (International Journal of Environmental Science and Technology, 2018)

Fungal Endophyte Communities in Begonia Species from the Brazilian Atlantic Rainforest - Ana M. L. Correia; Simone P. Lira; Marco A. Assis; Andre Rodrigues (Current Microbiology, 2018)

Embryonic and larval development and fatty‐acid profile of Epinephelus marginatus spawned in captivity: tools applied to captive rearing - P. H. Mello; B. C. Araújo; M. F. Campos; J. A. Rodrigues‐Filho; C. E. O. Garcia; R. G. Moreira (Journal of Fish Biology, 2018)
Development, ontogeny of the digestive system and the fatty‐acid (FA) profile, were analysed during development of Epinephelus marginatus . Larvae were analysed 7 and 17 days post fertilization (dpf) to evaluate fatty‐acid profile and morphological variables, respectively. Epinephelus marginatus larvae have relatively slow development of digestive structures, but were able to capture, ingest and digest prey by 5 dpf. Eggs were composed of high percentages of polyunsaturated fatty acids (PUFA) in phospholipids. The percentage of n3 PUFAs was higher than n6, especially docosahexaenoic acid (DHA), which exhibited higher levels compared with other marine species during the first 3 days of development, both in terms of phospholipids and triglycerides. The larvae present a high content of docosahexaenoic acid–eicosapentaenoic acid (DHA–EPA) and, during this phase, live food of small size was required (copepods or SS‐strain Brachionus rotundiformes ), enriched with DHA–EPA. These results may guide future studies on the contribution of FAs required during this stage of the life cycle of E. marginatus , to advance knowledge of the use of these FAs throughout ontogeny and contribute to the culture of this species commercial production or restocking.

Author Correction: Ouabain attenuates ovalbumin-induced airway inflammation - José Guilherme F. M. Galvão; Luiz Henrique Agra Cavalcante-Silva; Deyse Cristina M. Carvalho; Laércia Karla D. P. Ferreira; Talissa Mozzini Monteiro; Adriano Francisco Alves; Larissa Adiles M. P. Ferreira; Francisco Allysson A. F. Gadelha; Marcia Regina Piuvezam; Sandra Rodrigues-Mascarenhas (Inflammation Research, 2018)

Pesticide dichorvos induces early solid Ehrlich tumoral development associated with a non-protective pro-inflammatory response - Marcela Rodrigues de Camargo; Pedro Vinicius Teruya Akamine; James Venturini; Maria Sueli P. de Arruda; Carla Adriene da Silva Franchi (Environmental Science and Pollution Research, 2018)

Tingenone, a pentacyclic triterpene, induces peripheral antinociception due to cannabinoid receptors activation in mice - C. C. Veloso; R. C. M. Ferreira; V. G. Rodrigues; L. P. Duarte; A. Klein; I. D. Duarte; T. R. L. Romero; A. C. Perez (Inflammopharmacology, 2018)

Feline immudeficiency virus subtypes B and A in cats from São Luis, Maranhão, Brazil - Nathálya dos S. Martins; Ana Paula de S. Rodrigues; Luciana A. da Luz; Luana da L. dos Reis; Renata M. de Oliveira; Rudson A. de Oliveira; Ana Lucia Abreu-Silva; Jenner Karlisson P. dos Reis; Ferdinan A. Melo (Archives of Virology, 2018)

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

Discovery of potential neurodegenerative inhibitors in Alzheimer’s disease by casein kinase 1 structure-based virtual screening - Ricardo P. Rodrigues; Carlos H. T. P. da Silva (Medicinal Chemistry Research, 2017)

Organosulfur compound protects against memory decline induced by scopolamine through modulation of oxidative stress and Na+/K+ ATPase activity in mice - Fernanda D. da Silva; Mikaela P. Pinz; Renata L. de Oliveira; Karline C. Rodrigues; Francine R. Ianiski; Mariana M. Bassaco; Claudio C. Silveira; Cristiano R. Jesse; Silvane S. Roman; Ethel A. Wilhelm; Cristiane Luchese (Metabolic Brain Disease, 2017)

Role of Dynein Axonemal Heavy Chain 6 Gene Expression as a Possible Biomarker for Huntington’s Disease: a Translational Study - Lorena B. Areal; Lorraine P. Pereira; Fabiola M. Ribeiro; Isabella G. Olmo; Marcelo R. Muniz; Maria do Carmo Rodrigues; Patrik F. Costa; Cristina Martins-Silva; Stephen S. G. Ferguson; Daniela A. M. Guimarães; Rita G. W. Pires (Journal of Molecular Neuroscience, 2017)

Ouabain attenuates ovalbumin-induced airway inflammation - José Guilherme F. M. Galvão; Luiz Henrique Agra Cavalcante-Silva; Deyse Cristina M. Carvalho; Laércia Karla D. P. Ferreira; Talissa Mozzini Monteiro; Adriano Francisco Alves; Larissa Adilis M. P. Ferreira; Francisco Allysson A. F. Gadelha; Marcia Regina Piuvezam; Sandra Rodrigues-Mascarenhas (Inflammation Research, 2017)

The carboxylic acid transporters Jen1 and Jen2 affect the architecture and fluconazole susceptibility of Candida albicans biofilm in the presence of lactate - Rosana Alves; Sandra Mota; Sónia Silva; Célia F. Rodrigues; Alistair J. P. Brown; Mariana Henriques; Margarida Casal; Sandra Paiva (Biofouling, 2017)

Physiological responses of reared sea bream ( Sparus aurata Linnaeus, 1758) to an Amyloodinium ocellatum outbreak - M Moreira; D Schrama; F Soares; T Wulff; P Pousão‐Ferreira; P Rodrigues (Journal of Fish Diseases, 2017)
Amyloodiniosis represents a major bottleneck for semi‐intensive aquaculture production in Southern Europe, causing extremely high mortalities. Amyloodinium ocellatum is a parasitic dinoflagellate that can infest almost all fish, crustacean and bivalves that live within its ecological range. Fish mortalities are usually attributed to anoxia, associated with serious gill hyperplasia, inflammation, haemorrhage and necrosis in heavy infestations; or with osmoregulatory impairment and secondary microbial infections due to severe epithelial damage in mild infestation. However, physiological information about the host responses to A. ocellatum infestation is scarce. In this work, we analysed the proteome of gilthead sea bream ( Sparus aurata ) plasma and relate it with haematological and immunological indicators, in order to enlighten the different physiological responses when exposed to an A. ocellatum outbreak. Using 2D‐ DIGE , immunological and haematological analysis and in response to the A. ocellatum contamination we have identified several proteins associated with acute‐phase response, inflammation, lipid transport, homoeostasis, and osmoregulation, wound healing, neoplasia and iron transport. Overall, this preliminary study revealed that amyloodiniosis affects some fish functional pathways as revealed by the changes in the plasma proteome of S. aurata, and that the innate immunological system is not activated in the presence of the parasite.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

MPP+-Lesioned Mice: an Experimental Model of Motor, Emotional, Memory/Learning, and Striatal Neurochemical Dysfunctions - Mauricio P. Cunha; Francis L. Pazini; Vicente Lieberknecht; Josiane Budni; Ágatha Oliveira; Júlia M. Rosa; Gianni Mancini; Leidiane Mazzardo; André R. Colla; Marina C. Leite; Adair R. S. Santos; Daniel F. Martins; et al. (Molecular Neurobiology, 2017)

Creatine Prevents Corticosterone-Induced Reduction in Hippocampal Proliferation and Differentiation: Possible Implication for Its Antidepressant Effect - Francis L. Pazini; Mauricio P. Cunha; Dayane Azevedo; Julia M. Rosa; André Colla; Jade de Oliveira; Ana B. Ramos-Hryb; Patricia S. Brocardo; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2017)

Atorvastatin Protects from Aβ1–40-Induced Cell Damage and Depressive-Like Behavior via ProBDNF Cleavage - Fabiana K. Ludka; Maurício P. Cunha; Tharine Dal-Cim; Luisa Bandeira Binder; Leandra C. Constantino; Caio M. Massari; Wagner C. Martins; Ana Lúcia S. Rodrigues; Carla I. Tasca (Molecular Neurobiology, 2017)

The mating system of the symbiotic pea-crab Dissodactylus crinitichelis (Brachyura, Pinnotheridae): monogamy or promiscuity? - Douglas Fernandes Rodrigues Alves; Gustavo Luis Hirose; Samara de P. Barros-Alves; J. Antonio Baeza (Marine Biology, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Signaling pathways underlying the antidepressant-like effect of inosine in mice - Filipe Marques Gonçalves; Vivian Binder Neis; Débora Kurrle Rieger; Mark William Lopes; Isabella A. Heinrich; Ana Paula Costa; Ana Lúcia S. Rodrigues; Manuella P. Kaster; Rodrigo Bainy Leal (Purinergic Signalling, 2017)

Tauroursodeoxycholic Acid Enhances Mitochondrial Biogenesis, Neural Stem Cell Pool, and Early Neurogenesis in Adult Rats - Rita Soares; Filipa F. Ribeiro; Sara Xapelli; Tânia Genebra; Maria F. Ribeiro; Ana M. Sebastião; Cecília M. P. Rodrigues; Susana Solá (Molecular Neurobiology, 2017)

Entropy theory for analysing water resources in northeastern region of Brazil - Vicente de P. Rodrigues da Silva; Adelgicio F. Belo Filho; Vijay P. Singh; Rafaela S. Rodrigues Almeida; Bernardo B. da Silva; Inajá F. de Sousa; Romildo Morant de Holanda (Hydrological Sciences Journal, 2017)

Copper effect in petroleum hydrocarbons biodegradation by microorganisms associated to Juncus maritimus: role of autochthonous bioaugmentation - I. P. F. M. Montenegro; A. P. Mucha; I. Reis; P. Rodrigues; C. M. R. Almeida (International Journal of Environmental Science and Technology, 2017)

Detecting deforestation impacts in Southern Amazonia rainfall using rain gauges - Nathan S. Debortoli; Vincent Dubreuil; Marina Hirota; Saulo Rodrigues Filho; Diego P. Lindoso; Jean Nabucet (International Journal of Climatology, 2017)
During the last decades, several climate‐modelling studies have forecasted a decrease in precipitation in Southern Amazonia, projecting scenarios of a drier Amazon for the future in relation with deforestation (or forest cover). In this area, only a limited number of analyses using forest cover data and rainfall time series have considered the transitional zones between the Amazon Forest and the Cerrado biome. In this work, we evaluated whether forest cover and rainfall patterns are correlated. The analysis encompassed rainfall times series from 207 rain gauges during the 1971–2010 period, and forest cover data acquired from LANDSAT5 satellite images. The results indicate that, at local level (1–15 km), both seasonal and annual precipitation values are not correlated to forest cover, whereas at the regional scale (30–50 km) contrasting to annual values, significant correlation occurs between forest cover and seasonal precipitation. Additionally, the study suggests that the larger the forest areas, the greater the probabilities of those influencing precipitation at regional scale, in opposite direction to the observed local level effects.

Benthic dinoflagellate blooms in tropical intertidal rock pools: elucidation of photoprotection mechanisms - J. S. Patil; R. V. Rodrigues; P. Paul; K. Sathish; M. Rafi; A. C. Anil (Marine Biology, 2017)

Assessing in vivo digestibility and effects on immune system of sheep fed alfalfa hay supplemented with a fixed amount of Ulva rigida and Gracilaria vermiculophylla - Ana R. J. Cabrita; Alexandra Correia; Ana R. Rodrigues; Paulo P. Cortez; Manuel Vilanova; António J.M. Fonseca (Journal of Applied Phycology, 2017)

Preparation of Extruded Snacks with Flavored Flour Obtained from the Carcasses of Nile Tilapia: Physicochemical, Sensory, and Microbiological Analysis - Alex P. Justen; Maria Luiza Rodrigues de Souza; Antonio R. G. Monteiro; Jane M. G. Mikcha; Eliane Gasparino; Ádina B. Delbem; Maria Regina B. de Carvalho; Ana P. Del Vesco (Journal of Aquatic Food Product Technology, 2017)

Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. C. Gonçalves; G. V. Tolesano; V. S. Rodrigues; M. P. J. Szabó (Tropical Animal Health and Production, 2017)

Caffeine Reverts Memory But Not Mood Impairment in a Depression-Prone Mouse Strain with Up-Regulated Adenosine A2A Receptor in Hippocampal Glutamate Synapses - Nuno J. Machado; Ana Patrícia Simões; Henrique B. Silva; Ana Paula Ardais; Manuella P. Kaster; Pedro Garção; Diana I. Rodrigues; Daniela Pochmann; Ana Isabel Santos; Inês M. Araújo; Lisiane O. Porciúncula; Ângelo R. Tomé; et al. (Molecular Neurobiology, 2017)

Pramipexole, a Dopamine D2/D3 Receptor-Preferring Agonist, Prevents Experimental Autoimmune Encephalomyelitis Development in Mice - Vicente Lieberknecht; Stella C. Junqueira; Mauricio P. Cunha; Thaís A. Barbosa; Luiz F. de Souza; Igor S. Coelho; Adair R. S. Santos; Ana Lúcia S. Rodrigues; Alcir L. Dafré; Rafael C. Dutra (Molecular Neurobiology, 2017)

Synthesis, antimicrobial activity and cytotoxic investigation of novel trifluoromethylated tetrazolo[1,5-a]pyrimidines - Elisandra Scapin; Clarissa P. Frizzo; Leticia V. Rodrigues; Geórgia C. Zimmer; Rodrigo A. Vaucher; Michelle R. Sagrillo; Janice L. Giongo; Carlos A. M. Afonso; Patrícia Rijo; Nilo Zanatta; Helio G. Bonacorso; Marcos A. P. Martins (Medicinal Chemistry Research, 2017)

3-D distribution of the radioelements in the granitic rocks of northern and central Portugal and geothermal implications - R. Lamas; M. M. Miranda; A. J. S. C. Pereira; L. J. P. F. Neves; N. Ferreira; N. V. Rodrigues (Journal of Iberian Geology, 2017)

Exceptional Symmetry by Genomic Word - Vera Afreixo; João M. O. S. Rodrigues; Carlos A. C. Bastos; Ana H. M. P. Tavares; Raquel M. Silva (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Adaptative processes, control measures, genetic background, and resilience of malaria vectors and environmental changes in the Amazon region - W. P. Tadei; I. B. Rodrigues; M. S. Rafael; R. T. M. Sampaio; H. G. Mesquita; V. C. S. Pinheiro; J. A. C. Zequi; R. A. Roque; J. M. M. dos Santos (Hydrobiologia, 2017)

Bacteria and fungi inactivation by photocatalysis under UVA irradiation: liquid and gas phase - Caio Rodrigues-Silva; Sandra M. Miranda; Filipe V. S. Lopes; Mário Silva; Márcia Dezotti; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar; Eugénia Pinto (Environmental Science and Pollution Research, 2017)

Selection and Characterization of Bacillus thuringiensis (Berliner) (Eubacteriales: Bacillaceae) Strains for Ecdytolopha aurantiana (Lima) (Lepidoptera: Tortricidae) Control - J Zorzetti; A P S Ricietto; F A P Fazion; A M Meneguim; P M O J Neves; L A Vilas-Boas; R B Rodrigues; G T Vilas-Bôas (Neotropical Entomology, 2017)

A method for collecting eggs of Pseudocapillaria tomentosa (Nematoda: Capillariidae) from zebrafish Danio rerio and efficacy of heat and chlorine for killing the nematode's eggs - M L Martins; V Watral; J P Rodrigues‐Soares; M L Kent (Journal of Fish Diseases, 2017)
Pseudocapillaria tomentosa is a common pathogen of zebrafish ( Danio rerio ) in research facilities. We developed a method to collect and concentrate the nematode eggs using a modified sugar centrifugation method and documented their normal development. Embryonating stages with blastomere formation followed by elongation of the embryo prior to larva formation cumulated in developed larvae inside the eggs and hatching after 5–10 day. We then evaluated the efficacy of heat and chlorine to kill them based on a larva development assay. Eggs were exposed to 40, 50, 60 °C for 30 min and 1 h. Chlorine treatment was performed at 100, 250, 500, 1000, 3000 and 6000 ppm for 10 min. Samples exposed to 40 °C for 30 min or 1 h showed incidences of larvated eggs similar to controls. In contrast, no larvation occurred with eggs exposed to either 50 or 60 °C for 30 min or 1 h. Remarkably, in repeated assays, samples exposed to low doses of chlorine (100, 250, 500 and 1000 ppm for 10 min) showed significantly higher incidence of larvation than controls. Eggs treated with 3000 ppm for 10 min did not develop larvae, and no eggs were found after 6000 ppm treatment.

Creatine, Similar to Ketamine, Counteracts Depressive-Like Behavior Induced by Corticosterone via PI3K/Akt/mTOR Pathway - Francis L. Pazini; Mauricio P. Cunha; Julia M. Rosa; André R. S. Colla; Vicente Lieberknecht; Ágatha Oliveira; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2016)

Microbial diversification of Diels–Alder cycloadducts by whole cells of Penicillium brasilianum - Zia Ud Din; Taicia P. Fill; M. Carolina Donatoni; Carolina A. A. dos Santos; Timothy J. Brocksom; E. Rodrigues-Filho (Molecular Diversity, 2016)

Diet‐related gut bacterial dysbiosis correlates with impaired development, increased mortality and Nosema disease in the honeybee ( Apis mellifera ) - Patrick W. Maes; Pedro A. P. Rodrigues; Randy Oliver; Brendon M. Mott; Kirk E. Anderson (Molecular Ecology, 2016)
Dysbiosis, defined as unhealthy shifts in bacterial community composition, can lower the colonization resistance of the gut to intrinsic pathogens. Here, we determined the effect of diet age and type on the health and bacterial community composition of the honeybee ( Apis mellifera ). We fed newly emerged bees fresh or aged diets, and then recorded host development and bacterial community composition from four distinct regions of the hosts’ digestive tract. Feeding fresh pollen or fresh substitute, we found no difference in host mortality, diet consumption, development or microbial community composition. In contrast, bees fed aged diets suffered impaired development, increased mortality and developed a significantly dysbiotic microbiome. The consumption of aged diets resulted in a significant reduction in the core ileum bacterium Snodgrassella alvi and a corresponding increase in intrinsic pathogen Frischella perrara . Moreover, the relative abundance of S. alvi in the ileum was positively correlated with host survival and development. The inverse was true for both F. perrara and Parasacharibacter apium . Collectively, our findings suggest that the early establishment of S. alvi is associated with healthy nurse development and potentially excludes F. perrara and P. apium from the ileum. Although at low abundance, establishment of the common midgut pathogen Nosema spp. was significantly associated with ileum dysbiosis and associated host deficiencies. Moreover, dysbiosis in the ileum was reflected in the rectum, mouthparts and hypopharyngeal glands, suggesting a systemic host effect. Our findings demonstrate that typically occurring alterations in diet quality play a significant role in colony health and the establishment of a dysbiotic gut microbiome.

Effect of petroleum hydrocarbons in copper phytoremediation by a salt marsh plant (Juncus maritimus) and the role of autochthonous bioaugmentation - I. P. F. M. Montenegro; A. P. Mucha; I. Reis; P. Rodrigues; C. M. R. Almeida (Environmental Science and Pollution Research, 2016)

Prevalence of the genus Cladosporium on the integument of leaf-cutting ants characterized by 454 pyrosequencing - A. P. M. Duarte; M. Ferro; A. Rodrigues; M. Bacci; N. S. Nagamoto; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2016)

Whole genome and exome sequencing realignment supports the assignment of KCNJ12, KCNJ17, and KCNJ18 paralogous genes in thyrotoxic periodic paralysis locus: functional characterization of two polymorphic Kir2.6 isoforms - Rolf M. Paninka; Diego R. Mazzotti; Marina M. L. Kizys; Angela C. Vidi; Hélio Rodrigues; Silas P. Silva; Ilda S. Kunii; Gilberto K. Furuzawa; Manoel Arcisio-Miranda; Magnus R. Dias-da-Silva (Molecular Genetics and Genomics, 2016)

High efficacy on diclofenac removal by activated carbon produced from potato peel waste - M. Bernardo; S. Rodrigues; N. Lapa; I. Matos; F. Lemos; M. K. S. Batista; A. P. Carvalho; I. Fonseca (International Journal of Environmental Science and Technology, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Modulation of aquaporins 3 and 9 after exposure of ovine ovarian tissue to cryoprotectants followed by in vitro culture - A. D. Sales; A. B. G. Duarte; R. R. Santos; K. A. Alves; L. F. Lima; G. Q. Rodrigues; I. R. Brito; C. H. Lobo; J. B. Bruno; Y. Locatelli; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Research, 2016)

Involvement of PI3K/Akt Signaling Pathway and Its Downstream Intracellular Targets in the Antidepressant-Like Effect of Creatine - Mauricio P. Cunha; Josiane Budni; Fabiana K. Ludka; Francis L. Pazini; Julia Macedo Rosa; Ágatha Oliveira; Mark W. Lopes; Carla I. Tasca; Rodrigo B. Leal; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2016)

Advantages and limitations of chemical extraction tests to predict mercury soil-plant transfer in soil risk evaluations - R. J. R. Monteiro; S. M. Rodrigues; N. Cruz; B. Henriques; A. C. Duarte; P. F. A. M. Römkens; E. Pereira (Environmental Science and Pollution Research, 2016)

Aspects of fish conservation in the upper Patos Lagoon basin - N. F. Fontoura; J. P. Vieira; F. G. Becker; L. R. Rodrigues; L. R. Malabarba; U. H. Schulz; O. O. Möller; A. M. Garcia; F. S. Vilella (Journal of Fish Biology, 2016)
The Patos Lagoon basin is a large (201 626 km 2 ) and complex drainage system in southern Brazil. The lagoon is 250 km long and 60 km wide, covering an area of 10 360 km 2 . The exchange of water with the Atlantic Ocean occurs through a 0·8 km wide and 15 m deep inlet, fixed by 4 km long jetties, at the southernmost part of the Patos Lagoon. The estuarine area is restricted to its southern portion (10%), although the upper limit of saline waters migrates seasonally and year to year, influenced by the wind regime and river discharge. The known number of recorded limnetic fish species is 200, but this number is expected to increase. A higher endemism is observed in fish species occurring in upper tributaries. The basin suffers from the direct impact of almost 7 million inhabitants, concentrated in small to large cities, most with untreated domestic effluents. There are at least 16 non‐native species recorded in natural habitats of the Patos Lagoon basin, about half of these being from other South American river basins. Concerning the fishery, although sport and commercial fisheries are widespread throughout the Patos Lagoon basin, the lagoon itself and the estuarine area are the main fishing areas. Landing statistics are not available on a regular basis or for the whole basin. The fishery in the northern Patos Lagoon captures 31 different species, nine of which are responsible for most of the commercial catches, but only three species are actually sustaining the artisanal fishery: the viola Loricariichthys anus : 455 kg per 10 000 m 2 gillnet per day, the mullet Mugil liza : 123 kg per 10 000 m 2 gillnet per day and the marine catfish Genidens barbus : 50 kg per 10 000 m 2 gillnet per day. A decline of the fish stocks can be attributed to inadequate fishery surveillance, which leads to overfishing and mortality of juveniles, or to decreasing water quality because of urban and industrial activities and power production. Global climatic changes also represent a major threat to the Patos system by changing the frequency of El Niño‐La Niña‐Southern Oscillation ( ENSO ).

Leaf water potential and sap flow as indicators of water stress in Crimson ‘seedless’ grapevines under different irrigation strategies - S. Shahidian; P. Valverde; R. Coelho; A. Santos; M. Vaz; A. Rato; J. Serrano; S. Rodrigues (Theoretical and Experimental Plant Physiology, 2016)

“Watching the Detectives” report of the general assembly of the EU project DETECTIVE Brussels, 24–25 November 2015 - Ruani N. Fernando; Umesh Chaudhari; Sylvia E. Escher; Jan G. Hengstler; Jürgen Hescheler; Paul Jennings; Hector C. Keun; Jos C. S. Kleinjans; Raivo Kolde; Laxmikanth Kollipara; Annette Kopp-Schneider; Alice Limonciel; et al. (Archives of Toxicology, 2016)

Mating system and pollen dispersal in Eugenia dysenterica (Myrtaceae) germplasm collection: tools for conservation and domestication - Eduardo B. Rodrigues; Rosane G. Collevatti; Lázaro J. Chaves; Lucas R. Moreira; Mariana P. C. Telles (Genetica, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Nellore cattle (Bos indicus) and ticks within the Brazilian Pantanal: ecological relationships - Vanessa N. Ramos; Ubiratan Piovezan; Ana Helena A. Franco; Vinicius S. Rodrigues; Santiago Nava; Matias P. J. Szabó (Experimental and Applied Acarology, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Changes in Cd and Zn bioavailability upon an experimental resuspension of highly contaminated coastal sediments from a tropical estuary - Christiane N. Monte; Ana P. C. Rodrigues; Renato C. Cordeiro; Aline S. Freire; Ricardo E. Santelli; W. Machado (Sustainable Water Resources Management, 2015)

The biology and ecology of the Antarctic limpet Nacella concinna - Cecilia N. K. Suda; Gannabathula S. Vani; Mariana Feijó de Oliveira; Edson Rodrigues; Edson Rodrigues; Helena P. Lavrado (Polar Biology, 2015)

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

The Size But not the Symmetry of the Wings of Eulaema nigrita Lepeletier (Apidae: Euglossini) is Affected by Human-Disturbed Landscapes in the Brazilian Cerrado Savanna - N S Pinto; D P Silva; J G Rodrigues; P De Marco (Neotropical Entomology, 2015)

Oxidative stress markers in fish (Astyanax sp. and Danio rerio) exposed to urban and agricultural effluents in the Brazilian Pampa biome - D. G. Costa-Silva; M. E. M Nunes; G. L. Wallau; I. K. Martins; A. P. P Zemolin; L. C. Cruz; N. R. Rodrigues; A. R. Lopes; T. Posser; J. L. Franco (Environmental Science and Pollution Research, 2015)

Intensive cattle browsing did not prevent fallow recuperation on smallholder grass-capoeira pastures in the NE-Amazon - Stefan Hohnwald; Barbara Rischkowsky; John M. King; Ari P. Camarão; José A. Rodrigues Filho; Thorsten Zeppenfeld (Agroforestry Systems, 2015)

Respecification of structural equation models for the P cycle in tropical soils - M. V. S. Sales; A. C. Gama-Rodrigues; N. B. Comerford; W. P. Cropper; E. F. Gama-Rodrigues; P. H. G. Oliveira (Nutrient Cycling in Agroecosystems, 2015)

Sabotaging Behavior and Decision-Making in Larvae of the Queen Butterfly Danaus gilippus - Pedro P. S. Ferreira; Daniela Rodrigues (Journal of Insect Behavior, 2015)

Creatine, similarly to ketamine, affords antidepressant-like effects in the tail suspension test via adenosine A1 and A2A receptor activation - Mauricio P. Cunha; Francis L. Pazini; Julia M. Rosa; Ana B. Ramos-Hryb; Ágatha Oliveira; Manuella P. Kaster; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2015)

Cholesterol 24S-Hydroxylase Overexpression Inhibits the Liver X Receptor (LXR) Pathway by Activating Small Guanosine Triphosphate-Binding Proteins (sGTPases) in Neuronal Cells - Miguel Moutinho; Maria João Nunes; Anita Q. Gomes; Maria João Gama; Angel Cedazo-Minguez; Cecília M. P. Rodrigues; Ingemar Björkhem; Elsa Rodrigues (Molecular Neurobiology, 2015)

MicroRNA-34a Modulates Neural Stem Cell Differentiation by Regulating Expression of Synaptic and Autophagic Proteins - Ana L. Morgado; Joana M. Xavier; Pedro A. Dionísio; Maria F. C. Ribeiro; Raquel B. Dias; Ana M. Sebastião; Susana Solá; Cecília M. P. Rodrigues (Molecular Neurobiology, 2015)

Assessing families’ and patients’ attitudes toward brain donation for research purposes in a Brazilian population sample - M. K. Fonseca; E. Rodrigues-Neto; A. S. R. Costa; M. A. B. C. Rockembach; R. S. Padilha; L. L. Fernandez; F. H. Oliveira; L. P. Garcia; A. Hilbig (Cell and Tissue Banking, 2015)

The effect of conventional mechanical periodontal treatment on red complex microorganisms and clinical parameters in Down syndrome periodontitis patients: a pilot study - M. H. Tanaka; T. O. Rodrigues; L. S. Finoti; S. R. L. Teixeira; M. P. A. Mayer; R. M. Scarel-Caminaga; E. M. A. Giro (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Current knowledge on biotin nutrition in fish and research perspectives - Rodrigue Yossa; Pallab K. Sarker; Donald M. Mock; Santosh P. Lall; Grant W. Vandenberg (Reviews in Aquaculture, 2015)
Biotin, a water‐soluble vitamin, is essential for normal growth, development and health of all animals. In terrestrial animal nutrition, biotin has recently spurred scientific interest because of the increasing body of knowledge on biotin involvement in gene expression, cell cycle and reproduction in mammals, and recent advances in molecular biology techniques allowing a more effective estimation of biotin effects in metabolism and physiology. In contrast, this information is scarce in aquatic animal nutrition, as studies have essentially focused on the estimation of minimum biotin requirement for maximum growth and tissue storage as well as for the formulation of least‐cost diet. This scarcity of information is also due to the lack of well‐established indicators of biotin status in aquatic organisms. The present review is a comparative analysis of current knowledge on biotin physiology and nutritional biochemistry in terrestrial and aquatic animal nutrition. Also, general information on biotin sources, bioavailability, deficiency and requirement in mammals and fish is provided in order to plan further studies. In the future, biotin nutrition studies in aquaculture should also include haematological parameters, histopathology of the gills, liver and kidney, gonad development, gamete quality and quantity, fecundity, larvae survival and gene expression. Dietary biotin requirement levels should be estimated at every life history stage of farmed fish. The potential contribution of intestinal microflora to biotin supply in different fish species should be investigated. All this information will allow a better understanding of the essentiality of biotin in fish growth, development, reproduction and health.

Oysters as hot spots for mimivirus isolation - Kétyllen R. Andrade; Paulo P. V. M. Boratto; Felipe P. Rodrigues; Lorena C. F. Silva; Fábio P. Dornas; Mariana R. Pilotto; Bernard La Scola; Gabriel M. F. Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2015)

Ichthyofauna of the Selvagens Islands. Do small coastal areas show high species richness in the northeastern Atlantic? - Frederico Almada; David Abecasis; David Villegas-Ríos; Sofia Henriques; Miguel P. Pais; Marisa Batista; Bárbara Horta e Costa; Joana Martins; Inês Tojeira; Nuno Vasco Rodrigues; Ricardo Araújo; Miguel Souto; et al. (Marine Biology Research, 2015)

Solar photocatalytic gas-phase degradation of n-decane—a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda; Filipe V. S. Lopes; Caio Rodrigues-Silva; Susana D. S. Martins; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

Population dynamics of Aceodromus convolvuli (Acari: Mesostigmata: Blattisociidae) on spontaneous plants associated with Jatropha curcas in central Brazil - Wilton P. Cruz; Renato A. Sarmento; Marçal Pedro-Neto; Adenir V. Teodoro; Diego M. Rodrigues; Gilberto J. de Moraes (Experimental and Applied Acarology, 2014)

The Impact of Uranium Mine Contamination of Soils on Plant Litter Decomposition - Ana C. Freitas; Dina Rodrigues; Teresa A. P. Rocha-Santos; Fernando Gonçalves; Armando C. Duarte; Ruth Pereira (Archives of Environmental Contamination and Toxicology, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Description of a strain from an atypical population of Aspergillus parasiticus that produces aflatoxins B only, and the impact of temperature on fungal growth and mycotoxin production - Arita C; Calado T; Venâncio A; Lima N; Rodrigues P (European Journal of Plant Pathology, 2014)

Mercury Bioaccumulation in the Egyptian Mongoose (Herpestes ichneumon): Geographical, Tissue, Gender and Age Differences - S. Rodrigues; J. P. Coelho; V. Bandeira; T. Barros; A. C. Duarte; C. Fonseca; M. E. Pereira (Water, Air, & Soil Pollution, 2014)

A deep-water crinoid Leptometra celtica bed off the Portuguese south coast - Paulo Fonseca; Fátima Abrantes; Ricardo Aguilar; Aida Campos; Marina Cunha; Daniel Ferreira; Teresa P. Fonseca; Silvia García; Victor Henriques; Margarida Machado; Ariadna Mechó; Paulo Relvas; et al. (Marine Biodiversity, 2014)

Are seed germination and ecological breadth associated? Testing the regeneration niche hypothesis with bromeliads in a heterogeneous neotropical montane vegetation - Andréa Rodrigues Marques; Allbens P. F. Atman; Fernando A. O. Silveira; José Pires de Lemos-Filho (Plant Ecology, 2014)

Light and temperature induce variations in the density and ultrastructure of the secretory spaces in the diesel-tree (Copaifera langsdorffii Desf.—Leguminosae) - T. M. Rodrigues; P. F. S. M. Buarque; A. G. Coneglian; D. C. Reis (Trees, 2014)

Cold impact and acclimation response of Coffea spp. plants - J. C. Ramalho; F. M. DaMatta; A. P. Rodrigues; P. Scotti-Campos; I. Pais; P. Batista-Santos; F. L. Partelli; A. Ribeiro; F. C. Lidon; A. E. Leitão (Theoretical and Experimental Plant Physiology, 2014)

Resveratrol Induces Pro-oxidant Effects and Time-Dependent Resistance to Cytotoxicity in Activated Hepatic Stellate Cells - Leo A. Meira Martins; Bárbara P. Coelho; Guilherme Behr; Letícia F. Pettenuzzo; Izabel C. C. Souza; José Cláudio F. Moreira; Radovan Borojevic; Carmem Gottfried; Fátima Costa Rodrigues Guma (Cell Biochemistry and Biophysics, 2014)

Increasing the Added-Value of Onions as a Source of Antioxidant Flavonoids: A Critical Review - M. R. Pérez-Gregorio; J. Regueiro; J. Simal-Gándara; A. S. Rodrigues; D. P. F. Almeida (Critical Reviews in Food Science and Nutrition, 2014)

Evaluation of dihydroisocoumarins produced by the endophytic fungus Arthrinium state of Apiospora montagnei against Schistosoma mansoni - Henrique P. Ramos; Marilia R. Simão; Julia M. de Souza; Lizandra G. Magalhães; Vanderlei Rodrigues; Sérgio R. Ambrósio; Suraia Said (Natural Product Research, 2013)

Effect of forced aeration on citric acid production by Aspergillus sp. mutants in SSF - Cristine Rodrigues; Luciana P. S. Vandenberghe; Wilerson Sturm; Dario E. A. Dergint; Michele Rigon Spier; Júlio Cesar de Carvalho; Carlos R. Soccol (World Journal of Microbiology and Biotechnology, 2013)

Effect of ultraviolet-B radiation in laboratory on morphological and ultrastructural characteristics and physiological parameters of selected cultivar of Oryza sativa L. - Sérgio L. de Almeida; Éder C. Schmidt; Debora Tomazi Pereira; Marianne Kreusch; Marthiellen R. de L. Felix; Luz K. P. Osorio; Roberta de Paula Martins; Alexandra Latini; Fernanda Ramlov; Fungyi Chow; Marcelo Maraschin; Ana C. Rodrigues; et al. (Protoplasma, 2013)

Amyloid β Peptides Promote Autophagy-Dependent Differentiation of Mouse Neural Stem Cells - Maria B. Fonseca; Susana Solá; Joana M. Xavier; Pedro A. Dionísio; Cecília M. P. Rodrigues (Molecular Neurobiology, 2013)

Interaction of warm acclimation, low salinity, and trophic fluoride on plasmatic constituents of the Antarctic fish Notothenia rossii Richardson, 1844 - E. Rodrigues; M. Feijó-Oliveira; G. S. Vani; C. N. K. Suda; C. S. Carvalho; L. Donatti; H. P. Lavrado; E. Rodrigues (Fish Physiology and Biochemistry, 2013)

Amoebas as mimivirus bunkers: increased resistance to UV light, heat and chemical biocides when viruses are carried by amoeba hosts - Paulo V. M. Boratto; Fábio P. Dornas; Kétyllen R. Andrade; Rodrigo Rodrigues; Felipe Peixoto; Lorena C. F. Silva; Bernard La Scola; Adriana Oliveira Costa; Gabriel Magno Freitas de Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2013)

Humpback whales washed ashore in southeastern Brazil from 1981 to 2011: stranding patterns and microbial pathogens survey - Jailson F. Moura; Dália P. Rodrigues; Emily M. Roges; Roberta L. Souza; Paulo H. Ott; Maurício Tavares; Leila S. Lemos; Davi C. Tavares; Salvatore Siciliano (Biologia, 2013)

The antidepressant-like effect of inosine in the FST is associated with both adenosine A1 and A2A receptors - Manuella P. Kaster; Josiane Budni; Marta Gazal; Mauricio P. Cunha; Adair R. S. Santos; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2013)

Systematics of spiny‐backed treefrogs ( H ylidae: O steocephalus ): an A mazonian puzzle - Karl‐Heinz Jungfer; Julián Faivovich; José M. Padial; Santiago Castroviejo‐Fisher; Mariana M. Lyra; Bianca V. M. Berneck; Patricia P. Iglesias; Philippe J. R. Kok; Ross D. MacCulloch; Miguel T. Rodrigues; Vanessa K. Verdade; Claudia P. Torres Gastello; et al. (Zoologica Scripta, 2013)
Spiny‐backed tree frogs of the genus O steocephalus are conspicuous components of the tropical wet forests of the A mazon and the G uiana S hield. Here, we revise the phylogenetic relationships of O steocephalus and its sister group T epuihyla , using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of O steocephalus with respect to T epuihyla , (ii) the placement of ‘ H yla’ warreni as sister to T epuihyla , (iii) the non‐monophyly of several currently recognized species within O steocephalus and (iv) the presence of low ( O . taurinus and O . oophagus ) for the 16 S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of O steocephalus and T epuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of O steocephalus . The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for O steocephalus . We recognize and define five monophyletic species groups within O steocephalus , synonymize three species of O steocephalus ( O . germani , O . phasmatus and O . vilmae ) and three species of T epuihyla ( T . celsae , T . galani and T . talbergae ) and reallocate three species ( H yla helenae to O steocephalus , O . exophthalmus to T epuihyla and O . pearsoni to D ryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within O steocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described.

Soil attributes and leaf nitrogen estimating sugar cane quality parameters: Brix, pol and fibre - F. A. Rodrigues; P. S. G. Magalhães; H. C. J. Franco (Precision Agriculture, 2013)

Comparing kinematic changes between a finger-tapping task and unconstrained finger flexion–extension task in patients with Parkinson’s disease - W. P. Teo; J. P. Rodrigues; F. L. Mastaglia; G. W. Thickbroom (Experimental Brain Research, 2013)

Genetic and QTL analyses of yield and a set of physiological traits in pepper - N. A. Alimi; M. C. A. M. Bink; J. A. Dieleman; M. Nicolaï; M. Wubs; E. Heuvelink; J. Magan; R. E. Voorrips; J. Jansen; P. C. Rodrigues; G. W. A. M. van der Heijden; A. Vercauteren; et al. (Euphytica, 2013)

Isolation and characterization of 18 microsatellites for Lycengraulis grossidens (Pisces: Clupeiformes) - Ana C. G. Mai; João P. Vieira; Alicia A. Plavan; Marcelo F. Nobrega; Leonardo E. Moraes; Fábio L. Rodrigues; Luis F. Marins (Conservation Genetics Resources, 2013)

Development of Probiotic Tablets Using Microparticles: Viability Studies and Stability Studies - J. P. Sousa e Silva; Sérgio C. Sousa; Paulo Costa; Emília Cerdeira; Maria H. Amaral; José Sousa Lobo; Ana M. Gomes; Maria M. Pintado; Dina Rodrigues; Teresa Rocha-Santos; Ana C. Freitas (AAPS PharmSciTech, 2013)

Synthetic Condensed 1,4-naphthoquinone Derivative Shifts Neural Stem Cell Differentiation by Regulating Redox State - Daniela M. Santos; Maria M. M. Santos; Rui Moreira; Susana Solá; Cecília M. P. Rodrigues (Molecular Neurobiology, 2013)

Derivation of soil to plant transfer functions for metals and metalloids: impact of contaminant’s availability - S. M. Rodrigues; E. Pereira; A. C. Duarte; P. F. A. M. Römkens (Plant and Soil, 2012)

Spread of an OmpK36-modified ST15 Klebsiella pneumoniae variant during an outbreak involving multiple carbapenem-resistant Enterobacteriaceae species and clones - Â. Novais; C. Rodrigues; R. Branquinho; P. Antunes; F. Grosso; L. Boaventura; G. Ribeiro; L. Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Endoplasmic Reticulum Enrollment in Alzheimer’s Disease - Ricardo J. S. Viana; Ana F. Nunes; Cecília M. P. Rodrigues (Molecular Neurobiology, 2012)

Tauroursodeoxycholic Acid Prevents MPTP-Induced Dopaminergic Cell Death in a Mouse Model of Parkinson’s Disease - M. Castro-Caldas; A. Neves Carvalho; E. Rodrigues; C. J. Henderson; C. R. Wolf; C. M. P. Rodrigues; M. J. Gama (Molecular Neurobiology, 2012)

Driving Apoptosis-relevant Proteins Toward Neural Differentiation - Susana Solá; Márcia M. Aranha; Cecília M. P. Rodrigues (Molecular Neurobiology, 2012)

Long-Term Power Transmission Failures in Southeastern Brazil and the Geophysical Environment - Magda A. S. Duro; Pierre Kaufmann; Fernando C. P. Bertoni; Emilio C. N. Rodrigues; José Pissolato Filho (Surveys in Geophysics, 2012)

Revising the M235T Polymorphism Position for the AGT Gene and Reporting a Modifying Variant in the Brazilian Population with Potential Cardiac and Neural Impact - R. R. Lemos; S. G. de Lima; J. E. Gomes da Cunha; D. F. Oliveira; M. B. Rodrigues de Souza; C. F. J. Ayres; M. F. P. M. Albuquerque; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

Influence of soil water content and atmospheric conditions on leaf water potential in cv. “Touriga Nacional” deep-rooted vineyards - P. Rodrigues; V. Pedroso; J. P. Gouveia; S. Martins; C. Lopes; I. Alves (Irrigation Science, 2012)

Cardiovascular Responses to Bothrops alternatus (Urutu) Snake Venom in Anesthetized Dogs - Lourdes Dias; Mariana A. P. Rodrigues; Adriana Smaal; André L. Rennó; Sueli M. Mello; Heitor Moreno; Stephen Hyslop (Cardiovascular Toxicology, 2012)

First record of a whale shark Rhincodon typus in continental Europe - N. V. Rodrigues; J. P. S. Correia; J. T. C. Graça; F. Rodrigues; R. Pinho; M. Hirofumi (Journal of Fish Biology, 2012)
A whale shark Rhincodon typus was found in a set‐net in southern Portugal in October 2011. This was the first record for continental Europe and represents an increase of the species' known range. Upwelling events and increase in sea‐surface temperatures are possible reasons for this occurrence.

Reproductive isolation between diploid and tetraploid cytotypes of Libidibia ferrea (= Caesalpinia ferrea) (Leguminosae): ecological and taxonomic implications - Laís Angélica Borges; Luiz Gustavo Rodrigues Souza; Marcelo Guerra; Isabel Cristina Machado; Gwilym P. Lewis; Ariadna Valentina Lopes (Plant Systematics and Evolution, 2012)

TUDCA, a Bile Acid, Attenuates Amyloid Precursor Protein Processing and Amyloid-β Deposition in APP/PS1 Mice - Ana F. Nunes; Joana D. Amaral; Adrian C. Lo; Maria B. Fonseca; Ricardo J. S. Viana; Zsuzsanna Callaerts-Vegh; Rudi D’Hooge; Cecília M. P. Rodrigues (Molecular Neurobiology, 2012)

Overexpression of inducible 70-kDa heat shock protein in mouse improves structural and functional recovery of skeletal muscles from atrophy - Elen H. Miyabara; Tabata L. Nascimento; Débora C. Rodrigues; Anselmo S. Moriscot; Wilmer F. Davila; Younss AitMou; Pieter P. deTombe; Ruben Mestril (Pflügers Archiv - European Journal of Physiology, 2012)

Estimation of Small Reservoir Storage Capacities with Remote Sensing in the Brazilian Savannah Region - Lineu N. Rodrigues; Edson E. Sano; Tammo S. Steenhuis; Denílson P. Passo (Water Resources Management, 2012)

The dual crop coefficient approach using a density factor to simulate the evapotranspiration of a peach orchard: SIMDualKc model versus eddy covariance measurements - T. A. Paço; M. I. Ferreira; R. D. Rosa; P. Paredes; G. C. Rodrigues; N. Conceição; C. A. Pacheco; L. S. Pereira (Irrigation Science, 2012)

Hg transfer from contaminated soils to plants and animals - S. M. Rodrigues; B. Henriques; A. T. Reis; A. C. Duarte; E. Pereira; P. F. A. M. Römkens (Environmental Chemistry Letters, 2012)

The habitat vegetational structure and the success of the blue alcon, Maculinea alcon (Denis & Schiffermüller) - P. O. Soares; A. L. Crespi; M. C. Rodrigues; P. S. Arnaldo (Plant Biosystems, 2012)

Post-exercise depression in corticomotor excitability after dynamic movement: a general property of fatiguing and non-fatiguing exercise - W. P. Teo; J. P. Rodrigues; F. L. Mastaglia; G. W. Thickbroom (Experimental Brain Research, 2012)

Breeding Habitat and Landscape Correlates of Frog Diversity and Abundance in a Tropical Agricultural Landscape - Fernando Rodrigues da Silva; James P. Gibbs; Denise de Cerqueira Rossa-Feres (Wetlands, 2011)

Vascular endothelial growth factor-A165 (VEGF-A165) stimulates the in vitro development and oocyte competence of goat preantral follicles - V. R. Araújo; G. M. Silva; A. B. G. Duarte; D. M. Magalhães; A. P. Almeida; R. F. B. Gonçalves; J. B. Bruno; T. F. P. Silva; C. C. Campello; A. P. R. Rodrigues; J. R. Figueiredo (Cell and Tissue Research, 2011)

Ultrastructural changes during early infection of Vigna unguiculata and Phaseolus vulgaris leaves by Xanthomonas axonopodis pv. phaseoli and an unexpected association between chloroplast and mitochondrion - André de O. Carvalho; Maura Da Cunha; Rosana Rodrigues; Cláudia P. Sudré; Izabela S. Santos; Kátia V. S. Fernandes; Guilherme R. Rabelo; Valdirene M. Gomes (Acta Physiologiae Plantarum, 2011)

Analysis of the activation mechanism of Pseudomonas stutzeri cytochrome c peroxidase through an electron transfer chain - P. M. Paes de Sousa; D. Rodrigues; C. G. Timóteo; M. L. Simões Gonçalves; G. W. Pettigrew; I. Moura; J. J. G. Moura; M. M. Correia dos Santos (JBIC Journal of Biological Inorganic Chemistry, 2011)

Kanagawa-Negative, tdh- and trh-Positive Vibrio parahaemolyticus Isolated from Fresh Oysters Marketed in Fortaleza, Brazil - Regine H. S. F. Vieira; Renata A. Costa; Francisca G. R. Menezes; Giselle C. Silva; Grace N. D. Theophilo; Dália P. Rodrigues; Rodrigo Maggioni (Current Microbiology, 2011)

A new race of Puccinia psidii defeats rust resistance in eucalypt - Rodrigo N. Graça; Cristina P. Aun; Lúcio M. S. Guimarães; Bruno V. A. Rodrigues; Edival A. V. Zauza; Acelino C. Alfenas (Australasian Plant Pathology, 2011)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Variation in Nectar and Pollen Availability, Sucrose Preference, and Daily Response in the Use of Flowers by Heliconius erato phyllis - Elisete A. Barp; Geraldo L. G. Soares; Erica J. M. Giani; Daniela Rodrigues; Gilson R. P. Moreira (Journal of Insect Behavior, 2011)

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Performance and meat quality traits of beef heifers fed with two levels of concentrate and ruminally undegradable protein - Marcio de Souza Duarte; Pedro Veiga Rodrigues Paulino; Sebastião de Campos Valadares Filho; Mario Fonseca Paulino; Edenio Detmann; Joanis Tilemahos Zervoudakis; João Paulo Ismerio dos Santos Monnerat; Gabriel da Silva Viana; Luiz Henrique P. Silva; Nicola Vergara Lopes Serão (Tropical Animal Health and Production, 2011)

Base excision repair genes XRCC1 and APEX1 and the risk for prostate cancer - H. Kuasne; I. S. Rodrigues; R. Losi-Guembarovski; M. B. Reis; P. E. Fuganti; E. P. Gregório; F. Libos Junior; H. M. Matsuda; M. A. F. Rodrigues; M. O. Kishima; I. M. S. Cólus (Molecular Biology Reports, 2011)

Spectrofluorimetric Determination of Coumarin in Commercial Tablets - Mirian Marcolan; Priscila Alfonso Martins; Valber A. Pedrosa; Maira R. Rodrigues; Hueder P. M. de Oliveira; Lucia Codognoto (Journal of Fluorescence, 2011)

Use of Multi-Sensor Data to Identify and Map Tropical Coastal Wetlands in the Amazon of Northern Brazil - Suzan Waleska P. Rodrigues; Pedro Walfir M. Souza-Filho (Wetlands, 2011)

Unraveling new genes associated with seed development and metabolism in Bixa orellana L. by expressed sequence tag (EST) analysis - Virgínia L. F. Soares; Simone M. Rodrigues; Tahise M. de Oliveira; Talisson O. de Queiroz; Lívia S. Lima; Braz T. Hora-Júnior; Karina P. Gramacho; Fabienne Micheli; Júlio C. M. Cascardo; Wagner C. Otoni; Abelmon S. Gesteira; Marcio G. C. Costa (Molecular Biology Reports, 2011)

Molecular characterization of a miraculin-like gene differentially expressed during coffee development and coffee leaf miner infestation - Jorge Maurício Costa Mondego; Melina Pasini Duarte; Eduardo Kiyota; Leandro Martínez; Sandra Rodrigues de Camargo; Fernanda P. De Caroli; Beatriz Santos Capela Alves; Sandra Maria Carmello Guerreiro; Maria Luiza Vilela Oliva; Oliveiro Guerreiro-Filho; Marcelo Menossi (Planta, 2011)

Wheat resistance to leaf blast mediated by silicon - M. S. Xavier Filha; F. A. Rodrigues; G. P. Domiciano; H. V. Oliveira; P. R. Silveira; W. R. Moreira (Australasian Plant Pathology, 2011)

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Isolation and characterization of 13 tetranucleotide microsatellite loci in the Stone marten (Martes foina) - Mafalda P. Basto; Mónica Rodrigues; Margarida Santos-Reis; Michael W. Bruford; Carlos A. Fernandes (Conservation Genetics Resources, 2010)

Seroprevalence of orthopoxvirus in an Amazonian rural village, Acre, Brazil - B. E. F. Mota; G. S. Trindade; T. C. Diniz; M. da Silva-Nunes; E. M. Braga; M. Urbano-Ferreira; G. O. L. Rodrigues; C. A. Bonjardim; P. C. P. Ferreira; E. G. Kroon (Archives of Virology, 2010)

Growth of Hydrilla verticillata (L.f.) Royle under controlled conditions - I. Bianchini; M. B. Cunha-Santino; J. A. M. Milan; C. J. Rodrigues; J. H. P. Dias (Hydrobiologia, 2010)

Biodiversity of the urban homegardens of São Luís city, Northeastern Brazil - Festus Kehinde Akinnifesi; Gudeta W. Sileshi; Oluyede C. Ajayi; Adetutu I. Akinnifesi; Emanoel G. de Moura; Jairo F. P. Linhares; Ivanilde Rodrigues (Urban Ecosystems, 2010)

Carbon Storage in Soil Size Fractions Under Two Cacao Agroforestry Systems in Bahia, Brazil - Emanuela F. Gama-Rodrigues; P. K. Ramachandran Nair; Vimala D. Nair; Antonio C. Gama-Rodrigues; Virupax C. Baligar; Regina C. R. Machado (Environmental Management, 2010)

A method for detecting false bifurcations in dynamical systems: application to neural-field models - Serafim Rodrigues; David Barton; Frank Marten; Moses Kibuuka; Gonzalo Alarcon; Mark P. Richardson; John R. Terry (Biological Cybernetics, 2010)

Transitions to spike-wave oscillations and epileptic dynamics in a human cortico-thalamic mean-field model - Serafim Rodrigues; David Barton; Robert Szalai; Oscar Benjamin; Mark P. Richardson; John R. Terry (Journal of Computational Neuroscience, 2009)

Butyltin levels in several Portuguese coastal areas - Pedro N. Carvalho; Pedro Nuno R. Rodrigues; M. Clara P. Basto; M. Teresa S. D. Vasconcelos (Environmental Monitoring and Assessment, 2009)

Isolation and characterization of microsatellites loci for “piramutaba” (Brachyplatystoma vaillantii, Siluriformes: Pimelodidae), one of the commercially most important migratory catfishes in the Amazon Basin - Fabiola C. Rodrigues; Izeni P. Farias; Jacqueline S. Batista; José Alves-Gomes (Conservation Genetics Resources, 2009)

Mercury pollution in Ria de Aveiro (Portugal): a review of the system assessment - M. E. Pereira; A. I. Lillebø; P. Pato; M. Válega; J. P. Coelho; C. B. Lopes; S. Rodrigues; A. Cachada; M. Otero; M. A. Pardal; A. C. Duarte (Environmental Monitoring and Assessment, 2009)

Synthesis and antimalarial activities of optically active labdane-type diterpenes - José Villamizar; Jean P. Pittelaud; Juan R. Rodrigues; Neira Gamboa; Nieves Canudas; Eleonora Tropper; Franklin Salazar; Juan Fuentes (Natural Product Research, 2009)

Rapid slowing of maximal finger movement rate: fatigue of central motor control? - Julian P. Rodrigues; Frank L. Mastaglia; Gary W. Thickbroom (Experimental Brain Research, 2009)

Assessment of high-level gentamicin and glycopeptide-resistant Enterococcus faecalis and E. faecium clonal structure in a Portuguese hospital over a 3-year period - R. Mato; F. Almeida; R. Pires; P. Rodrigues; T. Ferreira; I. Santos-Sanches (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Effects of the Papaya meleira virus on papaya latex structure and composition - Silas P. Rodrigues; Maura Da Cunha; José A. Ventura; Patricia Machado Bueno Fernandes (Plant Cell Reports, 2009)

Identification of predator–prey relationships between coccinellids and Saissetia oleae (Hemiptera: Coccidae), in olive groves, using an enzyme-linked immunosorbent assay - Sónia A. P. Santos; José A. Pereira; Maria da Conceição Rodrigues; Laura M. Torres; Ana Maria N. Pereira; António J. A. Nogueira (Journal of Pest Science, 2009)

A role for atorvastatin and insulin combination in protecting from liver injury in a model of type 2 diabetes with hyperlipidemia - P. Matafome; E. Nunes; T. Louro; C. Amaral; J. Crisóstomo; L. Rodrigues; A. R. Moedas; P. Monteiro; A. Cipriano; R. Seiça (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Extraction recoveries and stability of diarrhetic shellfish poisoning (DSP) toxins in naturally contaminated samples - S.M. Rodrigues; P. Vale; M.J. Botelho; S.S. Gomes (Food Additives & Contaminants: Part A, 2009)

Assessment of a new lateral flow immunochromatographic (LFIC) assay for the okadaic acid group of toxins using naturally contaminated bivalve shellfish from the Portuguese coast - P. Vale; S.S. Gomes; J. Lameiras; S.M. Rodrigues; M.J. Botelho; M.V. Laycock (Food Additives & Contaminants: Part A, 2009)

Temperature-dependent development rates of Bracon vulgaris, a parasitoid of boll weevil - F. S. Ramalho; P. A. Wanderley; J. B. Malaquias; K. C. V. Rodrigues; J. V. S. Souza; J. C. Zanuncio (Phytoparasitica, 2009)

Foliar application of potassium silicate reduces the intensity of soybean rust - F. A. Rodrigues; H. S. S. Duarte; G. P. Domiciano; C. A. Souza; G. H. Korndörfer; L. Zambolim (Australasian Plant Pathology, 2009)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

Detection of Polymolecular Associations in Hydrophobized Chitosan Derivatives using Fluorescent Probes - Máira R. Rodrigues; Adriana Lima; Lúcia Codognoto; Antonio Balbin Villaverde; Marcos Tadeu Tavares Pacheco; Hueder P. Moisés de Oliveira (Journal of Fluorescence, 2008)

Resveratrol inhibits cell growth by inducing cell cycle arrest in activated hepatic stellate cells - Izabel C. Souza; Leo Anderson M. Martins; Barbara P. Coelho; Ivana Grivicich; Regina M. Guaragna; Carmem Gottfried; Radovan Borojevic; Fátima Costa Rodrigues Guma (Molecular and Cellular Biochemistry, 2008)

Effect of additives on the esterification activity of immobilized Candida antarctica lipase - Dasciana S. Rodrigues; George P. Cavalcante; Giovanilton F. Silva; Andrea L. O. Ferreira; Luciana R. B. Gonçalves (World Journal of Microbiology and Biotechnology, 2008)

Benefits of membrane electrodes in the electrochemistry of metalloproteins: mediated catalysis of Paracoccus pantotrophus cytochrome c peroxidase by horse cytochrome c: a case study - P. M. Paes de Sousa; S. R. Pauleta; D. Rodrigues; M. L. Simões Gonçalves; G. W. Pettigrew; I. Moura; J. J. G. Moura; M. M. Correia dos Santos (JBIC Journal of Biological Inorganic Chemistry, 2008)

Effect of the Herbicide Roundup® on Perkinsus olseni in vitro Proliferation and in vivo Survival when Infecting a Permissive Host, the Clam Ruditapes decussatus - L. M. Elandalloussi; R. B. Leite; P. M. Rodrigues; R. Afonso; M. L. Cancela (Bulletin of Environmental Contamination and Toxicology, 2008)

Attempts at a peptide vaccine against paracoccidioidomycosis, adjuvant to chemotherapy - Luiz R. Travassos; Elaine G. Rodrigues; Leo K. Iwai; Carlos P. Taborda (Mycopathologia, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Water tank and numerical model studies of flow over steep smooth two-dimensional hills - J. B. R. Loureiro; D. V. Soares; J. L. A. Fontoura Rodrigues; F. T. Pinho; A. P. Silva Freire (Boundary-Layer Meteorology, 2007)

Antiinflammatory effects of natural tetranortriterpenoids isolated from Carapa guianensis Aublet on zymosan-induced arthritis in mice - C. Penido; F. P. Conte; M. S. S. Chagas; C. A. B. Rodrigues; J. F. G. Pereira; M. G. M. O. Henriques (Inflammation Research, 2006)

Calculating derivatives for automatic history matching - José Roberto P. Rodrigues (Computational Geosciences, 2006)

Contamination Levels and Preliminary Assessment of the Technical Feasibility of Employing Natural Attenuation in 5 Priority Areas of Presidente Bernardes Refinery in Cubatão, São Paulo, Brazil - René P. Schneider; Sandra C. Morano; Maria Alejandra C. Gigena; Silvia K. Missawa; Rafael C. S. Rocha; Lucimara Rodrigues Da Silva; Nelson Ellert; Sérgio Kataoka; Carlos Katsuragi; Carlos Da Silva Rosa; Luiz Calixto De Oliveira Filho (Environmental Monitoring and Assessment, 2006)

Decreased Susceptibility to Nitroimidazoles Among Bacteroides Species in Brazil - Jessica Manya B. D. Vieira; Renata F. Boente; Karla Rodrigues Miranda; Kátia E. S. Avelar; Regina M. C. P. Domingues; Maria Candida de S. Ferreira (Current Microbiology, 2006)

Evaluation of Extracts Produced by Some Tropical Fungi as Potential Cholinesterase Inhibitors - Katia F. Rodrigues; Gisela L. Costa; Meriane P. Carvalho; Rosângela de A. Epifanio (World Journal of Microbiology and Biotechnology, 2005)

Influence of the time of occlusion on the quantitative parameters obtained by modelling trans-epidermal water loss curves to describe the human cutaneous barrier functionin vivo - P. C. Pinto; L. M. Rodrigues (Medical & Biological Engineering & Computing, 2005)

Modulation of endocytosis in pollen tube growth by phosphoinositides and phospholipids - D. Monteiro; P. Castanho Coelho; C. Rodrigues; L. Camacho; H. Quader; R. Malhó (Protoplasma, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE—Brazil III. Three legume trees in a semi-deciduous dry forest - A. Geßler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; P. J. F. P. Rodrigues; F. R. Scarano; H. Rennenberg (Trees, 2005)

Meiotic instability of chicken ultra-long telomeres and mapping of a 2.8 megabase array to the W-sex chromosome - K. L. Rodrigue; B. P. May; T. R. Famula; M. E. Delany (Chromosome Research, 2005)

Molecular marker-mediated validation of morphologically defined landraces of Pejibaye (Bactris gasipaes) and their phylogenetic relationships - Doriane P. Rodrigues; Spartaco Astolfi Filho; Charles R. Clement (Genetic Resources and Crop Evolution, 2005)

Element-Enrichment Factors in Lichens from Terceira, Santa Maria and Madeira Islands (Azores and Madeira Archipelagoes) - B. J. Vieira; M. C. Freitas; A. F. Rodrigues; A. M. G. Pacheco; P. M. Soares; N. Correia (Journal of Atmospheric Chemistry, 2004)

Effect of dietary iron overload on Photobacterium damselae ssp. piscicida pathogenicity in sea bass, Dicentrarchus labrax (L.) - P N S Rodrigues; F A Pereira (Journal of Fish Diseases, 2004)

First records of Fistularia petimba and Diodon eydouxii for the Azores, with notes on the occurrence of three additional species - J. M. N. Azevedo; P. M. Raposeiro; L. Rodrigues (Journal of Fish Biology, 2004)
Two new records of fishes from the Azores are reported: Fistularia petimba and Diodon eydouxii . The occurrence of Centracanthus cirrus, Decapterus macarellus and Priacanthus arenatus in Azorean waters is confirmed.

The genetics of non-host disease resistance in wheat to barley yellow rust - P. Rodrigues; J. M. Garrood; Q.-H. Shen; P. H. Smith; L. A. Boyd (Theoretical and Applied Genetics, 2004)

Vegetation structure descriptors regulating the presence of wild rabbit in the National Park of Peneda-Gers, Portugal - A. Monzn; P. Fernandes; N. Rodrigues (European Journal of Wildlife Research, 2004)

p53 dephosphorylation and p21Cip1/Waf1 translocation correlate with caspase-3 activation in TGF-β1-induced apoptosis of HuH-7 cells - G. Fan; X. Ma; P. Y. Wong; C. M. P. Rodrigues; C. J. Steer (Apoptosis, 2004)

Phase Transition of Thylakoid Membranes Modulates Photoinhibition in the Cyanobacterium Anabaena siamensis - Ricardo M. Chaloub; Luiz Mauro T. Silva; Marcoaurélio A. Rodrigues; Cesar P. Dos Santos (Photosynthesis Research, 2003)

Impairment of inflammatory response in adult rats submitted to maternal undernutrition during early lactation: Role of insulin and glucocorticoid - C. Barja-Fidalgo; E. P. G. Souza; S. V. Silva; A. L. Rodrigues; E. A. Anjos-Valotta; P. Sannomyia; M. S. DeFreitas; A. S. Moura (Inflammation Research, 2003)

Severe Disseminated Tuberculosis After Intravesical Instillation of Bacillus Calmette-Gurin - R. Proena; M. Toscano Rico; O. Cardoso; C. Salvado; P. Rodrigues; J. Machado (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Chromosomal studies in Callicebus donacophilus pallescens, with classic and molecular cytogenetic approaches: Multicolour FISH using human and Saguinus oedipus painting probes - R. M. S. Barros; C. Y. Nagamachi; J. C. Pieczarka; L. R. R. Rodrigues; M. Neusser; E. H. de Oliveira; J. Wienberg; J. A. P. C. Muniz; J. D. Rissino; S. Muller (Chromosome Research, 2003)

Hard X-ray microprobe studies of chromium(VI)-treated V79 Chinese hamster lung cells: intracellular mapping of the biotransformation products of a chromium carcinogen - Carolyn T. Dillon; Peter A. Lay; Brendan J. Kennedy; Anton P. Stampfl; Zhonghou Cai; Peter Ilinski; William Rodrigues; Daniel G. Legnini; Barry Lai; Jörg Maser (JBIC Journal of Biological Inorganic Chemistry, 2002)

The interhepatocytic macrophages and pale‐grey cells in brown trout liver ontogenesis - A. D. Resende; E. Rocha; R. A. F. Monteiro; P. Rodrigues (Journal of Fish Biology, 2002)
Pale‐grey cells appeared in the livers of healthy and non‐stressed brown trout Salmo trutta 3 weeks post‐hatching whereas interhepatocytic macrophages appeared at 5 months. Cells with intermediate morphological characteristics between those of pale‐grey cells and macrophages were identified in all ages studies. Cell ultrastructure supported the idea that pale‐grey cells probably belonged to the macrophage lineage, being eventual precursors of the active phagocytes residing amongst hepatocytes.

Shoot organogenesis and mass propagation of Coleus forskohlii from leaf derived callus - P. Sairam Reddy; Rosaline Rodrigues; Ram Rajasekharan (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Complementary representation and zones of ecological transition - K.J. Gaston; A.S.L. Rodrigues; B.J. Van Rensburg; P. Koleff; S.L. Chown (Ecology Letters, 2001)
Minimum complementary sets of sites that represent each species at least once have been argued to provide a nominal core reserve network and the starting point for regional conservation programs. However, this approach may be inadequate if there is a tendency to represent several species at marginal areas within their ranges, which may occur if high efficiency results from preferential selection of sites in areas of ecological transition. Here we use data on the distributions of birds in South Africa and Lesotho to explore this idea. We found that for five measures that are expected to reflect the location of areas of ecological transition, complementary sets tend to select higher values of these measures than expected by chance. We recommend that methods for the identification of priority areas for conservation that incorporate viability concerns be preferred to minimum representation sets, even if this results in more costly reserve networks.

Effects of xenoestrogen bisphenol A on uterine and pituitary weight, serum prolactin levels and immunoreactive prolactin cells in ovariectomized Wistar rats - Tatiana Goloubkova; Maria Flá via M. Ribeiro; Luciene P. Rodrigues; Ana L. Cecconello; Poli Mara Spritzer (Archives of Toxicology, 2000)

Air pollution and mortality in Madrid, Spain: a time-series analysis - J. C. Alberdi Odriozola; J. Díaz Jiménez; J. C. Montero Rubio; I. J. Mirón Pérez; M. S. Pajares Ortíz; P. Ribera Rodrigues (International Archives of Occupational and Environmental Health, 1998)

Elemental distribution in a sedimentary deposit on the shelf off the Tagus estuary (Portugal) - P. Paiva; J. -M. Jouanneau; F. Araújo; O. Weber; A. Rodrigues; J. M. A. Dias (Water, Air, & Soil Pollution, 1997)

Elemental Distribution in a Sedimentary Deposit on the Shelf Off the Tagus Estuary (Portugal) - P. Paiva; J.-M. Jouanneau; F. Araújo; O. Weber; A. Rodrigues; J.M.A. Dias (Water, Air, & Soil Pollution, 1997)

Sediment chemistry — Infaunal community structure in a southern European estuary related to solid-phase Microtox® toxicity testing - V. Quintino; A. M. Picado; A. M. Rodrigues; E. Mendonça; M. H. Costa; M. Bordalo Costa; P. Lindgaard-Jørgensen; T. H. Pearson (Aquatic Ecology, 1995)

Redefinition ofCandida Berkhout and the consequent emendation ofCryptococcus Kützing andRhodotorula Harrison - A. C. M. Weijman; L. Rodrigues de Miranda; J. P. Van Der Walt (Antonie van Leeuwenhoek, 1988)